Organic matter amendment regulates surface electrochemical properties of yellow soils: The major role of Alkyl C and O-Alkyl C - Xiaoshuai Song; Cheng Liang; Chenyang Liu; Lin Ning; Xiheng Lv; Wei Liu; Rena Yasin; Yunhang Luo; Jiangwen Li; Chenyang Xu; Wei Du; Wuquan Ding; et al. (Soil and Tillage Research, 2026)

Ecosystem-specific controls of denitrifier gene abundance and community composition on potential nitrous oxide emissions in upland and paddy soils - Xianchu Su; Guiping Ye; Hang-Wei Hu; Mengmeng Feng; Luyuan Sun; Yuheng Cheng; Zi-Yang He; Jia Liu; Yongxin Lin (Soil Ecology Letters, 2026)

De novo determination of fucose linkages in N-glycans using logically derived sequence tandem mass spectrometry - Jien-Lian Chen; Hsien-Wei Tseng; Chun-Cheng Lin; Chi-Kung Ni (Glycoconjugate Journal, 2026)

Late Cretaceous large-scale melting of the Neo-Tethyan oceanic slab in southern Tibet - Cheng Li; Lin Ma; Andrew C. Kerr; Qiang Wang; Zhiwei Yu; Wei Qiao (Lithos, 2026)

Mesozoic crustal thinning in the northern North China Craton: Evidence from Triassic and Jurassic plutons in the Huyu area, northwestern Beijing - Liang Qiu; Dan-Ping Yan; Jun-Ting Qiu; Wei Yang; Yiyu Lin; Suhua Cheng; Xiuhua Cao; Xuchao Chai; Pei Zhang; Lei Gao; Zeyilin Ma (Journal of Asian Earth Sciences, 2026)

Associations between early pregnancy essential metals and birth outcomes: Exploration of effect modification by maternal thyroid hormones - Xiao-Yu Zhao; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

A dual mechanical tuning framework for rigid pillared elastic metamaterials: Geometric reconfiguration and controllable prestress - Zu Shao; Tong Cheng; Yi Zhang; Wei Zhong Jiang; Zhu Kun Mi; Xiang Jie Wei; Xin Guo; Wang Lin Xiong; Kai Hao Lin; Chuang Li; Shu Hao Song; Cheng Shen; et al. (Engineering Structures, 2026)

An auxetic trampoline metamaterial with tunable bandgap under prestrain - Tong Cheng; Gui Lei Chen; Wei Zhong Jiang; Yi Zhang; Xiang Jie Wei; Zhu Kun Mi; Xiao Ji; Lin Hua; Jia Hui Zhang; Shu Hao Song; Cheng Shen; Xin Ren (Engineering Structures, 2026)

Engineered bacteria as ultrasound-responsive carbon monoxide vehicles for Cancer gas therapy and synergistic immunotherapy - Xiaorui Chen; Xiao Xiao; Wei Zhao; Bin Liu; Hongzhou Lian; He Ding; Piaoping Yang; Ping'an Ma; Lingjie Song; Shifang Luan; Ziyong Cheng; Jun Lin (Chemical Engineering Journal, 2026)

Integrated network pharmacology and experimental validation to elucidate the mechanism of WIN55,212–2 in mitigating sepsis-induced pulmonary fibrosis in mice - Quan He; Dei-xing Yang; Lin Duo; Tong-ling Shi; Yuan-wei Yang; Jie-cheng Li; Shu-ting Li; Shang-shang Zhu (Tissue and Cell, 2026)

Salinity shapes biofilm community to promote partial nitrification and sulfamethoxazole removal in membrane-aerated biofilm reactors - Zhi-Cheng Wu; Yu-Lin Han; Chen-Wei Zheng; He-Ping Zhao (Journal of Water Process Engineering, 2026)

Chemical-free closed-loop conversion of nitrate into struvite fertilizer via exsolved high-entropy perovskite electrocatalyst - Li-Hui Yang; Yi-Heng Liu; Si-Hao Lv; Man-Ting Liao; Hui Lin; Wei Li; Cao Yang; An-Qi Wang; Hao-Yi Cheng (Journal of Environmental Chemical Engineering, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Sedimentological and reservoir characteristics of Carboniferous–Permian shales in the northern Songliao Basin and surrounding areas, Northeastern China - Honggang Cheng; Deyong Li; Xuefeng Bai; Lin Jiang; Qinghua Huang; Dehai Wang; Hui Wang; Shujuan Xu; Xueqiong Wu; Wei Duan; Chengzao Jia (Journal of Asian Earth Sciences, 2026)

Unraveling the modulating mechanism of Maillard reaction gradients on structural properties and emulsifying stabilization of Prunus mume melanoidins - Wen-zhang Qian; Yi-xiao Xiao; Shou-wei Yin; Ji-cheng Chen; Jin-lin Guo; Shun Gao (Food Chemistry, 2026)

Synergistic magneto-aeration photocatalysis over AgI/TiO2/mrGO composite for high-salinity recalcitrant wastewater - Chunxia Zhao; Bingqian Wei; Feng Lin; Hongyang Xue; Yuxin Li; Miaomiao Cheng; Hongjie Wang (Chemical Engineering Journal, 2026)

Secondary growth enables post-healing of stress-induced cracks in 2D Zr-MOF membrane for enhanced water purification - Miaomiao Tian; Haochen Shen; Cheng Chen; Libo Zhao; Wei Yu; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

Interfacial energy homogenization enables β-phase transition and high piezoactivity in MOF/PVDF membrane for sustainable pollutant degradation - Zi Yang; Miaomiao Tian; Cheng Chen; Zhiyu Zhao; Libo Zhao; Jiujing Xu; Wei Yu; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

Mechanobiological antagonism of integrin β1/β3 gates YAP-driven reactionary dentinogenesis through fluid shear stress sensing - Peiqi Liu; Hui Zhang; Haoyu Wang; Jingning Gou; Lingxiang Lian; Bilun Jin; Yi Guo; Wei Gong; Chenxu Wang; Yijie Wang; Rui Zou; Bo Cheng; et al. (Chemical Engineering Journal, 2026)

Evolution of swine influenza surveillance and one health governance in Taiwan: from zoonotic risk management to integrated preparedness - Cheng-Han Lin; Tzu-Min Lin; Meng-Wei Lin; Chih-Sheng Lin (Veterinary Research Communications, 2026)

The influence of replacing soybean meal with corn gluten meal on the digestive and absorptive capacity and amino acid metabolism of sub-adult grass carp (Ctenopharyngodon idella) - Yan Liu; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Wen-Jie Tang; Cheng-Bo Zhong; Pei Wu (Aquaculture, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

Infragravity oscillations in a coupled-basin marina under typhoon conditions: physical model experiments and numerical modeling - Shih-Feng Su; Chia-Hsuan She; Jia-Lin Chen; Chen-Hsun Wei; Zhi-Cheng Huang (Ocean Engineering, 2026)

Evaluation and forecasting of habitat suitability and thermal growth responses in the mud clam Geloina coaxans under climate change - Bing-Xian Liu; Yu-Yang Zhang; Cheng-Rui Yan; Zhan-Wei Zhao; Ning Zhang; Lin-Xuan Ma; Xian-Bo Qiu; Yun-Wei Dong (Marine Environmental Research, 2026)

Non-contact discharge estimation using physics-informed neural networks and CNN-enhanced image velocimetry - Yen-Cheng Lin; Cheng-Wei Wu; Hao-Che Ho (Journal of Hydrology, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

Construction of MOF-decorated 3D printed membrane with hierarchical surface functionalization for oil-water separation: Role of interfacial energy barrier - Jingtao Hu; Zhiyu Zhao; Hua Li; Saleem Raza; Ying Liu; Cheng Chen; Wei Yu; Yanchao Xu; Hongjun Lin; Guanhua Jin; Liguo Shen (Journal of Hazardous Materials, 2026)

Optimization of sequential co-fermentation with Hanseniaspora opuntiae enhances aroma-active ester biosynthesis and sensory quality of rice beer - Wei-Ting Hung; Kai-Ler Ng; Yen-Tso Lai; Chang-Wei Hsieh; Chien-Hao Chen; Christoper Caesar Yudho Sutopo; Shella Permatasari Santoso; Kaemwich Jantama; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

PFOA promotes PMAIP1–MCL1 apoptotic vulnerability within a BHLHE41-associated macrophage regulatory architecture in atherosclerosis - Hou-liang Chen; Run Wang; Wei-jun Tao; Wang Zhang; Yan-lin Gao; Xiao-bing Cheng (Chemico-Biological Interactions, 2026)

First visualization of intact sperm storage tubules in the duck oviduct: A fluorescent labeling approach for targeted SST sampling - Hsiu-Lien Herbie Lin; Chin-Hui Su; Shih-Yi Huang; Ya-Hsin Kuo; Liang-Yuan Wei; Yi-Ying Chang; Ching-Wei Chang; Jeng-Fang Huang; Pascal Mermillod; Chih-Hsiang Cheng (Animal Reproduction Science, 2026)

Hydraulic conductivity and the associated xylem anatomy as reliable predictors of tree productivity for Populus species along the fast-slow spectrum - Attaullah Khan; Xue-Wei Gong; Jing-Jing Guo; Cheng-Lin Yuan; Shen-Hao Song; Zhong-Yi Pang; Yan-Hui Peng; Xue-Kai Sun; Guang-You Hao (Agricultural and Forest Meteorology, 2026)

Species-specific greenhouse gas emissions and carbon budgets in freshwater monoculture ponds - Zhao-Jun Yong; Wei-Jen Lin; Yao-Chen Lee; Yen-Cheng Liang; Shuenn-Der Yang; Hsing-Juh Lin (Aquaculture International, 2026)

New linear bromopyrrole-imidazolidine alkaloids from the Formosan sponge Agelas nakamurai - You-Cheng Lin; Atallah F. Ahmed; Chung-Wei Fu; Shu-Fen Chiou; Hui-Chun Wang; Ping-Jyun Sung; Jyh-Horng Sheu (Natural Product Research, 2026)

ROMO1 loss in cholinergic neurons induces mitochondrial ultrastructural damage and ALS-like neuromuscular degeneration - Wei Nie; Zhiwen Jing; Linling Cheng; Lin-Lin Li; Yuxiao Bai; Fengli Xu; Sihan Li; Limei Lin; Xiaohui Dong; Liping Yu; Lei Cai; Bingxing Pan; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Large-scale field measurement of a floating offshore wind turbine under realistic sea conditions - Pengxu Zou; Qiang Wang; Wei Lin; Yipin Cheng; Fujing Wang; Xiang Wang; Shilong Sun; Yongshuai Zhu; Baiwen Liu; Yiran Wang; Zheng Dong; Ming Lin (Ocean Engineering, 2026)

Comprehensive analysis of microbial community assembly and metabolic dynamics reveals the effects of environmental acidity on flavor formation pathways during the Zhejiang rosy vinegar fermentation process - Cheng-Hao Jin; Yong-Zhu Zhang; Wen-Tian Song; Peng Wang; Chang-Ling Wu; Lin-Mei Liang; Wei Feng; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2026)

Contrasting impacts of policy interventions and population mobility on organic aerosols and oxygenated volatile organic compounds in Beijing - Yu Zhang; Weiqi Xu; Wei Zhou; Jintai Lin; Mengying Wang; Yan Li; Siqi Zeng; Ziyi Zhang; Xiaomin Cheng; Yang Yang; Yele Sun (Environmental Pollution, 2026)

Identifying critical windows and sex-specific effects of periconceptional exposure to fine particulate matter and temperature on fetal growth trajectories: A longitudinal birth cohort study - Si-Wei Dai; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Xiao-Yu Zhao; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Non-overtly damaging cold atmospheric plasma induces adaptive epidermal molecular responses associated with integrin alpha 6 - Yu-Ping Cheng; Hua-Lin Chen; Yu-Hsuan Chen; Chang-Sheng Chen; Kuan-Wei Lee; Jong-Shinn Wu; Yun-Chien Cheng; Shih-Chang Lin; Jiun-Wen Guo (Chemico-Biological Interactions, 2026)

Study on pipeline structural integrity and wear mechanism during horizontal directional drilling pullback of submarine pipelines - Yungen He; Wang Jian; Yuqi Zhang; Minke Huang; Yanchuan Cheng; Bei Jiang; Ming Chen; Kehan Chen; Wei Lu; Rongsheng Lin (Marine Georesources & Geotechnology, 2026)

Artificial Intelligence and Protein Design: A retrospective study on 20-year emerging trends and core research areas from bibliometric perspectives - Wenjuan Zhao; Xiuwu Pan; Wei Yang; Zichang Liu; Xiyi Wei; Anqi Lin; Bufu Tang; Lin Zhang; Mingjia Xiao; Qing Zeng; Quan Cheng; Weiming Mou; et al. (Probiotics and Antimicrobial Proteins, 2026)

Trophic plasticity drives species-specific adaptive responses to seasonal variability in reef-building corals - Xiao-Lei Yu; Lei Jiang; Yong Luo; Lin-Tao Huang; Peng Zhang; Zhan-Wei Li; Cheng-Yue Liu; Pan Zhang; Jian-Yu Chen; Sheng Liu; Gui-Xin Dong; Hui Huang (Coral Reefs, 2026)

Elucidating targets and mechanisms of dietary mycotoxin carcinogenesis via network toxicology, pan-cancer analysis, and molecular simulation - Peng Lin; Wei Cheng; Xin Qi; Jing Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Two new chroman derivatives from the desert plant endophytic fungus Lasiodiplodia sp - Wen-Xiang Tao; Jin Ye; Lin-Ping Zhang; Le Zhang; Dong-Yang Liu; Xiu-Feng Yang; Tian-Cheng Ma; Yi Sun; Chang Zhang; Fan-Wei Liu; Ying Chen; Bo Song (Natural Product Research, 2026)

Ginsenoside Rb1 attenuates hyperoxia-induced lung injury in neonatal rats by inhibiting ferroptosis via the system Xc− pathway - Huidan Lian; Haiyu Zhou; Jie Dong; Junyi Qian; Yue Cheng; Jinyu Lou; Xinqi Zheng; Wei Lin; Danyun Jia (Toxicology and Applied Pharmacology, 2026)

Deciphering peroxydisulfate vs. peroxymonosulfate activation by biochar catalysts via explainable machine learning - Xiaochong Wang; Wei Zhang; Ruobing Cheng; Pengyuan Ma; Junhui Su; Mingyue Lin; Toru Murayama; Guangli Xiu (Journal of Hazardous Materials, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Magnetic field effects on methane–air combustion and emissions in an optical constant volume combustion chamber - Jhe-Kai Lin; Son Hoang Do; Wei-Cheng Wang; Chun-Hao Chiu; Po-Wei Chen; Thong Duc Hong (Fuel, 2026)

Scale up fermentation of Chenopodium formosanum dairy products with process optimization and evaluation of ACE inhibitory peptides and antioxidant activity - Chen-Che Hsieh; Jing-Rong Wu; Yi-Cheng Huang; Shin-Ping Lin; Jheng-Jhe Lu; Adyasa Barik; Shella Permatasari Santoso; Chang-Wei Hsieh; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2026)

Probabilistic predictions of the impacts of climate warming on permafrost stability along the Qinghai-Xizang Railway, China - Chengsong Yang; Guodong Cheng; Wei Wei; Lin Chen; Wenqiang Zhang; Xinbin Wang; Qihao Yu; Dan Wang (Cold Regions Science and Technology, 2026)

A comprehensive review on the chemical composition, pharmacological effects and quality evaluation of Gentiana straminea Maxim. - Yuan-Wen Zhuang; Min Wang; Jian-Tao Zhao; Yu-Qing Wang; Run-Qian Yu; Huan Xia; Xiao-Hong Wei; Peng-Cheng Lin; Gui-Yang Xia; Sheng Lin (Journal of Natural Medicines, 2026)

SAIR reconstruction method based on deep generalized unfolding network - Xiaocheng Yang; Zihan Hou; Weihao Cheng; Jingye Yan; Lin Wu; Mingfeng Jiang; Bo Wei (Advances in Space Research, 2026)

Effects of dietary Zn deficiency and excess on growth performance, glycolipid metabolism, and intestinal homeostasis of juvenile golden pompano (Trachinotus ovatus) - Hongkai Ye; Zhanzhan Wang; Jun Wang; Yun Wang; Zhong Huang; Wei Yu; Heizhao Lin; Zhenhua Ma; Zhenyan Cheng; Chuanpeng Zhou (Aquaculture International, 2026)

Gut microbiota profiles across intrinsic capacity strata in community-dwelling older adults using full-length 16S rRNA sequencing - Chi-Hsien Huang; I-Cheng Lu; Chi-Wei Lin; Ming-Ta Hsieh; I-Hui Chiang; Po-Hsuan Lai; I-Ting Liu; Jung-Sheng Chen (GeroScience, 2026)

A Large-Scale Micro-friction True Triaxial Apparatus for Analyzing the Failure Features of Coarse-Grained Soils Under Complex Stress Conditions - Jia-Jun Pan; Wei Zhao; Zhan-Lin Cheng; Yong-Zhen Zuo (Rock Mechanics and Rock Engineering, 2026)

Macro-micro mechanical properties and modified damage constitutive model of marine soil after cement reinforcement - Xiao-Hu Zhang; Jian-Min Yang; Han-Lin Wang; Cheng-Shuang Yin; Liu-Mei Wei; Wen-Han Yu; Kamchibek Kozhogulov (Marine Georesources & Geotechnology, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Orchestrated multicopper heterostructural motifs in MOF enable tandem CO2 valorization via photothermal-photocatalytic C–N coupling - Jian-Qiang Zhao; Hui-Li Zheng; Yu-Jia Cheng; Cheng-Xia Chen; Xiong-Feng Ma; Zheng Yin; Jia-Wei Li; Dong-Dong Ma; Hua Lin; Xin-Tao Wu; Cheng-Yong Su; Qi-Long Zhu (Science Bulletin, 2026)

Avermectin disrupts blood-brain barrier integrity in zebrafish larvae via the Wnt/β-catenin signaling pathway - Wei-Guo Wang; Lin-Jing Du; Huan-Ou Ma; Wen-Ping Xu; Li-Ming Tao; Zhong Li; Jia-Gao Cheng; Li Zhao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Dynamics of cavitation bubbles induced by whipping motion of flexible bodies with large deformation - Cheng Wang; Wei-Lin Xu; Yue Pan; Li-Xin Bai (Ocean Engineering, 2026)

Petrogenesis of Late Triassic adakitic rocks and basalts from the southern Lhasa: Insights into subduction initiation of Neo-Tethys - Cheng Li; Lin Ma; Andrew C. Kerr; Wei Dan; Qiang Wang; Zhiwei Yu; Wei Qiao; Rui Pu; Fan Yang (Lithos, 2026)

Process-intensified synthesis of sulfonated peanut shell char through dilute acid hydrolysis and low-temperature sulfonation–carbonization for Pb2 + removal - Maria Stefani; Kuan-Chen Cheng; Theresia Angeline Veronica; Shella Permatasari Santoso; Edward Hartman Ernest; Shin-Ping Lin; Jindrayani Nyoo Putro; Wiyanti Fransisca Simanullang; Hsien-Yi Hsu; Chang-Wei Hsieh; Suryadi Ismadji (Journal of Environmental Chemical Engineering, 2026)

Artificial intelligence-enabled flexible surface-enhanced Raman scattering substrate based on silver nanoparticles/polypyrrole/chitosan film for sensitive uric acid detection in saliva, serum and urine - Nazar Riswana Barveen; Petchi Raman Mariappan; Sathishkumar Chinnapaiyan; Yen-Yu Lin; Chih-Yu Kuo; Yu-Wei Cheng (Carbohydrate Polymers, 2026)

Transcarotid Artery Revascularization for Asymptomatic Carotid Stenosis: A Systematic Review and Meta-Analysis - Zhi-Cheng Jiang; Qi-Fei Hu; Jia-Ming Huang; Xian-Wei Wang; Tong Lin; Xi-Lin Gao; Jia-Wen Cui; Jing-Lin Zhao; Dong Chen; Shu-Peng Li (Translational Stroke Research, 2026)

Doxorubicin-Induced Cardiotoxicity in Breast Cancer: Mechanistic Pathways, Pharmacogenomic Modifiers, and Translational Strategies - Chi-Tong Kuok; Hao-Wei Lee; Chen-Yu Huang; Yu-Che Cheng; Shih-Chang Lin; Jiun-Wen Guo (Cardiovascular Toxicology, 2026)

Migration and enrichment of rare earth elements in a mining ion-adsorption type deposit tailings under ecological restoration - Zhuoling Lin; Longyong Lin; Sheng Cheng; Gaoling Wei; Yirong Deng; Junchun Li; Guangqing Huang (Applied Geochemistry, 2026)

Neutrophil extracellular traps in post-traumatic urethral microenvironment promote hypertrophic urethral stricture via the TLR9/NF-kB/Smad3/IL-8 axis - Ye-Hui Chen; Zhi-Bin Ke; Bo-Han Lin; Yi-Cheng Xu; Xue-Yi Xue; Qing-Shui Zheng; Xiong-Lin Sun; Yong Wei; Ying-Chun Liang; Ning Xu (Apoptosis, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Multiprotein-based nanomedicines with dual CD44/CD133 targeting and GSH-responsive drug release for improving cancer chemotherapy - Lu-Yi Yu; Pei-Wei Shueng; Yu-Hsin Wang; Yu-Wei Yen; Kuan-Wei Chen; Chieh-Ru Li; Hsin-Cheng Chiu; Yu-Wen Lin; Chun-Liang Lo (Drug Delivery and Translational Research, 2026)
Albumin, a highly biocompatible protein, has been utilized in the construction of anti-cancer drugs for the treatment of various cancers. However, albumin-based nanomedicines still face several clinical challenges, including low stability in the bloodstream, non-specific targeting ability, and lack of controlled release capability. To address these limitations, we developed a multiprotein-based nanomedicine for targeted chemotherapy of non-small cell lung cancer (NSCLC). This nanomedicine was assembled using a heart-shaped albumin and two Y-shaped anti-CD44 and anti-CD133 antibodies. To enhance stability and improve therapeutic efficacy, the multiproteins were crosslinked using disulfide bond linkers and loaded with paclitaxel and ceramide. This resulted in nanomedicines that exhibited responsiveness to glutathione (GSH) and demonstrated inhibition of tumor cancer cells and cancer stem cells (CSCs). Our experimental results indicated that the inclusion of anti-CD44 and anti-CD133 antibodies enhanced the targeting capability of nanomedicines towards cancer cells and CSCs in an in vitro study and the accumulation in both normoxic regions and hypoxic niches in in vivo tumor xenografts. The multiprotein-based nanomedicines also demonstrated GSH-dependent drug release behavior, induced apoptosis in cancer cells and CSCs, inhibited cell migration, and effectively suppressed NSCLC tumor growth. Overall, our findings presented a novel nanostructure created from differently shaped proteins for application in drug delivery. This multiprotein-based nanomedicines showed promising potential in addressing the limitations of albumin-based nanomedicines and may offer improved therapeutic outcomes for cancer treatment. Graphical Abstract

Detection method for missing seeding in plug trays for small vegetable seeds based on image registration - Wenqi Zhao; Xianliang Wang; Xiaona Lin; Xiangcai Zhang; Jiangtao Ji; Xiupei Cheng; Zhongcai Wei; Xiuhong Wang; Lei Liu (Computers and Electronics in Agriculture, 2026)

Ensemble learning: a study on the border inspection prediction model for high-risk products adulterated with Sudan Red in Taiwan - Li-Ya Wu; Wei-Chih Cheng; King-Fu Lin; Jia-Jhen Lee; Wen-Chou Lin; Hsu-Yang Lin; Chia-Yen Lu; Chih-Kang Chiang (Food Control, 2026)

Windows of susceptibility and the modifying role of residential greenness in the association between prenatal exposure to non-optimal temperatures and infant BMIZ trajectories - Zhen-Hua Li; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Xiao-Yu Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Introducing Double-Moment Warm Rain Physics into the Goddard 4ICE Microphysics Scheme - Kao-Shen Chung; Yu-Jyun Liou; Cheng-Rong You; Zhao-Cheng Zeng; Pay-Liam Lin; Donghai Wang; Wei-Kuo Tao; Stephen Lang; Takamichi Iguchi; Adrian Loftus; Jiun-Dar Chern (Asia-Pacific Journal of Atmospheric Sciences, 2026)
In this study, a new double-moment warm rain Goddard 4ICE scheme (GCEDM) is developed based on the Goddard 4ICE single-moment (GCESM) scheme and then tested using idealized 2D squall line and 3D supercell simulations. The addition of the total number concentrations for cloud water ( $$\:N_{TC}$$ ) and rainwater ( $$\:N_{TR}$$ ) enables this new scheme to simulate more diverse raindrop size distributions, making it more realistic. GCEDM has similar overall thermal and dynamic characteristics to GCESM but produces higher evaporation rates, predicted particle number concentrations, and mass mixing ratios than GCESM, leading to stronger cold pools than with GCESM. In addition, comparisons are made versus the Weather Research and Forecasting Model Double-Moment Microphysics 7-class scheme (WDM7), which was also improved from a single-moment 4-class ice scheme to a double-moment warm-rain scheme. WDM7 also shows a stronger cold pool, but the system characteristics and microphysical processes are quite different from the single-moment version of this scheme.

Machine Learning Approaches for Probabilistic Prediction of Coastal Freak Waves - Dong-Jiing Doong; Wei-Cheng Chen; Fan-Ju Lin; Chi Pan; Cheng-Han Tsai (Journal of Marine Science and Engineering, 2026)
Coastal freak waves (CFWs) are sudden and hazardous wave events that occur near shorelines and can pose serious threats to coastal visitors and infrastructure. Due to the complex interactions among coastal bathymetry, wave dynamics, and environmental conditions, the mechanisms governing CFW formation remain poorly understood, making reliable prediction difficult. This study investigates the feasibility of applying machine learning techniques to predict CFW occurrences using observational environmental data. Three machine learning algorithms, the Random Forest (RF), Support Vector Machine (SVM), and Artificial Neural Network (ANN), were developed to generate probability-based predictions of CFW events. Environmental variables derived from buoy observations, including wave characteristics, wind conditions, swell parameters, wave grouping indicators, and nonlinear wave interaction indices, were used as model inputs. Hyperparameters were optimized using grid search combined with k-fold cross-validation. The results show that all three models achieved comparable predictive performance, with AUC values close to 0.80 and overall prediction accuracy around 74%. The ANN model achieved the highest recall, indicating strong capability in detecting CFW events, while the RF and SVM models showed more balanced precision and recall. Analysis of high-probability prediction events suggests that CFW occurrences are associated with swell-dominated conditions, strong wave grouping behavior, and enhanced nonlinear wave interactions. These results demonstrate that machine learning provides a promising framework for probabilistic prediction of coastal freak waves and has potential applications in coastal hazard assessment and early warning systems.

The emerging role of high-throughput proteomics in advancing precision medicine - Jia You; Yue-Ting Deng; Luo Chen; Lin-Bo Wang; Yu Guo; Ze-Yu Li; Jian-Feng Feng; Jin-Tai Yu; Wei Cheng (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

Functional divergence of two ethylene receptor subfamilies in calcium permeability - Chenliang Pan; Junyuan Cheng; Zining Lin; Dongdong Hao; Zhina Xiao; Yuhang Ming; Peng You; Hongtao Yu; Wei Yan; Wen Song; Li Liu; Hongwei Guo (Molecular Plant, 2026)

Effective metal recovery from lithium-ion battery waste using a ternary deep eutectic solvent in a high solid-to-liquid ratio under mild and ambient conditions - Hsin-Jou Cheng; Yi-Jane Lin; Shu-Chi Chang; Shih-Yen Yang; Ting-Wei Lee; Chiaying Chen (Journal of Environmental Chemical Engineering, 2026)

Dual-function tara gum-based antiscalant with efficient antiscaling and antibacterial activity: Performance and molecular simulation investigation - Liping Xiong; Wei Yu; Xinyi Lu; Zhiyu Zhao; Cheng Chen; Renjie Li; Guanhua Jin; Leihong Zhao; Hongjun Lin; Liguo Shen (Journal of Environmental Chemical Engineering, 2026)

Label-efficient outdoor 3D object detection via single click annotation from LiDAR point cloud - Qiming Xia; Hongwei Lin; Wei Ye; Yadan Luo; Shijia Zhao; Hai Wu; Chenglu Wen; Cheng Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Effects of baking degree of Longjing green tea on flavor attributes, antioxidant activity and advanced glycation end products - Ran Wei; Xiao-Yu Zhong; Kayama Kayama; Yu-Hong Lin; Fang-Ting Qin; Zhu-Cheng Su; Yong-Quan Xu (Food Research International, 2026)

Long-term intercropping increases soil aggregate stability by altering soil colloid content and stability - Chuan-Lin Xiao; Jing-Ru He; Cheng-Bao Wang; Wei-Ping Zhang; Jun Mao; Peter Christie; Jian-Ying Shang; Long Li (Plant and Soil, 2026)

Unraveling iron and zinc efficiency in pepper: integration of root architecture, uptake kinetics, and transcriptional regulation - Cheng-Xiang Zhou; Wei Zhang; Bao-Gang Yu; Hao-Feng Yang; Yuan Wang; Kai Sun; Fu-Lin Zhao; Huai-Yu Yang; Prakash Lakshmanan; Xin-Ping Chen; Chun-Qin Zou (Plant and Soil, 2026)

Infra-slow body-surface potentials show a group-level association with thyroid cancer - Bohan Deng; Ruili Zhang; Yuxuan Liu; Jinglao Lin; Shicong Gui; Xihao Wei; Yin Cheng; Li Zheng; Shaohua Hu; Pingping Lyu; Yubo Li; Huafen Wang (Journal of Zhejiang University-SCIENCE B, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Bisphenol AP promotes pulmonary fibrosis by regulating macrophage function in a bleomycin-induced mouse model - Ze Chen; Zhenying Lin; Meng Ni; Baihe Li; Qianqian Zhang; Zelin Cao; Wei Li; Yanan Tang; Dongting Yao; Chunyu Cheng; Yi Hu; Xiaorui Liu; et al. (Toxicology, 2026)

A novel mechanism of uranium mineralization: The role of zircon adsorption at the Qigequan deposit, Qaidam Basin, NW China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Zhe Chi; Zhi-Lin Cheng; Wen-Yi Wu; Chen Zhang; Bing-De Qi; Xue-Bin Wei (Sedimentary Geology, 2026)

AeroTrans: Hourly AOD retrieval over land from MSG-1/SEVIRI imagery integrating Transformer and transfer learning - Yulong Fan; Zhanqing Li; Lin Sun; Oleg Dubovik; Zhihui Wang; Fan Cheng; Xiaohang Shi; Jing Wei (Remote Sensing of Environment, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Evaluating long-term geomorphic responses and sediment budget impacts of threshold-based floods and sediment replenishment in the Naka River, Japan - Cheng Wei; Sameh A. Kantoush; Binh Quang Nguyen; Sohei Kobayashi; Jia Qi Lin; Tetsuya Sumi (Geomorphology, 2026)

Lactiplantibacillus pentosus JWN01 and Lactiplantibacillus plantarum JWN02 attenuate renal fibrosis and pathological autophagy in hyperuricemic nephropathy via gut–kidney axis - Qizhou Mo; Min Qin; Haiqi Liang; Liwei Wei; Yujian Li; Yangmei Qin; Lichun Tang; Jing Liang; Chong Qian; Yilong Liang; Shufeng Luo; Yutuo Wei; et al. (Food Research International, 2026)

Optoelectronic synaptic transistor array based on CsPbBr3/grating-patterned IDTBT heterojunctions for neuromorphic visual fatigue sensing - Jiajie Hong; Zhiqian Wei; Zunxian Yang; Yue Chen; Luxi Yuan; Shangwei Ye; Xudong Jiang; Yuting Bai; Benfang Liu; Zhiyu Yuan; Wenxin Zhang; Jie Li; et al. (Chemical Engineering Journal, 2026)

Antioxidant capability of peanut shell extracts obtained using an ethanol–ammonium sulfate two-phase system - Yung-Sheng Lin; Cheng-Kun He; Yun-En Jian; Ming-Ren Chen; Tz-Feng Lin; Cheng-You Chen; Wei-Hsun Wang (Biomass and Bioenergy, 2026)

Ecological responses of the largest lake-wetland system (North China Plain) to hydrological regulation and cultural eutrophication over the past 70 years - Longjuan Cheng; John P. Smol; Qi Lin; Chaoran Wei; Shuyi Yang; Dejun Wan; Qingfeng Jiang; Dongliang Ning; Bin Xue (Anthropocene, 2026)

High-resolution seismic data processing based on low-dimensional manifold constraints - Gang-lin Lei; Guang-liang Zhao; Suo Cheng; Yang Tan; Jiang-wei Shang; Ze-lin Li; Zi-lun Xiong; Zhu-kun Wang (Applied Geophysics, 2026)

Autumnicola aciditolerans sp. nov., a novel member of the genus Autumnicola isolated from tidal flat in Zhoushan - Yang Li; Dong-Yan He; Jia-Wei Gao; Ke Cao; Yun-Fei Cao; Xing-Cheng Wang; Lin Xu; Yan Bai; Can Chen; Cong Sun (Antonie van Leeuwenhoek, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Systematic assessment and improvement for the intelligent municipal solid waste sorter - Wei-Lung Mao; Shu-Han Huang; Hsu-Cheng Chen; Jun-Wei Zeng; Yu-Hao Lin (Journal of Cleaner Production, 2026)

Application of statistical methods to evaluate identification credibility of macerals in high-maturity marine shales - Lin Wei; Maria Mastalerz; Jingwen Wang; Yanan Wang; Xiaomiao Li; Xiong Cheng (International Journal of Coal Geology, 2026)

The study on soot formation and spray ignition characteristics of conventional aviation fuels: Jet A-1 and JP-5 - Jhe-Kai Lin; You-Cheng Huang; Wei-Cheng Wang; Hiew Mun Poon; Meng-Choung Chiong (Fuel, 2026)

A novel strategy for controlling nitrite accumulation in fermented cabbage by regulating microbial community structure via cold plasma - Lin Zhu; Mengke Cheng; Yuan Wang; Xinyu Hu; Rong Wang; Biyue Yang; Xiang Xiao; Wei Wei (Food Control, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Tunable synthesis of tailored high-energy-density fuels from coal-based fluorene - Bing-Wei Chen; Hua-Jun Zhai; Yan-Cheng Hu; Yan-Hong Tan; Jia Li; Zhilian Wu; Lin Shao; Jing-Pei Cao (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Triatomic-doped MXene based catalyst with sodium alginate encapsulation their molecular and DFT calculation study for efficient photocatalytic removal of disinfected by-product from drinking water - Saleem Raza; Ata Ur Rehman; Zhiyu Zhao; Hua Li; Cheng Chen; Wei Yu; Ying Liu; Yanchao Xu; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2026)

Fine-tuned Ce electron density directs H2O2 activation pathway in industrially employable CeO2 nanozymes for ∼100% specificity and boosted activity in (Bromo)peroxidase mimicking - Tianqi Cheng; Bo Yuan; Chao Zhao; Zicong Tan; Xinyu Wu; Jian Lin Chen; Juan Liu; Yufei Zhao; Hui Wei; Yung-Kang Peng (Chemical Engineering Journal, 2026)

Linear diacyl chloride enables polyamide nanofiltration membranes with balanced permeability and selectivity for efficient dye desalination - Jiujing Xu; Cheng Chen; Zhiyu Zhao; Leihong Zhao; Wei Yu; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2026)

Melatonin suppresses glycolysis and coordinately disrupts DNA repair via targeting the YAP1-NAMPT signaling in breast cancer - Yi-Wen Lai; Cheng-Ying Chu; Zei-Wei Liu; Hsin-Ying Lu; Chi-Ching Lee; Mei-Hsiang Lin; Cheng-Wei Lin (Chemico-Biological Interactions, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Dexmedetomidine Mitigates Sevoflurane-Induced Neurodevelopmental Effects in Paediatric Anaesthesia: A Meta-Analysis and Preclinical Study - Hsuan-Chih Lao; Chia-Wei Huang; Ssu-Han Wang; Yen-Lin Su; Chien-Hui Chang; Cheng-Yen Liao; Jen-Chieh Wu; Ying-Chun Lin; Jin-Wu Tsai (Journal of Neuroimmune Pharmacology, 2026)
Sevoflurane (Sevo) anaesthesia in children is linked to an increased incidence of postoperative emergence agitation (EA) and potential neurotoxicity in developing brains. However, the specific risks of subanaesthetic foetal or neonatal exposure to Sevo remain unclear. This study evaluates the safety and efficacy of combining dexmedetomidine (Dex) with Sevo to manage EA in paediatric anaesthesia. A systematic review and meta-analysis of randomized controlled clinical trials involving children under 8 years old revealed that Dex significantly reduces EA incidence when administered via intravenous, perineural, and intranasal routes. Using in utero electroporation, we found that pregnant mice exposed to 2.5% Sevo at embryonic days 14.5 and 15.5 exhibited transient neuronal migration deficits, with 25% of neurons delayed in deeper cortical layers. However, these neurons migrated to the cortex by postnatal day 8. Neonatal mice exposed to 2.5% Sevo experienced a 10% reduction in dendritic spine density in adolescence, associated with impaired somatosensory function, as assessed by the Von Frey test. Remarkably, Dex pretreatment ameliorated these pathological and functional changes. Thus, foetal or neonatal Sevo exposure can delay neuronal migration and reduce dendritic spine density. Dex co-administration effectively mitigates these adverse outcomes, supporting its potential use in paediatric anaesthesia to protect developing brains. Graphical abstract

Lithofacies Identification and Classification Based on Least Squares Support Vector Machine Optimized by Sparrow Search Algorithm - Chenyang Mu; Zhongjie Guo; Guangxu Wang; Xiaoxiao Zhang; Cheng Qian; Changsong Lin; Yang Chen; Yougong Wang; Wei Wu (Mathematical Geosciences, 2026)

Organochlorine pesticides (OCPs) in the sediment of the Bohai Sea in China: Slow phasing out but risk remaining - Xuan Shi; Jing Wang; Ming Xin; Chunye Lin; Baodong Wang; Hongguang Cheng; Mengchang He; Xitao Liu; Wei Ouyang (Marine Pollution Bulletin, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Eight previously undescribed flavonoids and four previously undescribed bibenzyls from Macaranga kurzii and their potential antiviral activities - Yan-Zi Ma; Ding-Cheng Zhang; Liu Yang; Xue-Wen Wu; Bo Li; Muhammad Aurang Zeb; Yuan-Lin Kong; Xue-Mei Zhou; Wei-Lie Xiao; Chang-Bo Zheng; Xiao-Li Li (Phytochemistry, 2026)

Expanded species diversity of fungi in metalliferous mine tailings ponds and their potential ecological roles revealed by PacBio sequencing - Yanying Li; Ting Huang; Weihang Zeng; Rongzhou Jin; Ye Wu; Zhipeng Chen; Qijie Cheng; Xinlin Yu; Xiao-lin Luo; Guan-xiong Wu; Jia-wei Li; Pu Jia; et al. (Journal of Hazardous Materials, 2026)

Investigation of the vertical distribution of formaldehyde and its implications for hydroxyl radical contribution and ozone formation sensitivity in Ningbo, China - Qianqian Hong; Xiaojian Zhang; Chengzhi Xing; Baixue Yang; Jingyi Chen; Shaocong Wei; Hua Lin; Yizhi Zhu; Jian Mei; Mao Mao; Cheng Liu (Journal of Environmental Sciences, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

From genes to products: High-efficiency biosynthesis and holistic optimization strategies for monounsaturated fatty acids - Lu-Wei Xu; Yan-Cheng Lin; Yi-Ting Shen; Xin Qi; Zi-Xu Zhang; Wang Ma; Xiao-Man Sun (Food Microbiology, 2026)

Lack of adverse effects in a subchronic 90-day oral toxicity study of almond hull powder in Sprague-Dawley rats - Yuyang Yao; Juer Liu; Yanling Cheng; Qiming Miao; Xinyue Zhu; Jingyi Xie; Na Zhang; Wei Hua; Guangwei Huang; Xiangyang Lin; Shengquan Mi; Roger Ruan (Food and Chemical Toxicology, 2026)

Association between urinary metabolites of 1,3-butadiene and toluene exposure with kidney function indices in Taiwanese school-aged children living near a petrochemical complex - Po-Keng Cheng; Vinoth Kumar Ponnusamy; Wei-Hong Lin; Jeganathan Chinnadurai; Pei-Chien Tsai; Cai-Yu Chen; Wan-Ting Chang; Po-Chin Huang (Environmental Pollution, 2026)

Self-reporting and high-energy supercapacitors enabled by electrochromic ZnCo-S@CuFe-LDH heterostructures via interfacial engineering - Jiale Hou; Zhenghu Zhu; Haofeng Lu; Hecong Wang; Cheng Chen; Xinfeng Wu; Yonghou Xiao; Wanghui Wei; Minjie Xue; Lexing You; Xinzhou Ma; Donghai Lin (Chemical Engineering Journal, 2026)

Electrochemically activated polypyrrole for full-polymer electrochemical deionization: Unraveling potential-gated ion exchange behavior and its application to oxyanion removal - Hung-Yi Huang; Yi-Heng Tu; Yi-An Chen; Cheng-Wei Lin; Yu-Hung Cheng; Hsing-Mei Chou; Yu-Hsiang Yang; Yun Ku; Zhiyin Yang; Sophia Uemura; Hsin-Lung Chen; Richard B. Kaner; et al. (Chemical Engineering Journal, 2026)

Smart SERS platform with a machine-learning approach for the detection of thiram in fruit juices using an Ag NPs/NiFeLDH/MXene composite - Nazar Riswana Barveen; Petchi Raman Mariappan; Sathishkumar Chinnapaiyan; Yen-Yu Lin; Chih-Yu Kuo; Yu-Wei Cheng (Chemical Engineering Journal, 2026)

Alternating current or direct current: Which is better for electrochemical membrane separation water purification system? - Zhen Qiu; Jiujing Xu; Cheng Chen; Wei Yu; Bisheng Li; Liguo Shen; Bing Yu; Huajun Feng; Hongjun Lin (Chemical Engineering Journal, 2026)

The p -JNKThr183/Tyr185 / p -Keap1Thr43 /Keap1 axis mediates arsenic-induced endothelial dysfunction by coordinating Chaperone-mediated autophagy with macroautophagy - Jinyu Li; Jin Cheng; Zhihan Yang; Lin Gao; Qiaoling Liu; Jing He; Yishan Dong; Shuo Wang; Jing Cui; Ziqi Xu; Dianjun Sun; Wei Zhang (Chemico-Biological Interactions, 2026)

Pre-existing but not post-solid organ transplantation diabetes mellitus predicts end stage renal disease and mortality - Wei-Syun Hu; Cheng-Li Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Brain Tissue-Derived Exosomal Proteomics Identifies Chemotaxis-Associated Protein Changes After Traumatic Brain Injury: An Exploratory Hippocampal Transcriptomic Comparison - Wei-can Chen; Xin-li Chen; Cheng-ye Lin; Yang-zi Huang; He-fan He; Yi-lin Zhou; Yi-bin Liu (Molecular Neurobiology, 2026)

3-n-Butylphthalide Protects SH-SY5Y Cells from Ferroptosis by Inhibiting ACSL4-Mediated Lipid Peroxidation - Huanhuan Wei; Yiyin Zhang; Qianqian Ju; Bolin Lian; Tong Gao; Haiqin Duan; Xiang Yin; Yongqi Lin; Jianhong Shen; Qiuhong Ji; Cheng Sun; Lihua Shen (Molecular Neurobiology, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Rapid nitrogen removal in sandy beaches driven by periodic tidal inundations - Lin Wei; Pinghe Cai; Qingquan Hong; Tong Wu; Wei Liu; Yilin Cheng; Pingping Mi (Limnology and Oceanography, 2026)
Sandy beaches are an important passage for the transport of various forms of nitrogen from land to sea. However, export fluxes of these forms of nitrogen and the mechanisms controlling their transformation remain elusive. Using the 224 Ra/ 228 Th disequilibrium approach, we estimated export fluxes of dissolved inorganic carbon and dissolved inorganic nitrogen at three intertidal sandy beaches with distinct slopes along the southeast China's coast. We identified that sandy beaches are a hotspot of nitrogen loss in the coastal ecosystem, with nitrogen removal rates reaching up to 87.1 mmolN m −2 d −1 and removal efficiencies varying between 7% and 82%. Notably, nitrogen removal rates peaked at intermediate seawater percolation fluxes, reflecting the optimal balance of oxygen consumption, marine organic matter remineralization, and nitrate production for fueling denitrification in the beach's interior. In addition, total nitrogen removal increased with beach slopes. This is likely due to the fact that steeper beaches facilitate seawater to percolate more efficiently into the beach's interior and travel along a longer flow path before it drains out, thus allowing denitrification to prevail. Overall, our field observations reveal that instead of the surface “skin circulation,” the “body circulation” system within an intertidal beach governs fluid transport and solute exchange between land and sea. We conclude that intertidal sandy beaches function as an efficient biogeochemical reactor, which attenuates anthropogenic nitrogen inputs to the coastal ocean.

Multistep-Ahead Forecasting of Chlorophyll Concentration Based on Dynamic Collaborative Attention Network - Lei Wang; Guodong Han; Ping Wu; Jie Mei; Zhenyu Lin; Shengming Cheng; Xianhua Wei; Xu Yang; Chuxu Xiong; Shaoyang Dai; Ying Zhao (Journal of Marine Science and Engineering, 2025)
Multistep-ahead forecasting of chlorophyll concentration is of great significance in red tide early warning systems. Existing methods often neglect the potential adverse interactions between non-predictive variables and chlorophyll while failing to fully utilize the effective information in historical decoder units. To address these issues, this paper proposes a Dynamic Collaborative Attention Network (DCAN) model for chlorophyll concentration forecasting, which consists of two components: a Two-Stage Variable Embedding Network (TSVEN) and a Dynamic Attention Network (DyAN). The TSVEN can identify the non-predictive variables that have the most significant impact on chlorophyll changes and generate corresponding spatial vectors from them, thereby alleviating the information conflict between chlorophyll and non-predictive variables. The DyAN integrates a context attention module and a filtering gate mechanism. The former effectively extends the forecasting time range by dynamically retrieving historical decoder states, while the latter selectively integrates historical decoder information, thereby improving the reliability of model decisions and prediction accuracy. Experimental results based on real datasets show that the proposed model outperforms the current state-of-the-art methods in chlorophyll concentration forecasting tasks and exhibits good interpretability.

Pilot study on integrating multidisciplinary technologies to implement an autonomous and smart harvester for asparagus - Joe-Air Jiang; Jen-Cheng Wang; Hung-Jen Lin; Cheng-Ying Chou; Chia-Chun Chien; Wei-Hao Huang; An-Chi Liu; Cheng-Chun Lee; Ming-Chi Guo; Jui-Chu Peng (Computers and Electronics in Agriculture, 2025)

Divergent impacts of partial manure substitution on soil nitrous oxide emissions dependent on phosphorus availability - Yuheng Cheng; Jinbo Zhang; Hang-Wei Hu; Xiangyin Ni; Jianbo Fan; Song Wan; Mengmeng Feng; Christoph Müller; Ji-Zheng He; Yongxin Lin (Soil Biology and Biochemistry, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Corrigendum to “Rho GAPase protein 1 (RACGAP1) affects the proliferation and metastasis of esophageal squamous cell carcinoma cells by regulating signaling pathways: Thermal infrared medical image inspection” [J Therm Biol. 2025 131 104178 doi: 10.1016/j.jtherbio.2025.104178. PMID: 40561732] - Yu-Hao Zhu; Jia-Cheng Lin; Xiao-Bing Lin; Wei-Yuan Lai; Jin-Dong Yu; Lin Long (Journal of Thermal Biology, 2025)

Quantification of the variability of the soil moisture field in response to variations in the rainfall field - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee; Wei-Cheng Lo (Journal of Hydrology, 2025)

Sustainable energy generation through engineered copper molybdate: a ternary metal oxide catalyst for efficient oxygen evolution in alkaline environments - Hung-Chang Cheng; Dhanapal Vasu; Hsin-Yu Lin; Zhen-Yuan Lan; Leggins Abraham; Tetsu Yonezawa; Te-Wei Chiu (Fuel, 2025)

Advances in the research on phenolic acids and flavonoids in vinegar: Sources, formation and degradation mechanisms, and functional properties - Cheng-Hao Jin; Yong-Zhu Zhang; Feng-Hua Wu; Chang-Ling Wu; Peng Wang; Wei Feng; Lin-Mei Liang; Wei-Jiang Xu; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2025)

Astaxanthin enhances broiler health via integrated regulation of antioxidant capacity, immune function, and gut microbiota - Xiao-Ming Gu; Ding-Cheng Ye; Jun-Wei Cheng; Zhi-Xin Lin; Hai-Xuan Lv; Zai-Xing Cai; Yun Yang; Chang-Kang Wang; Yu-Yun Gao; Ling Jin (Food Chemistry, 2025)

Revealing the inhibition mechanism of ultrasound-assisted purified dried apricot polyphenols on α-amylase: Insights from multispectral and computational analyses - Cheng Ma; Zhongyang Li; Jiangli Lin; Bin Wu; Shuailian Zhao; Xiaojing Yao; Xiuling Zhu; Xiangyun Wei; Shishan Zhou (Food Bioscience, 2025)

Mechanical performance of an assembled 3D auxetic hybrid structure under eccentric and axial compression - Jia Shuo Liu; Yi Zhang; Xiang Jie Wei; Wei Zhong Jiang; Meng Li Xue; Yi Chao Qu; Tao Ding; Jia Hui Zhang; Lin Hua; Tong Cheng; Xin Ren (Engineering Structures, 2025)

Thiol-ene click synthesis of a novel alginate-derived adsorbent: Synergistic adsorption and mechanistic investigation of dye and antibiotic - Xinyi Lu; Wei Yu; Chenglin Ji; Longyufan Liu; Jiaheng Teng; Cheng Chen; Hongjun Lin; Guanhua Jin; Leihong Zhao; Saleem Raza; Liguo Shen (Desalination, 2025)

Microbial, genetic, and urban drivers of ant invasions - Wei-Jiun Lin; Po-Wei Hsu; Edward L Vargo; Chin-Cheng Scotty Yang (Current Opinion in Insect Science, 2025)

Deep learning-assisted bionic gustatory sensing system based on aggregate-tuned silver nanoclusters and functionalized MXene for multiple foodborne pathogens recognition - Yuandong Lin; Wei Xiang; Fengqi Wang; Yong-Guang Jia; Jingzhu Wu; Jun-Hu Cheng (Chemical Engineering Journal, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Evaluation of Feeding Effect of a New Artificial Diet on Chilo sacchariphagus and Chilo infuscatellus (Lepidoptera: Crambidae), Two Major Stalk Borers on Sugarcane in China - Ji-li Wei; Yong-lin Ma; Cheng-hua Huang; Feng-ying Wang; Qiao-xian Wei; Liu-feng Li; Ren-zhao Liao; Fu Lv; Xue-hong Pan; Xian-kun Shang (Sugar Tech, 2025)

Hemorrhoid risk among people with diabetes mellitus using glucose lowering agents - Wei-Syun Hu; Cheng-Li Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The whole genome sequence of Cordyceps cicadae — an edible and potential medicinal fungus - Yuwei Liu; Xueqian Li; Yiqi Meng; Yifan Wu; Yuting Jin; Xiaotong Ma; Wei Zhou; Yuchong Tan; Fu-Cheng Lin; Hongkai Wang (Molecular Genetics and Genomics, 2025)

Analytical and usability comparison of microsampling dried blood spot devices for glucocorticoid detection in sports using ultra-high-performance liquid chromatography–tandem mass spectrometry - Cheng-Chia Chen; Yu-En Lin; Mei-Chich Hsu; Yu-Chuan Lin; William Chih-Wei Chang (Analytica Chimica Acta, 2025)

Characterization of temporal nonstationary random soil moisture perturbation fields - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee; Wei-Cheng Lo (Advances in Water Resources, 2025)

Fast Forward Modeling of Resistivity Method under Complex Topography Using Finite Element Method - Zhan Wang; Chang-Wei Li; Yu-Zeng Lv; Run-Lin Luo; Bo Cheng; Bo Li (Applied Geophysics, 2025)

Serum cortisol and AdipoR2 rs12342 were involved in the correlation between stress and serum cholesterol in a gender-specific manner - Yi Lin Shen; Qi Wei Guo; Xue Cheng Li; Ke Xin Jia; Jun Yi Liu; Yan Zhi Yi; Jun Tao Ren; Jia Jing Cai; Guo Ming Su; Jia Lin; Ding Zhi Fang (Metabolic Brain Disease, 2025)

Reframing construction labor for sustainable urban land transformation - Lin Liu; Hsing-Wei Tai; Tsung-Chun Chen; Kuo-Tai Cheng (Environment, Development and Sustainability, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Molecular insights in outstanding performance of Ca2+ bridging MXene/Sodium alginate composite membranes - Hua Li; Hongjun Lin; Saleem Raza; Zhiyu Zhao; Siyuan Chen; Yue Wang; Qianqian Zeng; Cheng Chen; Wei Yu; Liguo Shen (Water Research, 2025)

The influence of trees shade level on human thermal comfort and the development of applied assessment tools - Yu-Ying Wei; Ching-Yin Cheng; Tzu-Ping Lin (Landscape and Urban Planning, 2025)

Efficient and selective separation of uranium(VI) from natural waters by MgAl-LDH/CNT composites: Performance evaluation and adsorption mechanism - Jianchun Qin; Wenlin Zhao; Wensheng Zhao; Gao Cheng; Xiuxian Huang; Yuan Liu; Jiebing He; Xing Wei; Shunyan Ning; Lin Yu (Journal of Water Process Engineering, 2025)

Integrated assessment of wind energy's emission and meteorological effects on PM2.5 in Taiwan - I-Chun Tsai; Pei-Rong Hsieh; Cheng-Wei Lin; Chung-Cheh Chou; Chia-Ying Tu; Chao-Tzuen Cheng; Huang-Hsiung Hsu (Journal of Environmental Management, 2025)

Closing in on carbonate uranium isotopes as a paleo-redox proxy based on continuous records from Late Oligocene to Holocene island carbonates - Guolin Xiong; Feifei Zhang; Yi-Bo Lin; Guang-Yi Wei; Na Li; Mengchun Cao; Xuexue Jia; Jian Wang; Wen Yan; Hai Cheng; Shu-zhong Shen (Geochimica et Cosmochimica Acta, 2025)

Protective effects of microalgal macular pigment on diabetic retinopathy upon blue light irradiation induced oxidative stress, inflammation, and MAPK pathways - Meng-Wei Lin; Cheng-Han Lin; Wei-Hong Chiu; Hui-Fang Chang; Wai-Man Cheang; Chien-Chun Chang; Vivian C.H. Wu; Chih-Sheng Lin; Chiu-Mei Kuo (Food Research International, 2025)

Tyramine injection enhances immune function and disease resistance in Penaeus monodon - Wan-Lin Tsai; Li-Yang Hsu; Cheng-Ying Li; Hsin-Wei Kuo; Winton Cheng (Fish & Shellfish Immunology, 2025)

Associations between prenatal exposure to air pollution and infant growth trajectories in the first two years: Exploring potential sexual dimorphism and sensitive windows - Zhen-Hua Li; Si-Wei Dai; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2025)

Double cross-linking architectonics membranes for high-efficiency oil-water separation and the mechanistic investigation - Yue Wang; Hongjun Lin; Siyuan Chen; Hua Li; Zhiyu Zhao; Qianqian Zeng; Cheng Chen; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2025)

A novel vortexing-driven droplet digital CRISPR (VTD-CRISPR) platform for rapid and absolute quantitative detection of genetically modified crops - Jingzheng Chi; Yuzhen Wei; Jiannan Chen; Lin Ding; Xiaoyun Chen; Xiaofu Wang; Junfeng Xu; Cheng Peng (Chemical Engineering Journal, 2025)

Impact of sacubitril/valsartan on adverse clinical events in heart failure with end-stage renal disease patients—a real life nationwide investigation - Wei-Syun Hu; Cheng-Li Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Three-dimensional material point analysis of the Guanghua landslide influenced by topographic constraints - Yi-Pin Peng; Kuo-Hsin Yang; Wei-Lin Lee; Tatag Yufitra Rus; Shih-Hao Cheng; Jyun-Yen Wang; Chihping Kuo (Landslides, 2025)

An in vivo NanoBiT-based pseudoviral biosensor for real-time monitoring of SARS-CoV-2 spike/hACE2 interactions and therapeutic screening - Cheng-Han Lin; Meng-Wei Lin; Xin-Rui Yang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chin-Hung Tsai; Chih-Sheng Lin (Analytica Chimica Acta, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

Sediment characteristics affecting natural radionuclide distribution and radiological assessment in a tropical wetland near Maanshan Nuclear Power Plant, Southern Taiwan - Ting-Chien Chen; Yi-Lung Yeh; Fan-Cheng Zeng; Chih-Chung Lin; Zhi-Mou Chen; Wei-Hsiang Huang (Environmental Monitoring and Assessment, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

Manipulation of carbon dioxide adsorption and desorption via CO₂-philic fibrous polyethyleneimines under alternating current electric fields by frequency tuning - Chih-Wei Chen; Yi-Hua Lin; Chih-Chia Cheng; Chien-Hsing Lu; Jem-Kun Chen (Science of The Total Environment, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Exploring the anticancer potential of Polygonum barbatum (L.) against colorectal cancer: In vitro and in vivo investigations - Pi-Kai Chang; I-Chuan Yen; Wei-Cheng Tsai; Kuen-Tze Lin; Shih-Yu Lee (Phytochemistry Letters, 2025)

3D-printed super-wetting membranes with in situ grown MOF for efficient oil-water separation - Siyuan Chen; Zhiyu Zhao; Cheng Chen; Wei Yu; Xinchun Lu; Yue Wang; Hua Li; Qianqian Zeng; Hongjun Lin; Leihong Zhao; Guanhua Jin; Liguo Shen (Journal of Hazardous Materials, 2025)

Facile fabrication of MnCO3 and covalent organic framework on the surface of MXene with sodium alginate hydrogel for effective photocatalytic eradication of disinfected byproducts - Saleem Raza; Cheng Chen; Wei Yu; Muslim Raza; Malik Taj Ahmad; Nisha Singh; Liguo Shen; Hongjun Lin (Journal of Environmental Chemical Engineering, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

Harnessing basic helix-loop-helix-mediated transcriptional reprogramming in mixotrophic Chlorella for synergistic carbon waste remediation and biofuel production - Yu-Feng Yang; Jin-Hua Mou; Yu-Cheng Yang; Lan-Lan Hu; Wen-Li Huang; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2025)

Novel CoMo-LDH integration enhanced permeability and self-cleaning of MXene-based membrane for efficient water treatment - Qianqian Zeng; Zhiyu Zhao; Yue Wang; Siyuan Chen; Hua Li; Cheng Chen; Wei Yu; Jiaheng Teng; Hongjun Lin; Yu Yang; Liguo Shen (Chemical Engineering Journal, 2025)

Photoresponsive azobenzene-grafted thermoplastic elastomers with controlled hard segment ratios for fast-rewritable and tunable surface relief gratings - Ming-Chieh Lin; Wen-Kai Cheng; Mohamed Gamal Mohamed; Wei-Hung Su; Shiao-Wei Kuo (Chemical Engineering Journal, 2025)

Stable molecular-bridged graphene oxide membrane with bioinspired hydrophilic water inlets for ultrafast molecular separation - Boya Wang; Cheng Chen; Wei Yu; Jiujing Xu; Bisheng Li; Leihong Zhao; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2025)

Carbon nanotube/two-dimensional metal–organic framework composites with enhanced thermoelectric performances for thermoelectric generators - Cheng-Yuan Lin; Jhe-Wei Chang; Meng-Hao Lin; Kuan-Chu Wu; Shao-Huan Hong; Jhih-Min Lin; Chung-Wei Kung; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Tribopotential mediated ferroelectric polarization for versatile reconfigurable p–n junction - Keteng Zhang; Jinran Yu; Yichen Wei; Liuqi Cheng; Zhenyu Feng; Jie Gong; Zhong Lin Wang; Qijun Sun (Chemical Engineering Journal, 2025)

Self-feedback cascading DNA circuit encapsulated within a gene-modified bifunctional virus-inspired nanovector for light-gated spatiotemporal biosensing in live organisms - Xiao-Xue Chen; Yong-Yao Song; Zhuo Chen; Tian-Tian Zhang; Wei-Lin Chen; Xiao-Mei Wang; Jun-Rui Hu; Cheng-Yu Li (Analytica Chimica Acta, 2025)

Spatial–Temporal Dynamics of Drought Characteristics and Its Influencing Factors on Tibetan Plateau - Zhizhu Zhou; Wenjun Yu; Lin Zhao; Yanzhong Li; Shuo Cheng; Jiazhe Duan; Yincong Xing; Wei Shao (International Journal of Climatology, 2025)
Assessing drought on the Tibetan Plateau (TP) is essential for understanding the spatial characteristics of the region's hydrological regimes, as well as the trends of the evolving climate‐ecological system. Based on the precipitation and the potential evapotranspiration data from the ERA5‐Land dataset, this study evaluated the drought characteristics on the TP from 1950 to 2022 using the Standardised Precipitation Evapotranspiration Index (SPEI) and the Run theory. The analysis of SPEI at multiple time scales—SPEI‐1 (monthly), SPEI‐3 (seasonal), and SPEI‐12 (annual)—consistently revealed a pronounced drying trend across the TP over the past 70 years. Notably, the wet‐to‐dry transition points were detected in 2000 and 2001 based on the SPEI‐1 and SPEI‐3 series, respectively, while the SPEI‐12 series indicated a later shift occurring in 2004. In addition, the SPEI values indicated a spatial trend of increasingly severe drought conditions from south to north. Particularly, pronounced drought stress was observed in the Brahmaputra, Ganges, and Indus basins, as well as in the southern regions of the Inner Plateau. Furthermore, the relationships between drought variability and key climatic drivers—including sunspots, El Niño‐Southern Oscillation (ENSO), temperature (TEMP), and annual mean areal precipitation (AP)—were identified through cross‐wavelet transform (XWT) and wavelet coherence analysis (WTC). In general, the analysis showed that the SPEI values on the TP were negatively correlated to ENSO and TEMP but positively correlated to sunspots and AP. This study offers a comprehensive spatiotemporal assessment of drought dynamics across the TP, providing critical insights for regional water resource management and climate change adaptation planning.

Lateral Cerebellar Theta Burst Stimulation Can Modulate Default Mode Network Connectivity in Autistic Adults - Hsing-Chang Ni; Heng Chien; Chun-Hung Yeh; Michael Cheng; Wei-Cheng Lin; Hsiang-Yuan Lin (The Cerebellum, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Using speleothem 87Sr/86Sr variations tracking the controls on trace element (Sr-Mg) compositions - Rishui Chen; Shuyu Xue; Hongbin Zhang; Michael Griffiths; Yi Zhou; Xing Liu; Zhenli Zhu; Lin Chen; Wei Guo; Shitou Wu; Hai Cheng; Junhua Huang; et al. (Global and Planetary Change, 2025)

Block copolymer architectures with poly(ε-caprolactone) for modulating interactions to enhance selectivity and stability of semiconducting single-walled carbon nanotube dispersions - Mei-Nung Chen; Rin Iwasaki; Mayoh Ashiya; Haoyu Zhao; Qi-An Hong; Yen-Ting Li; Kai-Lin Chen; Maina Moses Mburu; Wei-Ting Li; Xiaodan Gu; Wei-Hung Chiang; Takuya Isono; et al. (Chemical Engineering Journal, 2025)

Association of stroke and mortality among patients receiving heart transplantation—a nationwide study - Wei-Syun Hu; Cheng-Li Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Characteristics and controlling factors of displacement pressure in mudstone caprock: insights from the Yinggehai Basin, South China Sea - Wei Duan; Cheng-Fei Luo; Lin Shi; Qian Li; Deyong Li (Marine Geophysical Research, 2025)

Aurantibrevibacter litoralis gen. nov. sp. nov. a Novel Member in the Family Flavobacteriaceae Isolated from Sediment of Tidal Flat Located in Ningbo, China - Yun-Fei Cao; Dong-Yan He; Yu-Ruo Wang; Ke Cao; Yang Li; Jia-Wei Gao; Xing-Cheng Wang; Lin Xu; Cong Sun; Xiao-Yun Yu (Current Microbiology, 2025)

Five novel RNA viruses of the invasive big-headed ant (Pheidole megacephala) - Charly T. Hartle; Chih-Chi Lee; Hung-Wei Hsu; Chun-Yi Lin; Kuan-Ling Liu; Joey Yin-Xin Chang; John A. Lawrence; Jia-Wei Tay; Chin-Cheng Scotty Yang (Archives of Virology, 2025)
The African big-headed ant, Pheidole megacephala , is one of the most destructive invasive ant species, posing a significant threat to native biodiversity and ecosystem function, particularly in island ecosystems. Despite recent efforts to characterize pathogens in other major invasive ants, P . megacephala has received comparatively little attention. In this study, we characterized five novel RNA viruses actively replicating in P . megacephala , which we have named Pheidole megacephala virus 1–5 (PmV1-5), and examined viral diversity and prevalence in two invasive populations in Taiwan and Hawaii. This ant possesses a unique trait of true morphological worker dimorphism (major and minor), allowing us to test whether virus prevalence differs between the major and minor worker castes. Our findings indicate that all five novel viruses were present in both populations, but viral prevalence was higher in Hawaii than in Taiwan, potentially due to differences in supercolony structure. Multiple-virus infections were common, with coinfection by PmV1 and PmV5 being the most frequent. Notably, we found no significant difference in infection patterns between major and minor workers, suggesting that virus distribution is stable within colonies and that sampling different castes does not introduce bias in pathogen detection. This study represents the first characterization of viral pathogens in P . megacephala and may contribute to the development of microbial control strategies against this globally invasive ant.

Replacement of fish oil with Schizochytrium-derived monoglycerides enriched in docosahexaenoic acid on the growth performance, lipid composition, and intestinal microbiota of Pacific white shrimp (Litopenaeus vannamei) - Wei Huang; Yongkang Song; Xiaonan Wang; Daiyan Lin; Tuyan Luo; Kaimin Cheng; Qiaolian Li; Baoyu Tian; Yongbiao Zheng; Yongjin He (Frontiers in Marine Science, 2025)
Docosahexaenoic acid (DHA) positively influences growth development, feed efficiency, physiological functions, and DHA accumulation in aquatic organisms. Recent mammalian studies demonstrate that DHA in the form of monoglycerides (MGs) is more conducive to facilitating the uptake and impact of DHA bioavailability than triglyceride (TG)-derived DHA. In this study, Schizochytrium -derived monoglyceride as a novel structured lipid form enriched in DHA-MGs was used to replace the fish oil of Litopenaeus vannamei diet and the effects of different DHA-MG levels on the growth performance, lipid composition of muscle and hepatopancreas, and intestinal microbiota of L. vannamei were investigated. The results showed that the diet with a high level of DHA-MGs distinctly increased the final weight, weight gain rate, and specific growth rate of L. vannamei . No notable variation in the biochemical makeup of shrimp muscle was detected among the four diets. The increase in DHA-MGs effectively facilitated the accumulation of DHA in the muscle and hepatopancreas of L. vannamei . In terms of lipidomics analysis, the addition of DHA-MGs significantly influenced the lipid species composition and DHA distribution in shrimp muscle and hepatopancreas. Additionally, the obtained results revealed that the addition of DHA-MGs improved the contents of diglycerides and triglycerides from the neutral lipid category with DHA and DHA located at specific positions on the glycerol backbone for shrimp muscle. Meanwhile, the lipid species from the glycerophospholipid category in shrimp tissues treated with four diets performed different variations. Besides that, the incorporation of DHA-MGs influenced the levels of microbial phylum and genus and the abundance of potential bacterial phenotypes for shrimp midgut. It was noted that the addition of DHA-MGs significantly decreased the abundance of potentially pathogenic bacteria, manifesting that DHA-MGs could readjust the intestinal microecological balance for intestinal health. In conclusion, the use of Schizochytrium -derived DHA-MGs to replace the fish oil in shrimp diet boosted the accumulation of DHA into tissues, modified the levels of lipid species with DHA and DHA located at specific positions on the glycerol backbone, and improved the intestinal health for the growth performance of L. vannamei .

Bio-derived carboxymethyl cellulose-graft-gallic acid antiscalant with remarkable antibacterial activity for reverse osmosis scaling and biofouling control - Liping Xiong; Wei Yu; Chenglin Ji; Longyufan Liu; Jiaheng Teng; Cheng Chen; Hongjun Lin; Liguo Shen (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Chemical and cell toxicity properties of particulate matter emitted from a diesel engine fueled with biodiesel and ethanol blends - Pak Kin Wong; Shou Hao Chen; Meisam Ahmadi Ghadikolaei; Kar Wei Ng; Simon Ming Yuen Lee; Jin Cheng Xu; Zhen Dong Lian; Lin Li; Shuli Li; Zhi Ning; Nirmal Kumar Gali; Adebayo Afolabi Fadairo (Environmental Pollution, 2025)

Biomass energy for a sustainable Taiwan: Technologies, policies, and future prospects - Yu-Wei Lin; Yu-Ting Liu; Li-Cheng Huang; Shing-Chou Lin; Shean-Jen Chen; YongMan Choi (Biomass and Bioenergy, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

Lactiplantibacillus plantarum GMNL-661 Ameliorates Clostridioides difficile Infection and Reconfigures Intestinal Microbiota in a Murine Model - Meng-Jia Li; Hong-Ming Chen; Yueh-Lin Chen; Yi-Hsin Lai; Cheng-Yu Lai; Jhen-Wei Ruan; Jenn-Wei Chen; Wan-Hua Tsai; Wen-Chien Ko; Pei-Jane Tsai (Probiotics and Antimicrobial Proteins, 2025)

Comparison of nebivolol, carvedilol, and bisoprolol for adverse clinical outcomes among patients with heart failure—a real-world nationwide investigation - Wei-Syun Hu; Cheng-Li Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

Seismic response of the composite bucket foundation supported offshore wind turbines under marine environmental loadings - Wei Cheng; Yikang Wang; Ming Li; Guangwei Xu; Haoran Lin; Panpan Shen (Marine Georesources & Geotechnology, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

Unraveling the potential of chemical recycling for poly(methyl methacrylate) through pyrolysis: Rigorous modeling, economic, and environmental evaluation - Hsu-Cheng Hua; Meng-Wei Lin; Zi-Cheng Su; I-Lung Chien; Bor-Yih Yu (Process Safety and Environmental Protection, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Dynamic effects of monopiles and sacrificial piles on Lagrangian residual velocity in an idealized rectangular bay - Xudong Liu; Cheng Fan; Lin Chen; Jinzhen Yu; Shuwen Zhang; Zhangliang Wei; Fangjing Deng (Ocean Engineering, 2025)

Microplastic-induced hypertension in rats: A two-hit model exploring oxidative stress and gut microbiota - Yu-Chun Cheng; Wei-Ling Chen; Hong-Ren Yu; Ching-Yi Tsai; Jiunn-Ming Sheen; Mao-Meng Tiao; Chien-Ning Hsu; You-Lin Tain (NanoImpact, 2025)

Rho GAPase protein 1 (RACGAP1) affects the proliferation and metastasis of esophageal squamous cell carcinoma cells by regulating signaling pathways: Thermal infrared medical image inspection - Yu-Hao Zhu; Jia-Cheng Lin; Xiao-Bing Lin; Wei-Yuan Lai; Jin-Dong Yu; Lin Long (Journal of Thermal Biology, 2025)

Fire ants exhibit self-medication but lack preventive behavioral immunity against a viral pathogen - Fang-Ling Chloe Liu; Wei-Jiun Lin; Liam McMillan; Chin-Cheng Scotty Yang (Journal of Invertebrate Pathology, 2025)

Effortless rule: Effects of oversized microplastic management on lettuce growth and the dynamics of antibiotic resistance genes from fertilization to harvest - Jing-Yuan Chen; Lin-Jie Qin; Tiao Long; Rui-Ting Wu; Shi-Hua Niu; Shuo Liu; Wei-Kang Deng; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Mitigation of the toxic effects of nitrite: Role and mechanism of isoleucine in mitigating mitochondrial DNA leakage-induced inflammation in grass carp (Ctenopharyngodon idella) under nitrite exposure - Kai-Xuan Ren; Lin Feng; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Cheng-Bo Zhong; Xiao-Qiu Zhou; Wei-Dan Jiang (Journal of Hazardous Materials, 2025)

Mechanism study of enhanced gas recovery and CO2 storage in naturally fractured carbonate reservoirs using a dual-permeability model coupled with association equation of state - Wei Xiong; Yu-Long Zhao; Lie-Hui Zhang; Shao-Mu Wen; Li-Li Liu; Zheng-Lin Cao; Cheng Cao; Xiang-Yu Liu; Xian-Yu Jiang (Gas Science and Engineering, 2025)

Systematic analysis of associations between obesity and memory decline - Ying Yue Huang; Wei Sen Zhang; Jiao Wang; Chao Qiang Jiang; Feng Zhu; Ya Li Jin; Kar Keung Cheng; Tai Hing Lam; Lin Xu (GeroScience, 2025)
Despite the development of numerous obesity indicators, the optimal measure associated with memory remains to be elucidated. We examined and compared these associations whilst also exploring potential interactions with education. We analysed the associations between 20 obesity indicators and memory (measured by Delayed Word Recall Test (DWRT)) in middle-aged and older participants from Guangzhou Biobank Cohort Study by linear regression and stratification analyses. We used two-sample Mendelian randomisation (2SMR) to analyse the associations of obesity with cognitive performance. Of 20 obesity indicators, 6 and 7 were associated with poorer memory function measured by baseline and follow-up DWRT; 7 and 10 with faster memory decline measured by mean annual change (MAC) and MAC rate of DWRT. Central obesity measured by waist-to-hip-to-height ratio (WHHR) z -score showed the greatest effect size, with the β s (95% CIs) being − 0.09 (− 0.11 to − 0.07), − 0.07 (− 0.09 to − 0.04), − 0.02 (− 0.03 to − 0.01) and − 0.49 (− 0.69 to − 0.29), respectively. The associations were weaker in those with higher education ( P for education-interaction from 0.008 to 0.049). In 2SMR, body mass index (BMI), waist circumference and BMI-adjusted waist-to-hip ratio were negatively associated with cognitive performance using inverse-variance weighted method, with β s (95% CIs) being − 0.11 (− 0.15 to − 0.07), − 0.07 (− 0.12 to − 0.02) and − 0.06 (− 0.09 to − 0.02), respectively. In conclusion, obesity, especially central obesity measured by WHHR, was associated with poorer memory function and faster memory decline in middle-aged and older people, with a weaker association observed amongst those with higher education. Graphical Abstract

Corrigendum to “Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella)” [Aquaculture Volume 598, 15 March 2025, 742053] - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Insights into Leuconostoc-clade as starters in Chinese paocai: Shaping microbial communities for rapid, safe, and flavor-preserving fermentation - Xinyu Hu; Mengke Cheng; Meng Zhang; Biyue Yang; Rong Wang; Juan Bai; Jiayan Zhang; Wei Wei; Lin Zhu; Xiang Xiao (Food Bioscience, 2025)

Chalcomoracin induces autophagy-mediated apoptosis in pancreatic cancer by suppressing the mTOR pathway - Xueli Hu; Zhipan Wu; Lin Cheng; Yuhang Shen; Luping Wang; Eman Shawky; Kaisa Sulaiman; Wei Zhu; Hua Gu; Jingkui Tian (Food Bioscience, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

High sensitivity mercury ion detection via thermal shock and quench with molecular sieve-functionalized FETs - Guan-Cheng Zeng; Hsuan-Wei Huang; Chia-Kai Lin; Jung-Chih Chen; Sheng-Chun Hung; Guo-Chun Dong; Yu-Lin Wang (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Microbiological Activity and Oxygen Availability Influence Arsenic Mobilization and Redox Transformation in an Arsenic-Rich Aquifer - Yu-Chen Su; Yu-Ju Chu; Chia-Cheng Wei; Chan-Wei Yu; Pei-Ling Yen; Yu-Hsuan Kuo; Ting-An Lin; Vivian Hsiu-Chuan Liao (Exposure and Health, 2025)

Pathotyping and molecular serotyping of clinical isolates of Glaesserella parasuis in Taiwan - Wei-Hao Lin; Chia-Hung Yen; Cheng-Yao Yang; Chuen-Fu Lin; Yung-Fu Chang; Chao-Nan Lin; Ming-Tang Chiou (Brazilian Journal of Microbiology, 2025)

RNA-binding protein expression based machine learning model predicts metastasis and treatment outcome of testicular cancer - Lin-jian Mo; Hai-qi Liang; Zhen-yuan Yu; Yao-wen Liang; Chuan-xin Gu; Qiu-ju Wei; Qi-huan He; Fa-ye Wei; Ji-wen Cheng; Zeng-nan Mo (Genes & Genomics, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

Identification of dietary protein utilization traits related SNPs and genes in brown-marbled grouper (Epinephelus fuscoguttatus) - Jin Zhang; Qinxi Dai; Yaorong Wang; Qianhao Wei; Cheng Peng; Yuqing Yang; Jinxiong Huang; Yanhua Huang; Jinhui Wu; Haoran Lin; Danqi Lu; Yong Zhang; et al. (Aquaculture, 2025)

Sedimentary geochemical records of the palaeovegetation and palaeoclimate evolution in the Pinghu Formation, Western Slope Belt, Xihu Sag, East China Sea Basin - Yanan Wang; Lin Wei; Xiong Cheng; Hui Diao; Wenjun Li; Dujie Hou; Jiansheng Li (Organic Geochemistry, 2025)

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Seismic performance of grouted CFDST column base: Investigation and design method - Zhi-Cheng Yang; Wei Li; Yu-Feng Cheng; Lin-Hai Han (Engineering Structures, 2025)

Enhancing color conversion of perovskite quantum dot-based micro-light-emitting diodes via electrochemical etching and flow chemistry system - Wen-Tse Huang; Yen-Huei Lin; Po-Yi Tu; Loan Thi Ngo; Wei-Cheng Chen; Kai-Ling Liang; Yen-Hsiang Fang; Chaochin Su; Ru-Shi Liu (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Development of a rat airway organoids model for studying chronic obstructive pulmonary disease - Chuanlai Yang; Hongwei Yang; Yangling Xian; Nanyi Liu; Haoyin Tan; Zirui Ren; Yanzhen Lin; Huan Zhao; Changjian Fang; Kang Yu; Dequan Pan; Yali Zhang; et al. (Tissue and Cell, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Micro-charging and accumulation of shale oil in lamellar shale interbedded with siltstones, Dongying Depression, Bohai Bay Basin - Jinjun Xu; Qilong Wu; Xiangang Cheng; Kaiyue Li; Yiru Zhao; Jie Wei; Fuqi Cheng; Lamei Lin (Marine and Petroleum Geology, 2025)

Mantle metasomatism by subducted Indian continental crust: Evidence from post-collisional basaltic ultrapotassic rocks in southern Tibetan plateau - Miao-Yan Zhang; Lu-Lu Hao; Yue Qi; Qiang Wang; Andrew C. Kerr; Lin Ma; Cheng-Cheng Huang; Gang-Jian Wei; Jie Li; Jin-Long Ma; Qi-Wei Li; Zi-Long Wang; et al. (Lithos, 2025)

Assessment of wetland sustainability capacity of artificial mangrove wetland on landscape scale: A case of Luoyangjiang River Estuary, China - Wei Lin; Shi-Hua Li; Xu Wei; Yang-Jian Cheng (Ecological Engineering, 2025)

2-Mercapto-1,3,4-thiadiazole-functionalized gold nanoclusters as a comparable bactericidal nanoantibiotic to vancomycin in treating methicillin-resistant Staphylococcus aureus infections - Quan-Quan Zhuang; Jia-Xin Ma; Yi-Ming Zheng; Lin-Yan Lu; Jia-Lin Yang; Qing-Qing Chen; Xiao-Li Yan; Yan-Cheng Jiang; Hao-Hua Deng; Wei Chen; Gang Liu (Chemical Engineering Journal, 2025)

Nano Sim@ZIF8@PDA modified injectable temperature sensitive nanocomposite hydrogel for photothermal/drug therapy for peri-implantitis - Dingkun Liu; Jinbing Chen; Linjuan Gao; Xing Chen; Liujun Lin; Yuan Liu; Xia Wei; Yu Pan; Yinghui Wang; Hui Cheng (Carbohydrate Polymers, 2025)

Enhancing concurrent production of volatile fatty acids and phosphorus minerals from waste activated sludge via magnesium ferrate pre-oxidation - Xiaodong Xin; Jiaqian Xie; Jian Cheng; Wei Li; Qian Liu; Yanfang Wang; Lin Li; Junguo He; Yue Yang; Liguo Zhang; Wangwang Yan (Bioresource Technology, 2025)

Beneficial effect of sodium-glucose cotransporter-2 inhibitors on mortality among patients with cancer and diabetes mellitus - Wei-Syun Hu; Cheng-Li Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Mutation Screening of ATXN1, ATXN2, and ATXN3 in Amyotrophic Lateral Sclerosis - Tianmi Yang; Qianqian Wei; Dejiang Pang; Yangfan Cheng; Jingxuan Huang; Junyu Lin; Yi Xiao; Qirui Jiang; Shichan Wang; Chunyu Li; Huifang Shang (Molecular Neurobiology, 2025)

Terpenoids with Antiangiogenic Activity from Formosan Soft Coral Caementabunda hypotentaculata - Hsin Huang; Chen-Yu Yang; Shih-Wei Wang; Limbadri Salendra; Shu-Rong Chen; Tzi-Yi Ke; Yu-Liang Yang; Yu-Chi Lin; Yuan-Bin Cheng (Marine Biotechnology, 2025)

Long-term organic farming improves the red soil quality and microbial diversity in subtropics - Yongkang Wen; Wei Yao; Taobing Yu; Lang Cheng; Qing Zhang; Jida Yang; Fangding Lin; Hongye Zhu; Anna Gunina; Yadong Yang; Kevin Z. Mganga; Zhaohai Zeng; et al. (Agriculture, Ecosystems & Environment, 2025)

Deep percolation and soil water dynamics under different sand-fixing vegetation types in two different precipitation regions in semiarid sandy Land, Northern China - Liang He; Yiben Cheng; Wenbin Yang; Jianbin Guo; Zhiming Xin; Lin Chen; Wei Xiong; Qianqian Wang; Huaiyuan Liu (Agricultural and Forest Meteorology, 2025)

Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella) - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

The herbicide 2,4-dichlorophenoxyacetic acid induces pancreatic β-cell death via oxidative stress-activated AMPKα signal downstream-regulated apoptotic pathway - Ken-An Lin; Chin-Chuan Su; Kuan-I Lee; Shing-Hwa Liu; Kai-Min Fang; Chih-Hsin Tang; Wei-Cheng Lia; Chun-Ying Kuo; Kai-Chih Chang; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology Letters, 2025)

The influence of PM2.5 exposure on SARS-CoV-2 infection via modulating the expression of angiotensin converting enzyme II - Meng-Wei Lin; Cheng-Han Lin; Jia-Rong Chang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chih-Sheng Lin (Journal of Hazardous Materials, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Analytical behaviour of concrete-encased concrete-filled steel tubular (CFST) member under combined compression and shear load - Zhi-Cheng Yang; Lin-Hai Han; Wei Li (Engineering Structures, 2025)

Nonlinear flutter critical state prediction for a bridge girder based on instantaneous power balance principle - Yue Cheng; Genshen Fang; Wei Cui; Yongle Li; Lin Zhao (Engineering Structures, 2025)

Biocompatible and stretchable chitosan piezoelectric gel with antibacterial capability and motion monitoring function for Achilles tendon rupture treatment - Zhencheng Xiong; Bingqing Lin; Cheng Huang; Ao Duan; Chaoyi Zhang; Guangliang Qiang; Wenzheng Liu; Renliang Zhao; Xiangtian Deng; Dong Wang; Zilu Ge; Guanglin Wang; et al. (Carbohydrate Polymers, 2025)

Indoxyl Sulfate Induces Ventricular Arrhythmias Attenuated by Secretoneurin in Right Ventricular Outflow Tract Cardiomyocytes - Yuan Hung; Chen-Chuan Cheng; Yen-Yu Lu; Shih-Yu Huang; Yao-Chang Chen; Fong-Jhih Lin; Wei-Shiang Lin; Yu-Hsun Kao; Yung-Kuo Lin; Shih-Ann Chen; Yi-Jen Chen (Cardiovascular Toxicology, 2025)

Comammox Nitrospira and ammonia-oxidizing bacteria are metabolically active in a subtropical estuarine wetland - Mengmeng Feng; Yongxin Lin; Guiping Ye; Zi-Yang He; Dong Zhu; Hang-Wei Hu; Yuheng Cheng; Fengyi Han; Ping Yang; Ji-Zheng He (Applied Soil Ecology, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

A high-resolution multiproxy speleothem record of Eastern China hydroclimate variation during last glacial maximum - Shuyu Xue; Hongbin Zhang; Michael L. Griffiths; Chengfei He; Yitao Liu; Junhua Huang; Hai Cheng; Wei Guo; Shitou Wu; Jianzong Zhou; Youfeng Ning; Lin Chen; et al. (Quaternary Science Reviews, 2025)

Effects of plant species on reverse osmosis concentrate treatment in constructed wetlands: Performance, plant growth, and microbial community structure - Jie Wang; Tengfei Hu; Xiaohan Wei; Bin Xu; Xiaoyu Liu; Xiaoliang Zhai; Lin Chen; Wenxian Wang; Wenming Song; Shu Chen; Lihua Cheng; Xiaolin Zhou (Journal of Water Process Engineering, 2025)

Probabilistic mapping of imbalanced data for groundwater contamination using classification algorithms: Performance and reliability - Yang Qiu; Aiguo Zhou; Hanxiang Xiong; Defang Zhang; Cheng Su; Shizheng Zhou; Lin Go; Chi Yang; Hao Cui; Wei Fan; Yao Yu; Fawang Zhang; et al. (Groundwater for Sustainable Development, 2025)

In-situ reconstruction of active bismuth for enhanced CO2 electroreduction to formate - Chenchen Weng; Cheng Wang; Yang Song; Yu-Xiao Zhang; Kang Zou; Hongwu Chen; Xue Yang; Wei Lin (Chemical Engineering Journal, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Robust photothermal self-healing superhydrophobic composite coating for durable anti/de-icing applications - Jie zhu; Wen Li; Tong Wang; Huimeng Feng; Jia Cheng; Cunguo Lin; Xin Wang; Wei Wang; Shougang Chen (Chemical Engineering Journal, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Year-round natural spawning, early ontogeny, and larval rearing of the painted sweetlips, Diagramma pictum (Thunberg, 1792) in a hatchery: Potential as a new species for mariculture - Pei-Sheng Chiu; Bo-Hong Yu; Yu-Hsin Tu; Yeong-Torng Chu; Cheng-Hsuan Huang; Shine-Wei Ho; Sun-Hon Lin; Shinn-Lih Yeh; Ming-Yih Leu (Aquaculture, 2025)

Enhanced biodegradation of glyphosate by Chlorella sorokiniana engineered with exogenous purple acid phosphatase - Si-Fen Liu; Zhong-Chen Yi; Zi-Qiong Huang; Zhen-Dong Yuan; Yu-Cheng Yang; Yongteng Zhao; Qing-Yu He; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Water Research, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

Sex-specific associations between maternal exposure to metal mixtures and fetal growth trajectories: A prospective birth cohort study - Zhen-Hua Li; Cheng-Yang Hu; Si-Wei Dai; Hui-Ya Ma; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Xiu-Jun Zhang (Science of The Total Environment, 2025)

Effects of reclamation on the distribution and diversity of comammox along the coastal wetlands of China - Dongyao Sun; Yinghui Jiang; Hengchen Wei; Jun Li; Dengzhou Gao; Xianbiao Lin; Cheng Chen; Guoyu Yin; Yifei Zhang; Lijun Hou; Min Liu; Ping Han (International Biodeterioration & Biodegradation, 2025)

Unraveling the heterogeneous hydrogeological characteristics in the Choushui River alluvial fan, Taiwan, through observations from the multi-layer compaction monitoring wells - Reyhan Azeriansyah; Kuo-En Ching; Cheng-Wei Lin; Kuo-Chin Hsu; Pei-Ching Tsai; Chao-Lung Yeh; Ruey-Juin Rau (Engineering Geology, 2025)

Effect of anti-diabetic agent on interstitial lung disease in patients with diabetes mellitus - Wei-Syun Hu; Cheng-Li Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Plant litter crust enhances nitrogen accumulation by regulating microbial diversity and urease activity in semi-arid sandy soils - Zhen Cheng; Wei Liu; Zhigang Li; María José Carpio; Juan Carlos García-Gil; Zhanjun Wang; Gao-Lin Wu (Applied Soil Ecology, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Changes in the small-molecule fingerprints of rice planted near an industrial explosion site in Taiwan - Wen-Ling Chen; Husan-Yu Tai; Chang-Chuan Chan; Hung-Chien Lin; Ting-Hsuan Hung; Mong-Hsun Tsai; Chia-Cheng Wei; Yu-San Han; Chuan-Chou Shen (Environmental Science and Pollution Research, 2024)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Plasmonic Au-NPs photodecorated on NiCoLDH nanosheets as a flexible SERS sensor for the real-time detection of fipronil - Nazar Riswana Barveen; Sathishkumar Chinnapaiyan; Che-Wei Zeng; Chi-Hsien Huang; Yen-Yu Lin; Yu-Wei Cheng (Journal of Hazardous Materials, 2024)

Deep insights into the assembly mechanisms, co-occurrence patterns, and functional roles of microbial community in wastewater treatment plants - Zi-Yan Wei; Min Feng; Ding-Xi Zhang; Cheng-Ying Jiang; Ye Deng; Zhu-Jun Wang; Kai Feng; Yang Song; Nan Zhou; Yu-Lin Wang; Shuang-Jiang Liu (Environmental Research, 2024)

Injectable responsive chemodynamic hydrogel for the sustained and localized delivery of a ferroptosis inducer to improve anticancer therapy - Chu-Hung Chung; Tzu-Wei Lu; Chi Lin; Cheng-Wei Lin; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Blocking endogenous phosphorus release in sediments by a hydrotalcite mixture synthesized with natural sepiolite and discarded cans - Fulong Cheng; Jie Pan; Changxin Zhao; Wei Li; Yuting Peng; Zuo Zhang; Yanjuan Lin; Guowen Chen (Applied Clay Science, 2024)

Investigation of the abasic sites induced by hydrogen peroxide and methyl methanesulfonate in calf thymus DNA and BEAS-2B cells - Dat Thanh Dinh; Gilang Putra Bahari; Qi Xu; Cheng-Hao Wei; Dar-Ren Chen; Wei-Chung Hsieh; Po-Hsiung Lin (Toxicology Letters, 2024)

Dissection of molecular mechanisms of liver injury induced by microcystin-leucine arginine via single-cell RNA-sequencing - Yunmeng Bai; Yali Song; Miaoran Li; Jinhuan Ou; Hong Hu; Nan Xu; Min Cao; Siyu Wang; Lin Chen; Guangqing Cheng; Zhijie Li; Gang Liu; et al. (Journal of Environmental Sciences, 2024)

Eco-friendly synthesized zeolitic imidazolate framework-8 enables one-step cerium recovery from water - Ying Zhou; Shengshou Ma; Purui Lin; Changzhong Liao; Cheng-Wei Kao; Miaoling Chen; Minhua Su; Kaimin Shih (Chemical Engineering Journal, 2024)

Gel electrolyte design for nonflammable lithium-ion batteries with high-rate and high-voltage characteristics - Po-Wei Huang; Qin-Cheng Zhang; Ming-Yuan Hung; Yan-Cheng Lin; Hong-Kang Tian; Yuh-Lang Lee; Jeng-Shiung Jan; Hsisheng Teng (Chemical Engineering Journal, 2024)

Tin-based dual-modification enabling enhanced air stability and electrochemical performance for Li5.5PS4.5Cl1.5 in all-solid-state lithium metal batteries - Jie Yang; Ziling Jiang; Chen Liu; Lin Li; Siwu Li; Zhongkai Wu; Chaochao Wei; Qiyue Luo; Long Zhang; Shijie Cheng; Chuang Yu (Chemical Engineering Journal, 2024)

Stabilization of single crystal LiNi0.90Mn0.05Co0.05O2 via ZrO2 dual-functional coating enables superior performance for solid-state lithium battery - Chen Liu; Qiyue Luo; Lin Li; Chaochao Wei; Siwu Li; Xia Li; Wanming Li; Zihan Zhang; Zhongkai Wu; Zilin Jiang; Hui Yang; Long Zhang; et al. (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Role of HIF-1α-Activated IL-22/IL-22R1/Bmi1 Signaling Modulates the Self-Renewal of Cardiac Stem Cells in Acute Myocardial Ischemia - Wei Lee; Syuan-Ling Lin; Chih-Sheng Chiang; Jui-Yu Chen; Wee-Wei Chieng; Shu-Rou Huang; Ting-Yu Chang; B. Linju Yen; Mien-Chie Hung; Kuan-Cheng Chang; Hsu-Tung Lee; Long-Bin Jeng; et al. (Stem Cell Reviews and Reports, 2024)

Exosomal miR-21-5p derived from endometrial stromal cells promotes angiogenesis by targeting TIMP3 in ovarian endometrial cysts - Liyuan Sun; Yan Cheng; Jing Wang; Di Wu; Lin Yuan; Xiaoyu Wei; Yan Li; Jie Gao; Guangmei Zhang (Journal of Molecular Medicine, 2024)

Safety analysis code development and validation for lead-cooled fast reactor with helical coiled once-through steam generator - Jiaxin Zhang; Chenglong Wang; Wenxi Tian; G.H Su; Suizheng Qiu; Lin Xian; Kun Cheng; Xiao Chu; Shiying Wei; Guo Chen (Annals of Nuclear Energy, 2024)

Facile coupling of plasmonic Au-NPs on ZnS NFs as a robust SERS substrate for toluidine blue detection and degradation - Nazar Riswana Barveen; Sathishkumar Chinnapaiyan; Chi-Hsien Huang; Yen-Yu Lin; Jia-Lun Xu; Yu-Wei Cheng (Analytica Chimica Acta, 2024)

Formation Mechanism and Petroleum Geological Significance of (Ferro) Dolomite Veins from Fractured Reservoirs in Granite Buried Hills: Insights from Qiongdongnan Basin, South China Sea - Wei Duan; Cheng-Fei Luo; Lin Shi; Jin-Ding Chen; Chun-Feng Li (Journal of Marine Science and Engineering, 2024)
This study employs logging, petrology, and geochemistry to investigate the characteristics, origin, and hydrocarbon significance of fractures and (ferro) dolomite veins in a buried hill in the Qiongdongnan (QDN) Basin, South China Sea. We show that the study area is mainly characterized by three stages of fracturing with medium-high dipping angles. The orientation of the fractures is mainly NNW–SSE, consistent with the fault system strike formed by the Mesozoic–Cenozoic tectonic activity in the basin. (Ferro) dolomite veins in the fractures can be classified into three stages, all of which can be even observed in individual fractures. The first stage is the powdery crystal dolomite veins grown mainly on the fracture surface, which have the highest strontium isotope values, as well as high contents of the Mg element and extremely low contents of the Fe and Mn elements. The first-stage veins were formed in a relatively open oxidized environment, and the vein-forming fluids exhibit characteristics of mixing formation water and atmospheric freshwater within the fractures. The second stage, involving fine-crystal dolomite veins, was formed in a buried diagenetic environment where groundwater mixed with deep hydrothermal fluids, and contained the highest carbon isotope values, more Fe and Mn elements, and less Mg element than the first stage. The third stage of medium-crystal ankerite veins was formed in the latest stage, with the lowest strontium and oxygen isotope values. This was mainly a result of deep hydrothermal formation in which the rock-forming material formed from the interaction between the hydrothermal fluid and the iron-rich and aluminosilicate minerals in the surrounding granite of the fractures. We conclude that the multi-phase tectonic movements form a massive scale reticulated fracture inside the granite buried hill, which effectively improves the physical condition of the gas reservoirs. The gas reservoirs remain of high quality, despite the filling of the three stages of (ferro) dolomite veins.

Effects of Taurine and Enzymatic Cottonseed Protein Concentrate Supplementation in Low-Fishmeal Diet on Growth, Liver Antioxidant Capacity, and Intestinal Health of Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Zhong Huang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2024)
This study was conducted to investigate the impacts of the dietary addition of taurine and enzymatic cottonseed protein concentrate (ECPC) in low-fishmeal diet on the growth performance, plasma biochemical indices, hepatic antioxidant capacity, intestinal anti-inflammatory capacity, intestinal microflora, and muscle quality of golden pompano (Trachinotus ovatus). A total of three isonitrogenous diets were given to 225 golden pompanos (5.6 ± 0.14 g). They were randomly divided into nine cages (1.0 m × 1.0 m × 1.5 m; three cages per treatment) with equal stocking numbers of twenty-five fish per cage. The results indicated that the CSM-TC group significantly increased the growth performance of juvenile T. ovatus (p

Field performance of 15 rain gardens in different cities in Taiwan - Chi-Feng Chen; Yi-Wei Chen; Cheng-Han Lin; Jen-Yang Lin (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Achieving over 42 % indoor efficiency in wide-bandgap perovskite solar cells through optimized interfacial passivation and carrier transport - Zhong-En Shi; Ta-Hung Cheng; Chien-Yu Lung; Chi-Wei Lin; Chih-Lin Wang; Bing-Huang Jiang; Yu-Sheng Hsiao; Chih-Ping Chen (Chemical Engineering Journal, 2024)

Current status of molecular rice breeding for durable and broad-spectrum resistance to major diseases and insect pests - Xiaoyan Cheng; Guohua Zhou; Wei Chen; Lin Tan; Qishi Long; Fusheng Cui; Lei Tan; Guoxing Zou; Yong Tan (Theoretical and Applied Genetics, 2024)
In the past century, there have been great achievements in identifying resistance ( R ) genes and quantitative trait loci (QTLs) as well as revealing the corresponding molecular mechanisms for resistance in rice to major diseases and insect pests. The introgression of R genes to develop resistant rice cultivars has become the most effective and eco-friendly method to control pathogens/insects at present. However, little attention has been paid to durable and broad-spectrum resistance, which determines the real applicability of R genes. Here, we summarize all the R genes and QTLs conferring durable and broad-spectrum resistance in rice to fungal blast, bacterial leaf blight (BLB), and the brown planthopper (BPH) in molecular breeding. We discuss the molecular mechanisms and feasible methods of improving durable and broad-spectrum resistance to blast, BLB, and BPH. We will particularly focus on pyramiding multiple R genes or QTLs as the most useful method to improve durability and broaden the disease/insect spectrum in practical breeding regardless of its uncertainty. We believe that this review provides useful information for scientists and breeders in rice breeding for multiple stress resistance in the future.

Development of Quantitative Norms for Normal Lung Uptake Based on Three-Dimensional Gallium-67 Single Photon Emission Computed Tomography/Computed Tomography - Tzyy-Ling Chuang; Wei-Lin Li; Yu-Ching Hs; Jyh-Cheng Chen; Yuh-Feng Wang (Journal of Medical and Biological Engineering, 2024)
Purpose Gallium-67 (Ga-67) lung scans assess alveolitis and interstitial lung disease, with Ga-67 accumulation correlating with inflammation intensity as seen in lung biopsy sections. Both semi-quantitative and quantitative methods have been used, with the latter providing an inflammatory activity index linked to lung lavage and histopathological scores. However, differing reference points result in varying outcomes. This study aimed to establish standard Ga-67 index parameters using semi-quantitative analysis and a linear regression model based on planar and SPECT/CT images. Methods Twenty subjects without lung disease received a 5–6 mCi Ga-67 injection via the ankle. Both planar and SPECT/CT images were analyzed, with semi-quantitative values assessed using GraphPad Prism 9.5.1. Results Compared to planar images, SPECT/CT acquisitions for the lung-to-arm uptake ratio proved the most reliable indicator for assessing lung inflammation. Increased lung Ga-67 uptake was defined as greater than 2 standard deviations from the average Ga-67 uptake for healthy subjects. The normal range was 0.065 ± 0.049 for the right side and 0.076 ± 0.070 for the left side. Conclusion Lung-to-arm ratios in SPECT/CT images are more accurate than those in planar images. This method should be adopted as a standard clinical practice, providing more reliable diagnostic information and improving patient management. Future studies should compare patients without lung disease to those with lung disease to determine the diagnostic benefit of these norms.

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Active longevity and aging: dissecting the impacts of physical and sedentary behaviors on longevity and age acceleration - Ting Yu Lu; Jiao Wang; Chao Qiang Jiang; Ya Li Jin; Kar Keung Cheng; Tai Hing Lam; Wei Sen Zhang; Lin Xu (GeroScience, 2024)
Background To examine the associations of physical activity (PA) and sedentary behavior (SB) with longevity and age acceleration (AA) using observational and Mendelian randomization (MR) studies, and quantify the mediating effects of lipids. Methods In Guangzhou Biobank Cohort Study (GBCS), PA and SB were assessed by the Chinese Version of the International Physical Activity Questionnaire. Longevity was defined as participants whose age at follow-up or at death was at or above the 90th age percentile. AA was defined as the residual resulting from a linear model that regressed phenotypic age against chronological age. Linear regression and Poisson regression with robust error variance were used to assess the associations of total and specific PA in different intensities, and SB with AA and longevity, yielding βs or relative risks (RRs) and 95% confidence intervals (CIs). Two-sample MR was conducted to examine the causal effects. Mediation analysis was used to assess the mediating effects of lipids. Results Of 20,924 participants aged 50 + years in GBCS, during an average follow-up of 15.0 years, compared with low PA, moderate and high PA were associated with higher likelihood of longevity (RR (95% CI): 1.56 (1.16, 2.11), 1.66 (1.24, 2.21), respectively), and also cross-sectionally associated with lower AA (β (95% CI): -1.43 (-2.41, -0.45), -2.09 (-3.06, -1.11) years, respectively). Higher levels of moderate PA (MPA) were associated with higher likelihood of longevity and lower AA, whereas vigorous PA (VPA) showed opposite effects. The association of PA with longevity observed in GBCS was mediated by low-density lipoprotein cholesterol (LDL-C) by 8.23% (95% CI: 3.58–39.61%), while the association with AA was mediated through LDL-C, triglycerides and total cholesterol by 5.13% (3.94–7.30%), 7.81% (5.98–11.17%), and 3.37% (2.59–4.80%), respectively. Additionally, in two-sample MR, SB was positively associated with AA (β (95% CI): 1.02 (0.67, 1.36) years). Conclusions PA showed protective effects on longevity and AA, with the effects being partly mediated through lipids. Conversely, SB had a detrimental impact on AA. MPA was associated with higher likelihood of longevity and reduced AA, whereas VPA showed adverse effects. Our findings reinforce the recommendation of “sit less and move more” to promote healthy longevity, and highlight the potential risks associated with VPA in the elderly.

MCT1-mediated transport of valeric acid promotes porcine preimplantation embryo development by improving mitochondrial function and inhibiting the autophagic AMPK-ULK1 pathway - Xiu-Li Zhang; Zhi-Yong An; Gao-Jie Lu; Tuo Zhang; Cheng-Wei Liu; Meng-Qi Liu; Qing-Xin Wei; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Evolutionary trajectory of TRPM2 channel activation by adenosine diphosphate ribose and calcium - Cheng Ma; Yanping Luo; Congyi Zhang; Cheng Cheng; Ning Hua; Xiaocao Liu; Jianan Wu; Luying Qin; Peilin Yu; Jianhong Luo; Fan Yang; Lin-Hua Jiang; et al. (Science Bulletin, 2024)

Structurally diverse diterpenoids from the seeds of Caesalpinia minax Hance and their bioactivities - Wen-Chao Tu; Lin-Fen Ding; Liu-Dong Song; Yong-Jiao Li; Run-Cheng Yan; Yun Wu; Wei-Yang Feng; Xing-De Wu (Phytochemistry, 2024)

Transitioning weathered oil fields towards new energy: A review on utilizing hydrogenotrophic methanogens for petroleum hydrocarbons remediation - Jiaping Zhou; Wei-Han Lin; Ying-Liang Yu; Cheng-Di Dong; Haibing Zhang; Zhongtao Hu; Chih-Ming Kao (Journal of Hazardous Materials, 2024)

Natural pyrethrins induce cytotoxicity in SH-SY5Y cells and neurotoxicity in zebrafish embryos (Danio rerio) - Wei-Guo Wang; Shou-Lin Li; Bin Liu; Ning Tang; Cheng Zhang; Xu-Feng Jiang; Li-Ming Tao; Wen-Ping Xu; Yang Zhang (Environmental Research, 2024)

Experimental study of high-mode buckling behavior of flat steel core in a buckling-restrained brace - Pao-Chun Lin; Chih-Wei Chang; Bing-Cheng Wu (Engineering Structures, 2024)

Assessment of the antimicrobial and immunomodulatory activity of QS-CATH, a promising therapeutic agent isolated from the Chinese spiny frogs (Quasipaa spinosa) - Wei-Cheng Zheng; Xiao-Yun Cheng; Yu-Hui Tao; Yue-Song Mao; Cheng-Pu Lu; Zhi-Hua Lin; Jie Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Edible squid ink proteoglycans as a multifunctional sustainable additive for silk coatings: Fire protection, UV shielding and as a colorant - Wen-Jie Jin; Wei-Lin He; Sandro Lehner; Xian-Wei Cheng; Sabyasachi Gaan; Jin-Ping Guan (Chemical Engineering Journal, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Improvement of the Diagnostic Method for the Detection of Parasite Eggs Using the Formalin Ethyl Acetate Concentration Technique - Jia-Hung Liou; Te-Ling Lu; Hui-Fen Cheng; Long-Wei Lin; Po-Cheng Kung; Hong-Jing Chuang; Te-Hsiu Lee; Chee-Hong Chan; Te-Jung Lu (Acta Parasitologica, 2024)

Exploring the novel benefits of leucine: Protecting nitrite-induced liver damage in sub-adult grass carp (Ctenopharyngodon idella) through regulating mitochondria quality control - Lu-Lu Zhen; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

The relationship between landscape pattern and plant species diversity in east Dongting lake wetland based on different Eco-environment - Dongdong Zhang; Yang Lin; Wei Xiao; Deming Wang; Zihe Wang; Xingjian Jin; Tianzhuo Cheng; Jie Zhang; Peng Yi (Environmental Pollution, 2024)

Rapid differential diagnosis of periprosthetic joint infection by microdroplet reaction on portable biochip and indicator - Zheng Liu; Jimei Chi; Zewei Lian; Yaqi Yang; Lijun Cheng; Xiaoxue Lin; Xuwei He; Xiaojian Ji; Chenxuan Yang; Yunhao Tang; Minzhi Yang; Zhisen Gao; et al. (Chemical Engineering Journal, 2024)

Surface ligand engineering of perovskite quantum dots for n-type and stretchable photosynaptic transistor with an ultralow energy consumption - Wei-Cheng Chen; Yan-Cheng Lin; Zih-Syuan Syu; Ya-Shuan Wu; Kai-Wei Lin; Cheng-Liang Liu; Chi-Ching Kuo; Wen-Chang Chen (Chemical Engineering Journal, 2024)

Warming enhanced the interaction effects of fungi and fungivores and soil potassium mineralization in tropical forest - Feng Sun; Guanzhao Yan; Wei Lin; Wei He; Xianli Cheng; Yingwen Li; Akash Tariq; Jordi Sardans; Josep Penuelas; Jinchuang Wang; Mei Wang; Yuelin Li; et al. (CATENA, 2024)

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Two new aryltetralin-type lignans from Camellia oleifera husk - Huai-yu Cheng; Tian-qi Xu; Ya-lin Hu; Qing Shu; Wei Xu; Chun-lin Fan; Guang-xiong Zhou (Natural Product Research, 2024)

Influences on medical app adoption by patients: the unified theory of acceptance and use of technology model and the moderating effects of technology readiness - Yung-Zung Chang; Chen-Wei Yu; Cheng-Min Chao; Fang-Chen Lin (The Social Science Journal, 2024)

Number of global change factors alters plant-soil feedbacks via its effect on soil fungal communities - Wei Xue; Lin Huang; James D. Bever; Cheng Du; Hao-Ming Yuan; Lin-Xuan He; Xiao-Mei Zhang; Fei-Hai Yu (Soil Biology and Biochemistry, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Arbuscular mycorrhizal fungi reduce soil N2O emissions by altering root traits and soil denitrifier community composition - Tangqing He; Wei Lin; Shuo Yang; Jiaqi Du; Bhoopander Giri; Cheng Feng; Frank S. Gilliam; Fuliang Zhang; Xiaoquan Zhang; Xuelin Zhang (Science of The Total Environment, 2024)

Actin-related protein MoFim1 modulated the pathogenicity of Magnaporthe oryzae by controlling three MAPK signaling pathways, appressorium formation, and hydrophobicity - Yun-Yun Wei; Xue-Ming Zhu; Xiao-Hong Liu; Fu-Cheng Lin; Shuang Liang (Physiological and Molecular Plant Pathology, 2024)

Characterization of the individual domains of the Bacillus thuringiensis Cry2Aa implicates Domain I as a possible binding site to Helicoverpa armigera - Meng Meng; Cheng Shen; Manman Lin; Jiafeng Jin; Wei Chen; Xiao Zhang; Chongxin Xu; Xiaodan Hu; Qing Zhu; Chengyu Chen; Yajing Xie; Ofentse Jacob Pooe; et al. (Journal of Invertebrate Pathology, 2024)

Does invasive submerged macrophyte diversity affect dissimilatory nitrate reduction processes in sediments with varying microplastics? - Xueyuan Gao; Xiaowei Li; Yingcai Wang; Cheng Lin; Yanxia Zuo; Xiaolu Li; Wei Xing (Journal of Hazardous Materials, 2024)

Urine cadmium and urolithiasis: A systematic review and meta-analysis - Yuan-Hsin Chen; Chih-Fu Wei; Ya-Yun Cheng; Carol Mita; Chinh Lu Duc Hoang; Cheng-Kuan Lin; Yu-Tzu Chang; David C. Christiani (Environmental Research, 2024)

Cu-based bubble and ion sieve for ampere-level hydrogen evolution - Si-Wei Yan; Chuan-Qi Cheng; Fei-Fei Zhang; Ze-Yu Zhang; Kui Lin; Peng-Fei Yin; Rui Zhang; Jing Yang; Cun-Ku Dong; Jing Mao; Hui Liu; Xi-Wen Du (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Mineralization of SF6 and NF3 fluorinated compounds for greenhouse gas abatement by oxalates - Ndumiso Vukile Mdlovu; Kuen-Song Lin; Cheng-Yang Tang; Wei-Chung Chen; Jamshid Hussain (Chemosphere, 2024)

Cysteine and glycine-rich protein 2 is crucial for maintaining the malignant phenotypes of gliomas through its action on Notch signalling cascade - Lingtong Liu; Fei Li; Lingxue Zhang; Yingying Cheng; Lin Wu; Ru Tie; Xiaobing Jiang; Wenwen Gao; Bochuan Liu; Yao Wei; Pan Chang; Jun Xu; et al. (Toxicology and Applied Pharmacology, 2024)

Nitrogen fertilization modulates rice phyllosphere functional genes and pathogens through fungal communities - Wei-Feng Wu; Xin-Yuan Li; Song-Can Chen; Bing-Jie Jin; Chun-Yan Wu; Gang Li; Cheng-liang Sun; Yong-Guan Zhu; Xian-Yong Lin (Science of The Total Environment, 2024)

Energy-saving and low-carbon leather production: AI-assisted chrome tanning process optimization - Long Zhang; Qingsu Cheng; Chunhua Wang; Changping Huang; Wei Lin (Journal of Cleaner Production, 2024)

Reconstruction of Fe sacrifice protective layer enables highly effective CoP catalyst for hydrogen evolution reaction at high current density - Yingying Xu; Yingxia Zhao; Ming Sun; Wei Xie; Ying Wu; Gao Cheng; Yuanhong Zhong; Shenbo Han; Lin Yu (Chemical Engineering Journal, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

Metabolomic profiling of maternal plasma identifies inverse associations of acetate and urea with anti-SARS-CoV-2 antibody titers following COVID-19 vaccination during pregnancy - An-Shine Chao; Chiao-Yun Lin; Meng-Han Chiang; Kuan-Ying Lu; Cheng-Kun Tsai; Kuan-Ju Chen; Chih-Wei Chien; Ting-Shu Wu; Yao-Lung Chang; Angel Chao; Gigin Lin; Chih-Yung Chiu (Journal of Molecular Medicine, 2024)

An observational prospective study based on a large cohort of HIV-negative neurosyphilis patients with particular reference to the Jarisch-Herxheimer reaction - Rui-Rui Peng; Juan Wu; Wei Zhao; Lin Zhu; Zhifang Guan; Xin Gu; Mei Shi; Junjun Yu; Yanchun Cheng; Pingyu Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The purpose of this study is to outline a complete picture of Jarisch-Herxheimer reaction (JHR) in the central nervous system among HIV-negative neurosyphilis patients. Methods A prospective study cohort of 772 cases with almost all stages of neurosyphilis depicted the features of JHR including occurrence rate, risk profiles, clinical manifestations, medical management and prognosis. Results The total occurrence rate of JHR was 9.3% (95% CI, 7.3-11.4%), including 4.1% (95% CI, 2.7-5.6%) with severe JHR. The reaction started 5 h after treatment initiation, peaked after 8 h, and subsided after 18 h. Patients with severe JHR experienced a longer recovery time (26 h). Patients with general paresis (OR = 6.825), ocular syphilis (OR = 3.974), pleocytosis (OR = 2.426), or a high CSF-VDRL titre (per log 2 titre increase, OR = 2.235) were more likely to experience JHR. Patients with general paresis had an 11.759-fold increased risk of severe JHR. Worsening symptoms included cognitive impairment, mania, nonsense speech, and dysphoria, while symptoms of hallucination, urination disorder, seizures, myoclonus, or aphasia appeared as new-onset symptoms. Neurosyphilis treatment did not need to be interrupted in most patients with JHR and could be reinstated in patients with seizures under supportive medication when JHR subsided. Conclusion Severe JHR displayed a 4.1% occurrence rate and clinicians should pay particular attention to patients at a higher risk of JHR. The neurosyphilis treatment regime can be restarted under intensive observation for patients with severe JHR and, if necessary, supportive medication should be initiated and continued until the end of therapy.

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Fully automated learning and predict price of aquatic products in Taiwan wholesale markets using multiple machine learning and deep learning methods - Yi-Ting Lai; Yan-Tsung Peng; Wei-Cheng Lien; Yun-Chiao Cheng; Yi-Ting Lin; Chen-Jie Liao; Yu-Shao Chiu (Aquaculture, 2024)

Seg2Tunnel: A hierarchical point cloud dataset and benchmarks for segmentation of segmental tunnel linings - Wei Lin; Brian Sheil; Pin Zhang; Biao Zhou; Cheng Wang; Xiongyao Xie (Tunnelling and Underground Space Technology, 2024)

Activation of RXRα exerts cardioprotection through transcriptional upregulation of Ndufs4 in heart failure - Mingyan Shao; Lingru Li; Lin Ma; Chao Song; Weili Li; Yawen Zhang; Wenkun Cheng; Yun Chen; Ye Yang; Qian Wang; Chun Li; Qi Wang; et al. (Science Bulletin, 2024)

An efficient solution based on the synergistic effects of nickel foam in NiFe-LDH nanosheets for oil/water separation - Xinchun Lu; Liguo Shen; Hongjun Lin; Lei Han; Jiarong Du; Cheng Chen; Jiaheng Teng; Bisheng Li; Wei Yu; Yanchao Xu (Journal of Hazardous Materials, 2024)

Overall quality changes and deterioration mechanism of fragrant rapeseed oils during 6-Month storage - Chen Chen; Ping-Ping Ye; Feng-Jie Cui; Ming Tan; Hai-Bo Zhang; Tong-Lin Zhou; Jian-Cheng Shi; Xue-Quan Shu; Zhi-Wei Chen (Food Chemistry, 2024)

hOGG1: A novel mediator in nitrosamine-induced esophageal tumorigenesis - De-Rong Tang; Cheng-Lin Li; Zhi-Yun Xu; Zhen-Zhong Zhang; Qian-Wei Wang; Jian-Qiang Zhao (Food and Chemical Toxicology, 2024)

Influence of desiccation during freeze-thaw cycles on volumetric shrinkage and tensile strength of compacted clayey soils - Yao Wei; Chao-Sheng Tang; Cheng Zhu; Qing Cheng; Yang Lu; Lin Li; Ben-Gang Tian; Bin Shi (Engineering Geology, 2024)

Quantifying payloads of antibody‒drug conjugates using a postcolumn infused-internal standard strategy with LC‒MS - Chih-Ning Cheng; Hsiao-Wei Liao; Ching-Hung Lin; Wen-Chi Chang; I-Chun Chen; Yen-Shen Lu; Ching-Hua Kuo (Analytica Chimica Acta, 2024)

Higher stochasticity in comammox Nitrospira community assembly in upland soils than the adjacent paddy soils at a regional scale - Mengmeng Feng; Yongxin Lin; Zi-Yang He; Hang-Wei Hu; Shengsheng Jin; Jia Liu; Song Wan; Yuheng Cheng; Ji-Zheng He (Science of The Total Environment, 2024)

A novel BACG inverse reliability algorithm for efficient and robust reliability-based topology optimization of marine structures - Yupeng Cui; Baolei Zhang; Yang Yu; Siyuan Cheng; Mingxiu Wei; Zihang Jin; Lin Song (Ocean Engineering, 2024)

Efficient hydrogen recovery from wastewater treatment by piezo-photocatalytic heterostructure - Xinning Dai; Zhujun Liu; Zhihan Zhao; Jun Wang; Hongbing Luo; Lin Cheng; Wei Chen (Journal of Cleaner Production, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Impacts of ship emissions and sea-land breeze on urban air quality using chemical characterization, source contribution and dispersion model simulation of PM2.5 at Asian seaport - Yu-Lun Tseng; Wen-Hsi Cheng; Chung-Shin Yuan; Kuo-Cheng Lo; Chitsan Lin; Chia-Wei Lee; Gerry Bagtasa (Environmental Pollution, 2024)

Advances in synthesis and application of amphoteric polymer-based water treatment agents - Wei Yu; Liping Xiong; Jiaheng Teng; Cheng Chen; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Desalination, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Metal-phenolic nanocatalyst rewires metabolic vulnerability for catalytically amplified ferroptosis - Yang Zhu; Xuegang Niu; Tiantian Wu; Junjie Cheng; Jianhua Zou; Yuanbo Pan; Yu Tian; Wei Huang; Chengyu Ding; Yuanxiang Lin; Dezhi Kang; Xiaoyuan Chen (Chemical Engineering Journal, 2024)

Liquid-Liquid interfacial approach for rapid synthesis of Well-Crystalline Two-Dimensional Metal-Organic frameworks for nitro reduction - Jian Yang; Lulu Kong; Cheng Huang; Chongchong Wang; Shaohua Wei; Lin Zhou (Chemical Engineering Journal, 2024)

Thiosulfate/FeCl3 pre-treatment enhances short-chain fatty acid production and mitigates H2S generation during anaerobic fermentation of waste activated sludge: Performance, microbial community and ecological analyses - Boyi Cheng; Da Zhang; Qingshan Lin; Lichang Zhou; Jinqi Jiang; Xinqi Bi; Wei Jiang; Feixiang Zan; Zongping Wang; Guanghao Chen; Gang Guo (Bioresource Technology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Exploring nanoparticle emissions and size distributions during incense burning and filtration in an indoor space - Hsi-Hsien Yang; Wei-Cheng Weng; Yong-Wen Chen; Xuan-Yi Lin; Ying I. Tsai (Air Quality, Atmosphere & Health, 2024)

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

Wind-driven hydrodynamic characteristics of Lake Taihu, a large shallow lake in China - Zongpu Xue; Wei Zhu; Lin Cheng; Yi Lv; Ganyu Feng (Environmental Science and Pollution Research, 2024)

Lacticaseibacillus chiayiensis mediate intestinal microbiome and microbiota-derived metabolites regulating the growth and immunity of chicks - Xin-Dong Li; Yao Lu; Cheng-Ying Luo; Wei-Gang Xin; Xin Kang; Yi-Cen Lin; Lian-Bing Lin (Veterinary Microbiology, 2024)

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

Reduction of antigenicity and emulsibility improvement of ovalbumin by dielectric-barrier discharge plasma treatment induced structure modification - Pan-Pan Tang; Lin-Lin Zhang; Yu-Xin Xiong; Dan-Dan Jiang; Xiu-Bin Liu; Jun-Hu Cheng; Rana Muhammad Aadil; Zhi-Wei Liu (Innovative Food Science & Emerging Technologies, 2024)

Decarbonizing the energy supply chain: Ammonia as an energy carrier for renewable power systems - Chong Wei Ong; Nairen Chang; Meng-Lin Tsai; Cheng-Liang Chen (Fuel, 2024)

Unveiling the aromatic intricacies of Wuyi Rock Tea: A comparative study on sensory attributes and odor-active compounds of Rougui and Shuixian varieties - Daoliang Wang; Zhibin Liu; Xiaoye Lan; Cainan Wang; Wensong Chen; Sijia Zhan; Yaqian Sun; Weiying Su; Chih-Cheng Lin; Wei Liu; Yuan Liu; Li Ni (Food Chemistry, 2024)

Locally π-π conjugated polyimide cured triglycidyl isocyanurate epoxy resin with enhanced dielectric polarization and microwave absorption performance for X and Ku bands - Zichen Xu; Kexin Zhang; Yajie Cheng; Xiping Sun; Haofan Ren; Hao Wei; Qiang Wang; Lin Wang; Zhijia Zhang; Guojun Wang (Chemical Engineering Journal, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Sodium-glucose cotransporter-2 inhibitor in risk of sepsis/septic shock among patients with type 2 diabetes mellitus—a retrospective analysis of nationwide medical claims data - Wei-Syun Hu; Cheng-Li Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Boron deficiency decreased the root activity of Ga-exposed rice seedlings by reducing iron accumulation and increasing Ga in iron plaque - Wei-Lin Ren; Cheng-Zhi Li; Abid Ullah; Xiao-Zhang Yu (Ecotoxicology, 2024)

Macular pigments produced from microalga Chlorella sp. and applied to alleviate the pathogenic process in diabetic mice - Meng-Wei Lin; Wei-Hong Chiu; Cheng-Han Lin; Dung-Huan Liu; Pei-Ching Wu; Chih-Sheng Lin (Algal Research, 2024)

Methionine redox regulation of actin-interacting proteins primarily governs antioxidative signaling and response to the salvianolic acid B treatment in EA.hy926 cells - Ai-Cheng Wang; Xiao-Ming Qi; Qing-Fang Li; Yi-Jia Feng; Yuan-Lin Zhang; Hui-Zhi Wei; Jin-Shan Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2024)

Atomically dispersed dual-atom catalysts: A new rising star in environmental remediation - Xialiang Jiang; Cheng Chen; Junjie Chen; Shuning Yu; Wei Yu; Liguo Shen; Bisheng Li; Mingzhu Zhou; Hongjun Lin (Science of The Total Environment, 2024)

Regeneration of sedimentary phosphorus and iron in a large seasonally hypoxic estuary deciphered by 224Ra/228Th disequilibria - Zhongliang Lin; Yilin Cheng; Ergang Lian; Tong Wu; Lin Wei; Xiangming Shi; Xinyu Jiang; Liuting Yuan; Shouye Yang; Pinghe Cai (Marine Chemistry, 2024)

Performance and mechanism of sequential UV-NaClO disinfection: Inactivation and reactivation of antibiotic-resistant bacteria, disinfection byproduct formation and microbial community variation - Lihua Cheng; Xiaohan Wei; Aili Gao; Lin Zhou; Xueqing Shi; Xiaolin Zhou; Xuejun Bi; Tang Yang; Shujuan Huang (Journal of Water Process Engineering, 2024)

Modification of cellulosic adsorbent via iron-based metal phenolic networks coating for efficient removal of chromium ion - Valentino Bervia Lunardi; Kuan-Chen Cheng; Shin-Ping Lin; Artik Elisa Angkawijaya; Alchris Woo Go; Felycia Edi Soetaredjo; Suryadi Ismadji; Hsien-Yi Hsu; Chang-Wei Hsieh; Shella Permatasari Santoso (Journal of Hazardous Materials, 2024)

Evaporation and desiccation cracking of soils: Experiment evidence and insight on the freeze-thaw cycle dependence - Yao Wei; Chao-Sheng Tang; Yang Lu; Mingli Zhang; Qing Cheng; Lin Li; Bin Shi (Engineering Geology, 2024)

Effects of dietary betaine supplementation on growth performance, feed intake, intestinal histology, lipid metabolism, and immune response of black tiger shrimp (Penaeus monodon) fed diets containing two levels of raw feed attractants - Gui-Lun He; Meng-Lin Shi; Yu-Cheng Liu; Liu-Tong Chen; Xin Chen; Wen-Bo Zhu; Zheng-Bang Chen; Bei-Ping Tan; Shi-Wei Xie (Aquaculture International, 2024)

Oncogenic and immunological roles of RACGAP1 in pan-cancer and its potential value in nasopharyngeal carcinoma - Cheng-shan Zheng; Wei-mei Huang; Hong-mei Xia; Jing-lin Mi; Yuan-qing Li; Hui-qing Liang; Li Zhou; Zhou-xue Lu; Fang Wu (Apoptosis, 2024)

Protection of Pacific white shrimp (Penaeus vannamei) against white spot syndrome virus infection by nitric oxide-generating compound S-nitrosoglutathione - Qingna Lai; Chen Yu; Furong Zhao; Yunying Cheng; Qin Zheng; Changkun Pan; ZhenYue Lin; Suping Yang; Qian Zhang; Jianming Chen; Wei Wang (Aquaculture, 2024)

Effect of Streptomyces JD211 application on soil physicochemical properties and N2O emission characteristics of rice rhizosphere - Hailong Peng; Tianyu Xu; Lixin Wang; Jiaqing Yu; Xin Chen; Xin Cheng; Hanguang Li; Lin Huang; Lei Wei; Saijin Wei (Science of The Total Environment, 2024)

Highly effective degradation of ibuprofen by alkaline metal-doped copper oxides via peroxymonosulfate activation: Mechanisms, degradation pathway and toxicity assessments - Meng-Wei Zheng; Cheng-Wei Lin; Pei-Hsin Chou; Chao-Lung Chiang; Yan-Gu Lin; Shou-Heng Liu (Journal of Hazardous Materials, 2024)

VOCs hyperspectral imaging: A new insight into evaluate emissions and the corresponding health risk from industries - Chengzhi Xing; Cheng Liu; Jinan Lin; Wei Tan; Ting Liu (Journal of Hazardous Materials, 2024)

Yield loss of inferior crop species and its physiological mechanism in a semiarid cereal-legume intercropping system - Wei Wang; Jian-Hua Zhao; Meng-Ying Li; Wei Zhang; Muhammad Maqsood Ur Rehman; Bao-Zhong Wang; Fazal Ullah; Zheng-Guo Cheng; Li Zhu; Jin-Lin Zhang; Hong-Yan Tao; Wen-Ying Wang; et al. (European Journal of Agronomy, 2024)

AMPKα is active in autophagy of endothelial cells in arsenic-induced vascular endothelial dysfunction by regulating mTORC1/p70S6K/ULK1 - Ziqi Xu; Qiaoling Liu; Jinyu Li; Jingqiu Wang; Zhihan Yang; Juan Wang; Lin Gao; Jin Cheng; Jing He; Yishan Dong; Xiangnan Guo; Jing Cui; et al. (Chemico-Biological Interactions, 2024)

A Numerical Study of Moisture and Ionic Transport in Unsaturated Concrete by Considering Multi-ions Coupling Effect - Zhaozheng Meng; Yufei Zhang; Wei-kang Chen; Chuan-qing Fu; Qing Xiang Xiong; Cheng-lin Zhang; Qing-feng Liu (Transport in Porous Media, 2024)

Single-Cell Mapping of Brain Myeloid Cell Subsets Reveals Key Transcriptomic Changes Favoring Neuroplasticity after Ischemic Stroke - Fangxi Liu; Xi Cheng; Chuansheng Zhao; Xiaoqian Zhang; Chang Liu; Shanshan Zhong; Zhouyang Liu; Xinyu Lin; Wei Qiu; Xiuchun Zhang (Neuroscience Bulletin, 2024)

Psychiatric disorders in patients with type 2 diabetes mellitus on sodium-glucose cotransporter-2 inhibitors—a nationwide retrospective cohort study - Wei-Syun Hu; Cheng-Li Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Induced differentiation of primordial germ cell like cells from SOX9+ porcine skin derived stem cells - Geng Zhang; Xin-Xiang Xie; Shu-Er Zhang; Fa-Li Zhang; Chun-Xiao Li; Tian Qiao; Paul W. Dyce; Xin-Lei Feng; Wei-Bo Lin; Qi-Cheng Sun; Wei Shen; Shun-Feng Cheng (Theriogenology, 2023)

Clarification of the phosphorus release mechanism for recovering phosphorus from biofilm sludge in alternating aerobic/anaerobic biofilm system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yang Pan; Lin Chen; Liang Zhu; Yi-Ping Li; Jing-Ru Li (Science of The Total Environment, 2023)

Limonoids from the roots of Melia azedarach and their anti-inflammatory activity - Min Song; Hui-Juan Luo; Zi-Wei Li; Ling Qiu; Yu-Xin Zhao; Cheng-Wei He; Xiao-Qi Zhang; Wen-Cai Ye; Li-Gen Lin; Qing-Wen Zhang (Phytochemistry, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Single-cell RNA sequencing reveals a hierarchical transcriptional regulatory network of terpenoid biosynthesis in cotton secretory glandular cells - Jia-Ling Lin; Longxian Chen; Wen-Kai Wu; Xiao-Xiang Guo; Cheng-Hui Yu; Min Xu; Gui-Bin Nie; Jun-ling Dun; Yan Li; Baofu Xu; Ling-Jian Wang; Xiao-Ya Chen; et al. (Molecular Plant, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Hierarchical Y zeolite with accessible intracrystalline mesopores and enhanced hydrocracking performances via sequential multi-carboxyl acid and fluoroborate post-treatments - Lin-Jiao Wei; Peng Peng; Ke Qiao; Guang-Nan Cheng; Ubong Jerome Etim; Zi-Feng Yan (Fuel, 2023)

Combustion characteristics of waste styrene–butadiene rubber oil derived from thermal pyrolysis process: experiment and numerical simulation - Rusdan Aditya Aji Nugroho; Wei-Cheng Wang; Xinwei Cheng; Sivanjaneya Reddy Yelugoti; Hiew Mun Poon; Jhe-Kai Lin; Cho-Yu Lee (Fuel, 2023)

Transcriptome analysis of the effects of maternal fructose exposure during gestation and lactation on the cytoskeleton of offspring hippocampus - Yongyong Zhong; Yuchen Zou; Lin Cheng; Qing Guo; Yidan Chang; Wei Wei (Food Bioscience, 2023)

Active packaging incorporating chitosan, casein phosphopeptide, and plasmonic modification to maintain quality and regulate the respiration rate of fresh-cut Pyrus serotina Rehder during storage - Chao-Kai Chang; Fang-Yu Lin; Sheng-Yen Tsai; Mohsen Gavahian; Kuan-Chen Cheng; Chih-Yao Hou; Min-Hung Chen; Shella Permatasari Santoso; Chang-Wei Hsieh (Food Packaging and Shelf Life, 2023)

Improving soil resilience to drought climate by an eco-friendly approach - Lin Li; Chao-Sheng Tang; Jin-Jian Xu; Yao Wei; Qing Cheng; Bin Shi (Engineering Geology, 2023)

Binary-1D/2D nanomaterial-functionalization toward strong, stretchable, and anti-freezing electrically conductive organohydrogels for self-powered operation monitoring of robotic hand - Jie Zhou; Bo Tang; Dong Li; Cheng-Wei You; Yu-Yao Zhao; Lin-Yue Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Accumulated Hepatic Steatosis Grades Predicted by T2*-IDEAL Fat Fraction - Chang-Hsien Liu; Hing-Chiu Chang; Yi-Jui Liu; Wei-Ching Lin; Chi-Feng Hsieh; Te-Pao Lin; Cheng-Hsuan Juan; William Tzu-Liang; Chun-Jung Juan (Journal of Medical and Biological Engineering, 2023)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Analysis of Unidirectional Wave Spectral Characteristics in the Northeastern Waters of Taiwan - Wei-Ting Chao; Ting-Chieh Lin; Kai-Cheng Hu; Tai-Wen Hsu (Journal of Marine Science and Engineering, 2023)
Marine energy development has been actively promoted in recent years. Analyzing wave data in the surrounding sea areas is crucial for improving wave power generator efficiency. This study collected unidirectional wave spectrum data from the northeast coastal area of Taiwan (e.g., Pengjia Islet, Fugui Cape, and NTOU). It aimed to analyze the main wave types (i.e., wind waves, swell, or mixed sea) and their proportions during the northeast and non-northeast monsoon periods. The results indicate that swell waves dominate at the NTOU buoy, while wind waves dominate at the other two stations. In addition, the analysis of wave spectra ratios revealed a low percentage of unimodal spectra (only about 0.5%), and bimodal and unformed spectra presented as predominant. Furthermore, this study also introduced a brand new JW-J wave spectrum, which combines the JW and JONSWAP spectra to describe low-frequency (swell) and high-frequency (wind wave) systems, showing superior performance compared to the Torsethaugen spectrum. Finally, this research analyzed the JW-J spectrum parameters from the Pengjia Islet and Fugui Cape stations and applied these results to the NTOU bouy for effectively describing wind/swell wave variations.

Transcranial Alternating Current Stimulation in a Patient with Ataxia-Ocular Apraxia 2: a Case Report - Xiao-Ping Cheng; Wen-Hui Yu; Xia Liu; Wei Lin; Zhao-Di Wang; Xi-Chen Wang; Jun Ni; Nai-Qing Cai; Xin-Yuan Chen (The Cerebellum, 2023)

Analysis of the driving factors of the change of erosion-deposition in the Minjiang Estuary, Southeast China - Xiaohe Lai; Jianping Jia; Yuebao Hou; Beihan Jiang; Chuan Lin; Xinlu Lin; Pu Xu; Cheng Chen; Jun Jiang; Yan Liu; Wen Wei (Frontiers in Marine Science, 2023)
Understanding the evolution and driving factors of sedimentation and erosion at the mouths of small and medium-sized mountain streams during various periods is essential for regional spatial utilization, development, and sustainable economic growth. This is particularly important when considering the combined impact of climate change and human activities. This paper presents an analysis of the changes in sedimentation and erosion of mouth isobaths and underwater deltas over different periods using nautical chart data (1950-2019) and analyzes the factors driving changes in sedimentation and erosion during different periods from 1950 to 2020 based on the runoff-sediment discharge of the Minjiang River (MR) and extreme climate factors such as typhoons, especially the driving factors that caused a sudden change in the sedimentation and erosion process between 1998 and 2005. The results indicate that runoff-sediment characteristics are crucial in driving sedimentation and erosion changes. In the past 70 years, the underwater delta of the MRE has mainly experienced four stages: deposition (1950-1992) -erosion (1993-1998) -deposition (1998-2011) -erosion (2011-2019). Taking the impoundment operation of the Shuikou Reservoir in 1993 as the node, the sediment load of the Minjiang River into the sea began to decrease sharply, and then the estuary quickly showed a state of erosion. The change of sediment flux into the sea is the main driving factor for the evolution of erosion and deposition in the Minjiang River Estuary (MRE). The critical value of the erosion-deposition transition is about 570.3 × 10 4 t/yr. After the estuary entered a state of erosion in 1993-1998, significant siltation suddenly occurred in 1998-2005. The reason for the siltation in this period may be related to the frequent transit typhoons and flood events in 1998-2005. Therefore, the change of river sediment supply into the sea is the main driving factor controlling the erosion and deposition evolution of the Minjiang River estuary on a long time scale of more than 10 years, which reflects the influence of large-scale human activities on the river and estuary area in the past half century. Extreme climate events are the incentive to adjust the estuary landform in the short term. Extreme climate events will not fundamentally change the process of estuarine geomorphological evolution under the background of sediment supply reduction.

Association of mono-2-ethylhexyl phthalate with adverse outcomes in chronic hemodialysis patients - Chia-Lin Wu; Yu-Wei Fang; Yi-Chou Hou; Kuo-Cheng Lu; Wen-Hsin Tsai; Ping-Hsun Lu; Tzong-Shyuan Lee; Ko-Lin Kuo (Environmental Science and Pollution Research, 2023)
Phthalate exposure is widespread and has a global impact. Growing evidence shows that mono-2-ethylhexyl phthalate (MEHP) exposure has a negative impact on human health. However, whether MEHP exposure is associated with mortality and other adverse outcomes in hemodialysis patients remains unknown. This study prospectively enrolled 217 patients on maintenance hemodialysis from June 30, 2021, to August 16, 2022. Baseline serum MEHP, di-2-ethylhexyl phthalate (DEHP), and indoxyl sulfate (IS) concentrations were measured. Primary endpoints were all-cause mortality or composite adverse outcomes, including all-cause death plus hospitalization due to cardiovascular disease, heart failure, stroke, infection, or cancer. Serum MEHP concentrations were positively associated with DEHP but not indoxyl sulfate concentrations in hemodialysis patients. Additionally, serum MEHP concentrations were significantly and independently associated with all-cause mortality and composite adverse outcomes (adjusted hazard ratios [HRs], 1.04 and 1.03 per ng/mL, 95% confidence intervals [CIs], 1.01–1.07 and 1.00–1.05; p = 0.016 and 0.015, respectively). We found a cutoff value of MEHP for predicting both endpoints. Patients with serum MEHP concentrations of ≥ 41.8 ng/mL had much higher risks for all-cause mortality and composite adverse outcomes (adjusted HRs, 39.2 and 13; 95% CIs, 2.44–65.7 and 2.74–61.4; p = 0.011 and 0.001, respectively). MEHP exposure is significantly associated with higher risks for all-cause mortality and composite adverse outcomes. Hemodialysis patients with serum MEHP concentrations above 41.8 ng/mL had much poorer prognoses regarding both outcomes.

Direct and alternating current electric fields affect pectin esterase and cellulase in tomato (Solanum lycopersicum L.) fruit during storage - Chao-Kai Chang; Sheng-Yen Tsai; Mohsen Gavahian; Kuan-Chen Cheng; Chih-Yao Hou; Bara Yudhistira; Shu-Hui Lin; Shella Permatasari Santoso; Chang-Wei Hsieh (Postharvest Biology and Technology, 2023)

Development and application of an interactive generic physiologically based pharmacokinetic (igPBPK) model for adult beef cattle and lactating dairy cows to estimate tissue distribution and edible tissue and milk withdrawal intervals for per- and polyfluoroalkyl substances (PFAS) - Wei-Chun Chou; Lisa A. Tell; Ronald E. Baynes; Jennifer L. Davis; Yi-Hsien Cheng; Fiona P. Maunsell; Jim E. Riviere; Zhoumeng Lin (Food and Chemical Toxicology, 2023)

Quantifying the potential effects of air pollution reduction on population health and health expenditure in Taiwan - Yi-Hsuan Roger Chen; Wan-Chen Lee; Bo-Chen Liu; Po-Chieh Yang; Chi-Chang Ho; Jing-Shiang Hwang; Tzu-Hsuan Huang; Hsien-Ho Lin; Wei-Cheng Lo (Environmental Pollution, 2023)

Unlocking the potential of elemental sulfur autotrophic denitrification through inorganic nutrient optimization - Yi-Lu Sun; Xue-Ning Zhang; Han-Lin Wang; Chen-Yang Shao; Wei-Qin Zhuang; Hao-Yi Cheng; Ji-Xian Yang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Sand-fixing vegetation regulates deep percolation and soil water dynamics in semiarid sandy land: Evidence from a deep percolation recorder and in-situ test - Liang He; Jianbin Guo; Wei Xiong; Wenbin Yang; Yiben Cheng; Lei Wang; Xuewen Lin (CATENA, 2023)

Detection of micro-plasma-induced exosomes secretion in a fibroblast-melanoma co-culture model - Han Lee; Jiunn-Der Liao; Tak-Wah Wong; Che-Wei Wu; Bo-Yao Huang; Shun-Cheng Wu; Pei-Lin Shao; Yu-Han Wei; Ming-Hsien Cheng (Analytica Chimica Acta, 2023)

Acoustic Field Radiation Prediction and Verification of Underwater Vehicles under a Free Surface - Yung-Wei Chen; Cheng-Cheng Pan; Yi-Hsien Lin; Chao-Feng Shih; Jian-Hong Shen; Chun-Ming Chang (Journal of Marine Science and Engineering, 2023)
This study aimed to examine the acoustic field radiated by propellers and underwater vehicles. For the verification of sound radiation in underwater vehicles, numerical methods are widely used in addition to experiments and propeller blade frequencies for calculation and validation. Numerical convergence and accuracy are more important for near-field and far-field problems. This paper uses the boundary element method (BEM) to assess the convergence of the finite volume method (FVM). In this study, the FVM, including the Reynolds-averaged Navier–Stokes method and the Ffowcs Williams–Hawkings (FW-H) acoustic model, is used to investigate the influence of various geometric inflows on the hydrodynamic and noise performance of the propeller. Then, the sound radiation of the FVM is compared with the BEM at the far field to determine the number of meshed elements. Furthermore, spectral analysis is being conducted to examine the noise generated by the underwater vehicle and propeller. The objective is to investigate the influence of the free surface on propeller efficiency. After verifying the numerical simulation, the results indicate that a relationship can be established between water pressure and propeller thrust under specific conditions. This relationship can be used to estimate the magnitude of propeller thrust at different water depths. The simulated results of propeller thrust, torque coefficient, propulsion efficiency, and sound radiation in this study are consistent with experimental values. This demonstrates the accuracy and practicality of the findings of numerical procedures in engineering applications.

Corrigendum to “PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet” [Toxicology and Applied Pharmacology, 470, (2023), 116557] - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Recovering phosphorus and lithium separately from wastewater and brine using a novel coupled biofilm-precipitation system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yi-Ping Li; Lin Chen; Liang Zhu; Yang Pan (Journal of Water Process Engineering, 2023)

Single atom catalysts for degradation of antibiotics from aqueous environments by advanced oxidation processes: A review - Qi Jin; Wei Liu; Yingbo Dong; Yanrong Lu; Cheng Yang; Hai Lin (Journal of Cleaner Production, 2023)

Multiple path-dominated activation of peroxymonosulfate by MOF-derived Fe2O3/Mn3O4 for catalytic degradation of tetracycline - Chensi Tang; Min Cheng; Cui Lai; Ling Li; Zhen Wei; Dengsheng Ma; Li Du; Guangfu Wang; Lu Yang; Lin Tang (Journal of Environmental Chemical Engineering, 2023)

Dietary threonine improves muscle nutritional value and muscle hardness associated with collagen synthesis in grass carp (Ctenopharyngodon idella) - Mei-Lan Wen; Pei Wu; Wei-Dan Jiang; Yang Liu; Cai-Mei Wu; Cheng-Bo Zhong; Shu-Wei Li; Ling Tang; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

The effects of prenatal PM2.5 oxidative potential exposure on feto-placental vascular resistance and fetal weight: A repeated-measures study - Weiwei Lin; Yuming Lai; Shuling Zhuang; Qiannan Wei; Hedi Zhang; Qiansheng Hu; Peng Cheng; Manman Zhang; Yuhong Zhai; Qingqing Wang; Zhenyan Han; Hongying Hou (Environmental Research, 2023)

Damage detection of bridges subjected to moving load based on domain-adversarial neural network considering measurement and model error - Zhi-Dong Li; Wen-Yu He; Wei-Xin Ren; Yi-Lin Li; Yi-Fan Li; Hua-Cai Cheng (Engineering Structures, 2023)

Multi-scale domain and microstructure engineering for the high-energy-storage BCZT based lead-free relaxor ferroelectric ceramics - Jiayue Song; Fei Yan; Jinfeng Lin; Guanglong Ge; Cheng Shi; Jin Qian; Yali Hao; Yongqi Wei; Wu Yao (Chemical Engineering Journal, 2023)

SERS-based rapid susceptibility testing of commonly administered antibiotics on clinically important bacteria species directly from blood culture of bacteremia patients - Yin-Yi Han; Jann-Tay Wang; Wei-Chih Cheng; Ko-Lun Chen; Yi Chi; Lee-Jene Teng; Juen-Kai Wang; Yuh-Lin Wang (World Journal of Microbiology and Biotechnology, 2023)
Bloodstream infections are a growing public health concern due to emerging pathogens and increasing antimicrobial resistance. Rapid antibiotic susceptibility testing (AST) is urgently needed for timely and optimized choice of antibiotics, but current methods require days to obtain results. Here, we present a general AST protocol based on surface-enhanced Raman scattering (SERS-AST) for bacteremia caused by eight clinically relevant Gram-positive and Gram-negative pathogens treated with seven commonly administered antibiotics. Our results show that the SERS-AST protocol achieves a high level of agreement (96% for Gram-positive and 97% for Gram-negative bacteria) with the widely deployed VITEK 2 diagnostic system. The protocol requires only five hours to complete per blood-culture sample, making it a rapid and effective alternative to conventional methods. Our findings provide a solid foundation for the SERS-AST protocol as a promising approach to optimize the choice of antibiotics for specific bacteremia patients. This novel protocol has the potential to improve patient outcomes and reduce the spread of antibiotic resistance.

Targeting mitochondrial dynamics by AZD5363 in triple-negative breast cancer MDA-MB-231 cell–derived spheres - Yingqiang Fu; Wei Dong; Yuting Xu; Lin Li; Xin Yu; Yuheng Pang; Liujia Chan; Yuhan Deng; Cheng Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Breast cancer stem cells (BCSCs) have been suggested to contribute to chemotherapeutic resistance and disease relapse in breast cancer. Thus, BCSCs represent a promising target in developing novel breast cancer treatment strategies. Mitochondrial dynamics in BCSCs were recently highlighted as an available approach for targeting BCSCs. In this study, a three-dimensional (3D) cultured breast cancer stem cell spheres model was constructed. Mitochondrial dynamics and functions were analyzed by flow cytometry and confocal microscopy. We have demonstrated that the protein levels of FIS 1 and Mitofusin 1 were significantly increased in BCSCs. Moreover, Capivasertib (AZD5363) administration could suppress Mitofusin1 expression in BCSCs. Our use of MitoTracker Orange and annexin V double-staining assay suggested that AZD5363 could induce apoptosis in BCSCs. The sensitivity of stem cell spheres to doxorubicin was investigated by CCK8 assay, and our results indicated that AZD5363 could re-sensitize BCSCs to Doxo. Flow cytometry analysis identified doxo-induced CD44 and CD133 expression in BCSCs could be suppressed by AZD5363. In combination with AZD536, doxo-induced apoptosis in the BCSCs was significantly increased. In conclusion, our study explored, for the first time, that AZD5363 could target mitochondrial dynamics in 3D cultured stem cell spheres (BCSCs) by regulating Mitofusin.

Field reconnaissance and observations from the February 6, 2023, Turkey earthquake sequence - Gulen Ozkula; Robert K. Dowell; Tugce Baser; Jui-Liang Lin; Ozgun A. Numanoglu; Okan Ilhan; C. Guney Olgun; Cheng-Wei Huang; Tunc Deniz Uludag (Natural Hazards, 2023)

Effects of Fermented Cottonseed Meal Substitution for Fish Meal on Intestinal Enzymatic Activity, Inflammatory and Physical-Barrier-Related Gene Expression, and Intestinal Microflora of Juvenile Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Jun Wang; Yun Wang; Zhong Huang; Wei Yu; Xiaolin Huang; Heizhao Lin; Maoyan Luo; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2023)
The present study was conducted to investigate the effects of dietary fermented cottonseed meal (FCSM) substitution for fish meal on intestinal enzymatic activity, inflammatory and physical-barrier-related gene expression, and intestinal microflora of juvenile golden pompano. The 375 golden pompanos were divided into 15 groups of 25 fish each, with three replicates for each experimental group. The fish were fed five experimental diets (0 (FM), 12.5% (CSM12.5), 25% (CSM25), 50% (CSM50), and 100% (CSM100) substitution levels) for 8 weeks. The fish were reared and fed the experimental diets under a natural-day light cycle. Compared with the control group, the activities of AMY (amylase) enzymes in the CSM12.5 group and all other groups were elevated (p

Shifts in the high-resolution spatial distribution of dissolved N2O and the underlying microbial communities and processes in the Pearl River Estuary - Xiang Cheng; Yue Dong; Fuqiang Fan; Shangbin Xiao; Jia Liu; Shengrui Wang; Wei Lin; Chunyang Zhou (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Microbial community assembly responses to polycyclic aromatic hydrocarbon contamination across water and sediment habitats in the Pearl River Estuary - Wei Lin; Fuqiang Fan; Guangming Xu; Kaiyuan Gong; Xiang Cheng; Xingyu Yuan; Cheng Zhang; Yuan Gao; Shengrui Wang; How Yong Ng; Yue Dong (Journal of Hazardous Materials, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Spatio-temporal distribution of organochlorine pesticides in agricultural soils of southeast China during 2014-2019 - Wei Zuo; Qin Lin; Xinju Liu; Lu Lv; Chunrong Zhang; Shenggan Wu; Xi Cheng; Yijun Yu; Tao Tang (Environmental Research, 2023)

Investigating the stretchability of doped poly(3-hexylthiophene)-block-poly(butyl acrylate) conjugated block copolymer thermoelectric thin films - Qing-Bao Zheng; Yan-Cheng Lin; Yen-Ting Lin; Yun Chang; Wei-Ni Wu; Jhih-Min Lin; Shih-Huang Tung; Wen-Chang Chen; Cheng-Liang Liu (Chemical Engineering Journal, 2023)

Stable chromium isotope compositions of hydrogenetic ferromanganese crusts potentially linked to primary productivity - Xiangli Wang; Jian-Ming Zhu; Guangliang Wu; Wenjing Liu; Cheng Lin; Wei Yang; Zhifang Xu; James R. Hein (Chemical Geology, 2023)

Simultaneous phosphorus recovery from wastewater and sludge by a novel denitrifying phosphorus removal system - Hao Zhang; Wei Zhang; Shuang-Shuang Zhang; Wu-Cheng Ma; Liang Zhu; Yi-Ping Li; Yang Pan; Lin Chen (Bioresource Technology, 2023)

Clinical outcomes in heart failure patients with and without atrial fibrillation receiving sodium-glucose cotransporter-2 inhibitor - Wei-Syun Hu; Cheng-Li Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

PSME3 induces radioresistance and enhances aerobic glycolysis in cervical cancer by regulating PARP1 - Xing Wei; Ke Sun; Shubo Li; Cheng Lin; Zhongheng Wei (Tissue and Cell, 2023)

Integrated ground and vertical measurement techniques to characterize overhead atmosphere: Case studies of local versus transboundary pollution - Chang-Feng Ou-Yang; Chih-Chung Chang; Sheng-Hsiang Wang; Charles C.-K. Chou; Ming-Tung Chuang; Tang-Huang Lin; Wei-Nai Chen; Ta-Chih Hsiao; Ming-Cheng Yen; Yueh-Chen Wang; Neng-Huei Lin; Jia-Lin Wang (Science of The Total Environment, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Catalytically efficient Co-CoOx-Al2O3 interface for mild temperature fatty alcohol production via fatty acid transfer hydrogenation - Yi Chen; Yongsheng Zhang; Wei Lin; Xianglin Cheng; Jianshe Wang; Xiaolong Liu; Chunbao Charles Xu; Renfeng Nie (Fuel, 2023)

The health risk of acetochlor metabolite CMEPA is associated with lipid accumulation induced liver injury - Wei-Guo Wang; Mu-Yao Li; Lin Diao; Cheng Zhang; Li-Ming Tao; Wei-Xing Zhou; Wen-Ping Xu; Yang Zhang (Environmental Pollution, 2023)

A novel flower-like nickel-metal-organic framework (Ni-MOF) membrane for efficient multi-component pollutants removal by gravity - Lei Han; Jing Ma; Hongjun Lin; Cheng Chen; Jiaheng Teng; Bisheng Li; Dieling Zhao; Yanchao Xu; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Improving oxidation removal of toluene in plasma coupling perovskite catalysts system by constructing Au sites on a La0.5Ce0.5CoO3-δ - Bin Zhu; Qi-Wei Li; Ye-Cheng Li; Ya-Qiang Xia; Jing-Lin Liu; A-Min Zhou; Xiao-Min Zhang (Chemical Engineering Journal, 2023)

Captive Reproductive Behavior, Spawning, and Early Development of White-Barred Goby Amblygobius phalaena (Valenciennes, 1837) and Examined Larval Survival and Viability at Different Water Temperatures and Salinities - Pei-Sheng Chiu; Shine-Wei Ho; Cheng-Hsuan Huang; Yen-Chun Lee; Yu-Hung Lin (Fishes, 2023)
White-barred goby Amblygobius phalaena is a highly valued marine ornamental fish, but its captive reproduction and early life history are poorly understood. In this study, the captive reproductive behavior, early development, and optimal temperature and salinity for the larval survival and viability of A. phalaena were investigated for the first time. Spawning occurred between 11:00 and 13:00, with the breeding pairs naturally spawning 24 times from 1 June 2021 to 30 June 2022. The fecundity ranged from 11,022 to 95,858 eggs per spawning event. Hatching occurred approximately 81 h and 26 min after fertilization at a temperature of 27.0 ± 0.9 °C. Newly hatched larvae had a total length (TL) of 1.91–2.03 mm with 24–26 somites. The larvae transformed into juveniles at 30 days post-hatch. Experiments were conducted at different temperatures (21, 24, 27, 30, and 33 °C) and salinities (18, 24, 30, and 36 ppt) to determine the optimal conditions for larval survival and viability. The results indicate that the most suitable conditions in terms of temperature were in the range of 21–27 °C and 30 ppt for salinity. These findings provide valuable insights for the future development of captive-breeding techniques and the commercial production of other marine ornamental gobies.

Nighttime light perspective in urban resilience assessment and spatiotemporal impact of COVID-19 from January to June 2022 in mainland China - Yaohui Liu; Wenyi Liu; Xinyu Zhang; Yu Lin; Guoqiang Zheng; Zhan Zhao; Hao Cheng; Lutz Gross; Xiaoli Li; Benyong Wei; Fei Su (Urban Climate, 2023)

PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

DRL-based target interception strategy design for an underactuated USV without obstacle collision - Chenming Zhang; Peng Cheng; Bin Lin; Weidong Zhang; Wei Xie (Ocean Engineering, 2023)

Distribution of hydrogen isotope in the soil around the Qinshan Nuclear Power Plant - Jie Liang; Wen-yu Cheng; Jing-lin Li; Xiao-chong Xue; Ke Deng; Chao-fei Liang; Lin Du; Qin Zhang; Wei Liu (Journal of Environmental Radioactivity, 2023)

Variation in microbiological heterogeneity in Chinese strong-flavor Baijiu fermentation for four representative varieties of sorghum - Mao-Ke Liu; Yu-Ming Tang; Cheng-Yuan Liu; Xin-Hui Tian; Ji-Wei Zhang; Xiao-Li Fan; Kai-Feng Jiang; Xian-Lin Ni; Xin-Yu Zhang (International Journal of Food Microbiology, 2023)

Metabolomic characteristics in human CD34+ hematopoietic stem/progenitor cells exposed to polystyrene nanoplastics - Xiaoli Guo; Cheng Cheng; Lin chen; Changsong Cao; Dongbei Li; Ruihua Fan; Xudong Wei (Food and Chemical Toxicology, 2023)

A fractional-order two-surface plasticity model for over-consolidated clays and its application to deep gallery excavation - Wei Cheng; Ren-Peng Chen; Zhen-Yu Yin; Han-Lin Wang; Fan-Yan Meng (Computers and Geotechnics, 2023)

Antimicrobial cellulose paper tuned with chitosan fibers for high-flux oil/water separation - Hao Ling; Lei Wang; Qixuan Lin; Quanbo Huang; Xiaoqian Zhang; Junli Ren; Ning Li; Cheng Zhou; Zhiwei Lin; Jingpeng Zhou; Wenguang Wei; Xiaohui Wang (Carbohydrate Polymers, 2023)

Alternative splicing affects synapses in the hippocampus of offspring after maternal fructose exposure during gestation and lactation - Yuchen Zou; Qing Guo; Yidan Chang; Yongyong Zhong; Lin Cheng; Wei Wei (Chemico-Biological Interactions, 2023)

Ethanol production using the whole solid-state fermented sugarcane bagasse cultivated by Trichoderma reesei RUT-C30 supplemented with commercial cellulase - Ching An Lin; Cheng Cheng; Li Wei Chen; C. Will Chen; Kow Jen Duan (Biocatalysis and Agricultural Biotechnology, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Phosphorus amendment alters soil arbuscular mycorrhizal fungal functional guild compositions in a subtropical forest - Quan-Cheng Wang; Sheng-Sheng Jin; Shanshan Liu; Ge Song; Chunjian Duan; Peng-Peng Lü; Pulak Maitra; Lin Xie; Yongxin Lin; Hang-Wei Hu; Ji-Zheng He; Yong Zheng (Journal of Soils and Sediments, 2023)

Influence of microclimate control on the growth of asparagus under greenhouse in tropical climates - Kuo-An Hung; Yi-Wei Hsu; Yu-Cheng Chen; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

Exosomal MiR-381 from M2-polarized macrophages attenuates urethral fibroblasts activation through YAP/GLS1-regulated glutaminolysis - Ye-Hui Chen; Yi-Cheng Xu; Ting-Ting Lin; Hang Chen; Ru-Nan Dong; Feng-Ping Cai; Zhi-Bin Ke; Jia-Yin Chen; Yong Wei; Qing-Shui Zheng; Xue-Yi Xue; Ning Xu (Inflammation Research, 2023)

Hyperspectral imaging technique supports dynamic emission inventory of coal-fired power plants in China - Jinan Lin; Chengzhi Xing; Cheng Liu; Wei Tan; Wei Wang; Peng Wu; Chuan Lu; Qihua Li; Ting Liu (Science Bulletin, 2023)

The role of climate literacy in individual response to climate change: evidence from China - Wu-Lin Pan; Ruguo Fan; Wei Pan; Xinyu Ma; Cheng Hu; Piao Fu; Jingyi Su (Journal of Cleaner Production, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Epitomizing biohydrogen production from microbes: Critical challenges vs opportunities - Jia Min Woon; Kuan Shiong Khoo; Asla A. AL-Zahrani; Meznah M. Alanazi; Jun Wei Lim; Chin Kui Cheng; Nurul Tasnim Sahrin; Fatima Musa Ardo; Sun Yi-Ming; Kuen-Song Lin; John Chi-Wei Lan; Md Sohrab Hossain; et al. (Environmental Research, 2023)

Screening of Artificial Diet Formulations for Sugarcane Stalk Borer Chilo sacchariphagus Bojer - Ji-li Wei; Xue-hong Pan; Xian-kun Shang; Cheng-hua Huang; Yong-lin Ma (Sugar Tech, 2023)

Herbicidal Activity Evaluation of Topramezone and Its Safety to Sugarcane - Yong-lin Ma; Cheng-lin Guo; Yan-hui Wang; Yuan-yuan Gao; Jian-lin Qin; Ji-li Wei (Sugar Tech, 2023)

Carbon quantum dot fluorescent probe for labeling and imaging of stellate cell on liver frozen section below freezing point - Yan-Fei He; Kai Cheng; Zi-Tao Zhong; Xiao-Lin Hou; Chang-Zhi An; Jing Zhang; Wei Chen; Bo Liu; Jing Yuan; Yuan-Di Zhao (Analytica Chimica Acta, 2023)

Improving Aquaculture Water Quality Using Dual-Input Fuzzy Logic Control for Ammonia Nitrogen Management - Hung-Chih Li; Ker-Wei Yu; Chang-Hua Lien; Chitsan Lin; Cheng-Ruei Yu; Sundarapandian Vaidyanathan (Journal of Marine Science and Engineering, 2023)
In this paper, a closed-loop control system using dual-input fuzzy logic theory is proposed to improve the water quality of aquaculture. The new closed-loop control system is implemented on a Raspberry-Pi-embedded platform using Python programming. The proposed closed-loop control system integrates an RS485 function, a database transfer module, a simulating variable group function, and a trigger function import to achieve savings in human resources, power, and water consumption. The proposed closed-loop control system is equipped with an ammonia nitrogen sensor and solenoid valves for the water exchange. The experimental results demonstrate that the intelligent controller can rapidly eliminate ammonia nitrogen within the range of 2.0 ppm and maintain robust control in response to changes in ammonia nitrogen excretion from a school of fish. The experimental results provide insights into the relationship between tank capacity, water exchange solenoid valves, and ammonia nitrogen degradation time, which can be used to optimize aquaculture density and improve industrialization. The experimental results demonstrate that the savings for power and water can be achieved above 95%.

The Paleoenvironment and Mechanisms of Organic Matter Enrichment of Shale in the Permian Taiyuan and Shanxi Formations in the Southern North China Basin - Yanan Wang; Xiulei Cheng; Kai Fan; Zhipeng Huo; Lin Wei (Journal of Marine Science and Engineering, 2023)
The organic-rich shale of the Permian Taiyuan Formation (TYF) and Shanxi Formation (SXF) in the Southern North China Basin (SNCB) is considered a potential shale gas source. The shale was formed in a marine-continental transitional sedimentary environment, which has rarely been studied, with the enrichment mechanisms of organic matter (OM) remaining unclear. This study investigated the controlling factors and enrichment mechanisms of OM by analyzing the total organic carbon (TOC) content, paleoclimate, paleoproductivity, sedimentation rate, redox, and paleosalinity. The TOC of the TYF ranged from 0.92 to 7.43 wt.%, with an average of 2.48 wt.%, which was higher than that of the SXF (TOC = 0.36–5.1 wt.%, average of 1.68 wt.%). These geochemical indices suggest that both the TYF and SXF were deposited in warm and humid paleoclimates, with relatively high biological productivity and sedimentation rates. During the deposition process, the TYF experienced frequent transgression and regression events, leading to an enhancement of water reducibility, a relatively high sedimentation rate, reduced OM oxidation, and rapid deposition of OM, which were conducive to the preservation of OM. Moreover, a high biological productivity increased respiratory oxygen consumption in the water column, which could lead to OM accumulation. However, the regression event experienced by the SXF reduced the paleoproductivity and sedimentation rate and increased water oxidation, leading to a decrease in OM. The main controlling factors for the enrichment of OM in the TYF and SXF were the sedimentation rate, paleoproductivity, and redox conditions, thus establishing the enrichment models for OM in the TYF and SXF. This study is conducive to understanding shale enrichment mechanisms and guiding shale gas exploration.

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Selective accumulation of ionic nanocrystal H2 storage system as an in situ H2/boric acid nanogenerator fights against ethanol-induced gastric ulcers - Chih-Wei Chou; Wei-Tso Chia; Cam-Hoa Mac; Cheng-Yu Wu; Chun-Chieh Chen; Hsiang-Lin Song; Yi-Hsuan Lin; Yu-Jung Lin; Hsing-Wen Sung (Chemical Engineering Journal, 2023)

Quercetin alleviates tubulointerstitial inflammation by inhibiting exosomes-mediated crosstalk between tubular epithelial cells and macrophages - Di Yin; Jing-Yuan Cao; Yan Yang; Zhong-Tang Li; Hong Liu; Tao-Tao Tang; Wei-Jie Ni; Yi-Lin Zhang; Wei Jiang; Yi Wen; Zuo-Lin Li; Jing Zhao; et al. (Inflammation Research, 2023)

Aestuariibaculum lutulentum sp. nov., a marine bacterium isolated from coastal sediment in Beihai - Jia-Wei Gao; Dong-Yan He; Wen-Wu Zhang; Yu-Ruo Wang; Yue Su; Jun-Jie Ying; Zhi-Cheng Wu; Wu Qu; Lin Xu; Cong Sun (Archives of Microbiology, 2023)

Classification of ice and water in the Arctic using radar altimeter and microwave radiometer data from HY-2B satellite - Chengfei Jiang; Mingsen Lin; Ruixue Cao; Hao Wei; Lijian Shi; Bin Cheng; Yongjun Jia; Qimao Wang (Acta Oceanologica Sinica, 2023)

Genomic architecture underlying morphological and physiological adaptation to high elevation in a songbird - Chia‐Wei Lu; Shih‐Ting Huang; Shun‐Jen Cheng; Chen‐Tau Lin; Yu‐Cheng Hsu; Cheng‐Te Yao; Feng Dong; Chih‐Ming Hung; Hao‐Chih Kuo (Molecular Ecology, 2023)
Organisms often acquire physiological and morphological modifications to conquer ecological challenges when colonizing new environments which lead to their adaptive evolution. However, deciphering the genomic mechanism of ecological adaptation is difficult because ecological environments are often too complex for straightforward interpretation. Thus, we examined the adaptation of a widespread songbird—the rufous‐capped babbler ( Cyanoderma ruficeps )—to a relatively simple system: distinct environments across elevational gradients on the mountainous island of Taiwan. We focused on the genomic sequences of 43 birds from five populations to show that the Taiwan group split from its sister group in mainland China around 1–2 million years ago (Ma) and colonized the montane habitats of Taiwan at least twice around 0.03–0.22 Ma. The montane and lowland Taiwan populations diverged with gene flow between them, suggesting strong selection associated with different elevations. We found that the montane babblers had smaller beaks than the lowland ones, consistent with Allen's rule, and identified candidate genes— COL9A1 and SOX11 —underlying the beak size changes. We also found that altitudinally divergent mutations were mostly located in noncoding regions and tended to accumulate in chromosomal inversions and autosomes. The altitudinally divergent mutations might regulate genes related to haematopoietic, metabolic, immune, auditory and vision functions, as well as cerebrum morphology and plumage development. The results reveal the genomic bases of morphological and physiological adaptation in this species to the low temperature, hypoxia and high UV light environment at high elevation. These findings improve our understanding of how ecological adaptation drives population divergence from the perspective of genomic architecture.

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

Involvement of microRNA164 in responses to heat stress in Arabidopsis - Wei-An Tsai; Po-Han Sung; Yun-Wei Kuo; Ming-Cheng Chen; Shih-Tong Jeng; Jeng-Shane Lin (Plant Science, 2023)

BnIR: A multi-omics database with various tools for Brassica napus research and breeding - Zhiquan Yang; Shengbo Wang; Lulu Wei; Yiming Huang; Dongxu Liu; Yupeng Jia; Chengfang Luo; Yuchen Lin; Congyuan Liang; Yue Hu; Cheng Dai; Liang Guo; et al. (Molecular Plant, 2023)

Novel Al-doped UiO-66-NH2 nanoadsorbent with excellent adsorption performance for tetracycline: Adsorption behavior, mechanism, and application potential - Liangqian Fan; Jiaxin Miao; Xianda Wang; Jie Cai; Jiawei Lin; Fenghui Chen; Wei Chen; Hongbing Luo; Lin Cheng; Xiaochan An; Xiaoxiao Zhang; Ke Zhang; et al. (Journal of Environmental Chemical Engineering, 2023)

An exploration on CO faradaic efficiency with catalyst surface wettability ranging from hydrophilic to superhydrophobic - Jing Lin; Shenglin Yan; Qing Hu; Zhihang Wei; Zhenmin Cheng (Chemical Engineering Journal, 2023)

α7 nicotinic acetylcholine receptor agonist improved brain injury and impaired glucose metabolism in a rat model of ischemic stroke - Ya-Yu Wang; Shih-Yi Lin; Cheng-Yi Chang; Chih-Cheng Wu; Wen-Ying Chen; Wei-Chi Huang; Su-Lan Liao; Wen-Yi Wang; Chun-Jung Chen (Metabolic Brain Disease, 2023)

Whole-genome sequencing reveals putative underlying mechanisms of biocontrol capability of IBFCBF-5 - Chen Luo; Ai-rong Shen; Ye-song Ren; Yang Zhai; Yi Cheng; Jianping Xu; Lin Wei; Ji-lie Li; Liang-bin Zeng (Acta Physiologiae Plantarum, 2023)

Centenarian clocks: epigenetic clocks for validating claims of exceptional longevity - Eric Dec; James Clement; Kaiyang Cheng; George M. Church; Michael B. Fossel; David H. Rehkopf; Luis Rosero-Bixby; Michael S. Kobor; David TS. Lin; Ake T. Lu; Zhe Fei; Wei Guo; et al. (GeroScience, 2023)
Claims surrounding exceptional longevity are sometimes disputed or dismissed for lack of credible evidence. Here, we present three DNA methylation-based age estimators (epigenetic clocks) for verifying age claims of centenarians. The three centenarian clocks were developed based on n = 7039 blood and saliva samples from individuals older than 40, including n = 184 samples from centenarians, 122 samples from semi-supercentenarians (aged 105 +), and 25 samples from supercentenarians (aged 110 +). The oldest individual was 115 years old. Our most accurate centenarian clock resulted from applying a neural network model to a training set composed of individuals older than 40. An epigenome-wide association study of age in different age groups revealed that age effects in young individuals (age < 40) are correlated ( r = 0.55) with age effects in old individuals (age > 90). We present a chromatin state analysis of age effects in centenarians. The centenarian clocks are expected to be useful for validating claims surrounding exceptional old age.

Pharmacokinetics and residue elimination of metalaxyl enantiomers in snakehead (Channa argus) - Hao Zhou; Meiyu Zhang; Qi Shan; Heqing Huang; Meiling Zhang; Shugui Liu; Jiawei Lin; Lisha Ma; Guangming Zheng; Lichun Li; Cheng Zhao; Xiaoxin Dai; et al. (Aquaculture, 2023)

Cobalt nanoparticles induce mitochondrial damage and β-amyloid toxicity via the generation of reactive oxygen species - Jingrong Chen; Cheng Chen; Na Wang; Chunyu Wang; Zhaohui Gong; Jingxian Du; Honglin Lai; Xinpei Lin; Wei Wang; Xiangyu Chang; Michael Aschner; Zhenkun Guo; et al. (NeuroToxicology, 2023)

Flow measurement in open channels using imaging techniques in conjunction with a convolutional neural network - Hao-Che Ho; Yu-Wei Chiu; Ting-Yu Chen; Yen-Cheng Lin (Journal of Hydrology, 2023)

Comparison of tropomyosin released peptide and epitope mapping after in vitro digestion from fish (Larimichthys crocea), shrimp (Litopenaeus vannamei) and clam (Ruditapes philippinarum) through SWATH-MS based proteomics - LiLi Xu; Xiao Mei Zhang; Yun Qi Wen; Jin Long Zhao; Tong Cheng Xu; Ling Yong; Hong Lin; Hong Wei Zhang; Zhen Xing Li (Food Chemistry, 2023)

Fouling characteristic of reverse osmosis membrane for reclaimed water treatment operating under cold winter condition - Zi-Hao Li; Guo-Wei Ni; Jin-Long Wang; Lin Zhou; Qiang Yang; Pei-Zhuo Li; Ai-Li Gao; Tong Yu; Li-Hua Cheng; Xue-Jun Bi (Desalination, 2023)

Effect of landing disturbance caused by capping materials on the control efficiency of contaminated sediment capping - Bin Wang; Wei Zhu; Yong Wu; Hao Hou; Lin Cheng; Xiaoge Xu; Yuehong Li; Xiaowei Lin; Chengxin Fan (Journal of Soils and Sediments, 2023)

Stem cell-derived exosomes for chronic wound repair - Peng Mi; Jia-Lin Liu; Bao-Ping Qi; Ben-Mei Wei; Cheng-Zhi Xu; Lian Zhu (Cell and Tissue Research, 2023)

Rapid shifts in thermal reaction norms and tolerance of brooded coral larvae following parental heat acclimation - Lei Jiang; Cheng‐Yue Liu; Guoxin Cui; Lin‐Tao Huang; Xiao‐Lei Yu; You‐Fang Sun; Hao‐Ya Tong; Guo‐Wei Zhou; Xiang‐Cheng Yuan; Yi‐Si Hu; Wen‐Liang Zhou; Manuel Aranda; et al. (Molecular Ecology, 2023)
Thermal priming of reef corals can enhance their heat tolerance; however, the legacy effects of heat stress during parental brooding on larval resilience remain understudied. This study investigated whether preconditioning adult coral Pocillopora damicornis to high temperatures (29°C and 32°C) could better prepare their larvae for heat stress. Results showed that heat‐acclimated adults brooded larvae with reduced symbiont density and shifted thermal performance curves. Reciprocal transplant experiments demonstrated higher bleaching resistance and better photosynthetic and autotrophic performance in heat‐exposed larvae from acclimated adults compared to unacclimated adults. RNA‐seq revealed strong cellular stress responses in larvae from heat‐acclimated adults that could have been effective in rescuing host cells from stress, as evidenced by the widespread upregulation of genes involved in cell cycle and mitosis. For symbionts, a molecular coordination between light harvesting, photoprotection and carbon fixation was detected in larvae from heat‐acclimated adults, which may help optimize photosynthetic activity and yield under high temperature. Furthermore, heat acclimation led to opposing regulations of symbiont catabolic and anabolic pathways and favoured nutrient translocation to the host and thus a functional symbiosis. Notwithstanding, the improved heat tolerance was paralleled by reduced light‐enhanced dark respiration, indicating metabolic depression for energy saving. Our findings suggest that adult heat acclimation can rapidly shift thermal tolerance of brooded coral larvae and provide integrated physiological and molecular evidence for this adaptive plasticity, which could increase climate resilience. However, the metabolic depression may be maladaptive for long‐term organismal performance, highlighting the importance of curbing carbon emissions to better protect corals.

3D printing titanium dioxide-acrylonitrile-butadiene-styrene (TiO2-ABS) composite membrane for efficient oil/water separation - Lei Han; Liguo Shen; Hongjun Lin; Zhengyi Huang; Yanchao Xu; Renjie Li; Bisheng Li; Cheng Chen; Wei Yu; Jiaheng Teng (Chemosphere, 2023)

The extract from aerial part of Scutellaria baicalensis regulates gut microbiota in rabbit fish: Replacement of antibiotic fighting against pathogenic bacteria - Yi-Teng Xia; Edwin Hok-Chi Cheng; Huai-You Wang; Lynn Hoi-Lam Zhang; Sheng-Ying Lin; Tina Ting-Xia Dong; Ran Duan; Qi-Wei Qin; Wen-Xiong Wang; Karl Wah-Keung Tsim (Aquaculture, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Modeling of an integrated H2S/NH3 scrubber and regeneration columns for coke oven gas purification - Hao-Jen Pan; Ming-Chun Fang; Jeffrey D. Ward; Hao-Yeh Lee; Hsun-Yu Lin; Cheng-Ting Hsieh; Chih-Lung Lee; Tzu-Hsien Huang; Yu-Chen Hsieh; Shih-Chieh Lin; Wei-Ti Chou (Journal of Cleaner Production, 2023)

Using transcriptomics to reveal the molecular mechanism of higher alcohol metabolism in Saccharomyces cerevisiae - Danyao Cui; Ling Liu; Xiaoyuan Zhang; Liangcai Lin; Xin Li; Ting Cheng; Chunhui Wei; Yu Zhang; Zheng Zhou; Wei Li; Cuiying Zhang (Food Bioscience, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

Programmable CRISPR-Cas12a and self-recruiting crRNA assisted dual biosensing platform for simultaneous detection of lung cancer biomarkers hOGG1 and FEN1 - Xia Cheng; Xinyi Xia; Dandan Ren; Qiutong Chen; Guanhong Xu; Fangdi Wei; Jing Yang; Lin Wang; Qin Hu; Jianjun Zou; Yao Cen (Analytica Chimica Acta, 2023)

Reclamation and reuse of wastewater by membrane-based processes in a typical midstream petrochemical factory: a techno-economic analysis - Cheng-Wei Lin; Hai Nguyen Tran; Ruey-Shin Juang (Environment, Development and Sustainability, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

PGC-1α/NRF1-dependent cardiac mitochondrial biogenesis: A druggable pathway of calycosin against triptolide cardiotoxicity - Xiao-Ming Qi; Yuan-Biao Qiao; Yuan-Lin Zhang; Ai-Cheng Wang; Jin-Hong Ren; Hui-Zhi Wei; Qing-Shan Li (Food and Chemical Toxicology, 2023)

Identification of ISG15 in golden pompano, Trachinotus ovatus, and its role in virus and bacteria infections - Lin Huang; Yuan Cheng; Shuyu Han; Mingzhu Liu; Qing Yu; Hongling Wei; Jinzhao He; Pengfei Li (Fish & Shellfish Immunology, 2023)

Impact of the COVID-19 on electricity consumption of open university campus buildings – The case of Twente University in the Netherlands - Sheng Xu; Bin Cheng; Zefeng Huang; Tao Liu; Yuan Li; Lin Jiang; Wei Guo; Jie Xiong (Energy and Buildings, 2023)

Intimate interaction of TFSI− anions with MoO3−x oxygen vacancies boost ionic conductivity of cathode-supported solid polymer electrolyte - Rohan Paste; Chintam Hanmandlu; Po-Yu Su; Cheng-Hung Hou; Hsin-An Chen; Chun-Wei Pao; Jing-Jong Shyue; Kuei-Hsien Chen; Heng-Liang Wu; Hong-Cheu Lin; Chih Wei Chu (Chemical Engineering Journal, 2023)

A microscale regulation strategy for strong, tough, and efficiently self-healing energetic adhesives - Jing Yang; Xin Zhou; Junqing Yang; Jiaoyang Chen; Zhe Sun; Yuhang Cheng; Lin Yang; Hui Wang; Guangpu Zhang; Jiajun Fu; Wei Jiang (Chemical Engineering Journal, 2023)

Electron transfer-based peroxydisulfate activation by waste herb residue biochar: Adsorption versus surface oxidation - Xuantong Chen; Zhen Guo; Juemiao Liu; Fei Wu; Cheng Cheng; Heng Lin; Wei Ren; Hui Zhang (Chemical Engineering Journal, 2023)

Equilibrative Nucleoside Transporter 1 is a Target to Modulate Neuroinflammation and Improve Functional Recovery in Mice with Spinal Cord Injury - Kuan-Yu Chen; Chiao-Shin Lu; Cheng-Yoong Pang; Chin-Jui Ho; Kuo-Chen Wu; Hsiu-Wei Yang; Hsin-Lin Lai; Yijuang Chern; Chun-Jung Lin (Molecular Neurobiology, 2023)

Distribution and changes in microplastics in Taihu Lake and cyanobacterial blooms formed by the aggregation of Microcystis colonies - Bin Wang; Wei Zhu; Silin Wu; Hao Hou; Lin Cheng; Xiaoge Xu; Yuehong Li; Xiaowei Lin; Zongpu Xue (Environmental Science and Pollution Research, 2022)

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

Circular RNA expression profile of systemic lupus erythematosus and its clinical significance as a potential novel biomarker - Wenyu Li; Runge Fan; Cheng Zhou; Yue Wei; Shunsheng Lin; Sijian Wen; Wen Zeng; Wei Hou; Cheng Zhao; Youkun Lin (Genes & Genomics, 2022)
Background Circular RNAs (circRNAs) are a class of endogenous noncoding RNAs that are more abundant, specific, and highly organized than linear RNAs. Increasing evidence supports that circRNAs may serve as diagnostic biomarkers in many diseases, but their potential as biomarkers in systemic lupus erythematosus (SLE) remains unclear. Objective We investigated the critical circRNAs involved in SLE progression and explored their potential application as biomarkers in SLE. Method RNA sequencing was conducted on peripheral blood mononuclear cells (PBMCs) from 4 SLE patients and 4 healthy volunteers. CircRNA profile data were analyzed to identify differentially expressed circRNAs and visualized via R software. After screening, qPCR analysis of target circRNA expression was performed using PBMCs from 31 SLE patients and 35 healthy volunteers. Correlations between circRNA expression levels and the SLEDAI score were assessed via Spearman correlation analysis. Finally, the performance of circRNAs as biomarkers in SLE was examined by receiver operating characteristic curve analysis. Results The result identified six differentially expressed circRNAs between SLE patients and healthy controls: hsa_circ_0006689, hsa_circ_0070562, hsa_circ_0006117, hsa_circ_0007683, hsa_circ_0042519, and hsa_circ_0008647. The validation analysis showed differing relative expression levels of hsa_circ_0007683, hsa_circ_0042519, hsa_circ_0008647, and hsa_circ_0006689 between SLE patients and healthy volunteers (P < 0.05), and hsa_circ_0006689 expression in PBMCs correlated with the SLEDAI score (P < 0.05). Furthermore, addition of hsa_circ_0006689 expression increased the sensitivities of anti-dsDNA antibody and anti-Sm antibody levels for SLE diagnosis (from 29.03 to 61.30% and 32.26–71.00%, respectively). Conclusion Our results suggest hsa_circ_0006689 may be a useful circRNA biomarker for SLE diagnosis and prognosis.

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Gregarious larval settlement mediates the responses of new recruits of the reef coral Acropora austera to ocean warming and acidification - Lei Jiang; Yu-Yang Zhang; Cheng-Yue Liu; Lin-Tao Huang; Hao-Ya Tong; Guo-Wei Zhou; Ming-Lan Guo; Tao Yuan; Hui Huang (Frontiers in Marine Science, 2022)
Gregarious larval settlement represents an important window for chimera formation in reef corals, yet it remains largely unknown how aggregated settlement and early chimerism could modify the performance and responses of coral recruits under elevated temperature and p CO 2 . In this study, single and aggregated recruits of the broadcast spawning coral Acropora austera were exposed to contrasts of two temperatures (28 versus 30.5°C) and p CO 2 levels (~500 versus 1000 μatm) for two weeks, and algal symbiont infection success, survivorship and growth were assessed. Results showed that symbiont infection success was mainly affected by temperature and recruit type, with reduced symbiont infection at increased temperature and consistently higher infection success in chimeric recruits compared to single recruits. Furthermore, although chimeric recruits with larger areal size had significantly higher survivorship in all treatments, the polyp-specific growth rates were considerably lower in chimeric entities than individual recruits. More importantly, the recruit type significantly influenced the responses of recruit polyp-specific growth rates to elevated temperature, with chimeras exhibiting lowered skeletal lateral growth under elevated temperature. These results demonstrate the benefits and costs associated with gregarious larval settlement for juvenile corals under ocean warming and acidification, and highlight the ecological role of larval settlement behavior in mediating the responses of coral recruits to climate change stressors.

Environmental indicators combined with risk analysis to evaluate potential wildfire incidence on the Dadu Plateau in Taiwan - Chao-Yuan Lin; Pei-Ying Shieh; Shao-Wei Wu; Po-Cheng Wang; Yung-Chau Chen (Natural Hazards, 2022)
Wildfire is a common disaster in the world, and it has a considerable impact on the safety of residents and ecological disturbance. Periodic wildfires are an urgent problem to be solved. This research uses big data from relevant departments to extract environmental indicators that affect wildfires, including satellite images, meteorological observations, and field surveys and establishes a risk model for the Spatio-temporal distribution of wildfires based on risk analysis. Previous studies using Differenced Normalized Burn Ratio (dNBR) to assess fire severity and distinguish wildfire ruins did not deal with the impact of atmospheric humidity on dNBR values. In this study, an adjustable fire threshold was developed to enable dNBR to improve the accuracy of identifying wildfire locations. Regarding the temporal distribution of wildfire risks, environmental vulnerability cannot specifically reflect the frequency of actual wildfires. If the hazard degree is introduced to calculate the wildfire risk, the coefficient of determination can be increased from 0.49 to 0.79. The verification of the village boundary zone depicts that the risk analysis can effectively show the temporal and spatial distribution of wildfire hotspots. On this basis, a village-level wildfire disaster prevention strategy can be formulated.

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Recognition of behavior state of Penaeus vannamei based on passive acoustic technology - Maochun Wei; Keyu Chen; Yating Lin; En Cheng (Frontiers in Marine Science, 2022)
Underwater signal processing based on passive acoustic technology has carried out a lot of research on the behavioral sound of underwater creatures and the protection of marine resources, which proves the feasibility of passive acoustic technology for long-term and non-destructive monitoring of underwater biological sound production. However, at present, most relevant research focuses on fish but little research on shrimp. At the same time, as the main economic breeding industry, Penaeus vannamei has a backward industrial structure, in which the level of intelligence needs to be improved. In this paper, the acoustic signals generated by different physiological behaviors of P. vannamei are collected based on passive acoustic technology. Their different behaviors are finally classified and identified through feature extraction and analysis. Meanwhile, the characteristic non-parametric ANOVA is carried out to explore the relationship between the acoustic signals and the behavior state of P. vannamei to achieve the purpose of real-time monitoring of the behavior state of P. vannamei . The experimental results show that linear prediction cepstrum coefficient (LPCC) and Mel-frequency cepstrum coefficient (MFCC) characteristic coefficients are effective in the classification and recognition of different behavioral acoustic signals with interspecific acoustic signals of P. vannamei . Meanwhile, the SVM classifier based on OvR classification strategy can model the acoustic signal characteristics of different underwater biological behaviors more efficiently and has classification accuracy as high as 93%.

Isolation and identification of two new sargentodoxosides from Sargentodoxa cuneata and their agonistic effects against FXR - Wen Zhang; Cheng-Peng Sun; Yu-Lin Peng; Wen-Yu Zhao; Zheng-Yue Wang; Jing Ning; Xia Lv; Zhen-Long Yu; Shuang Zhou; Wei Peng; Bang-Jiang Fang; Xiao-Chi Ma (Natural Product Research, 2022)

Correction to: Receptor-Interacting Protein 140 Enhanced Temozolomide-Induced Cellular Apoptosis Through Regulation of E2F1 in Human Glioma Cell Lines - Hong-Chieh Tsai; Kuo-Chen Wei; Pin-Yuan Chen; Chiung-Yin Huang; Ko-Ting Chen; Ya-Jui Lin; Hsiao-Wei Cheng; Chun-Hao Huang; Hsiang-Tsui Wang (NeuroMolecular Medicine, 2022)

Receptor-Interacting Protein 140 Enhanced Temozolomide-Induced Cellular Apoptosis Through Regulation of E2F1 in Human Glioma Cell Lines - Hong-Chieh Tsai; Kuo-Chen Wei; Pin-Yuan Chen; Chiung-Yin Huang; Ko-Ting Chen; Ya-Jui Lin; Hsiao-Wei Cheng; Chun-Hao Huang; Hsiang-Tsui Wang (NeuroMolecular Medicine, 2022)

Using DeepLab v3 + -based semantic segmentation to evaluate platelet activation - Tsung-Chen Kuo; Ting-Wei Cheng; Ching-Kai Lin; Ming-Che Chang; Kuang-Yao Cheng; Yun-Chien Cheng (Medical & Biological Engineering & Computing, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

Spatiotemporal characteristics and influencing factors of urban resilience efficiency in the Yangtze River Economic Belt, China - Yingzi Lin; Chong Peng; Jianfeng Shu; Wei Zhai; Jianquan Cheng (Environmental Science and Pollution Research, 2022)

Estrogen Deficiency Aggravates Fluoride-Induced Liver Damage and Lipid Metabolism Disorder in Rats - Ya-ming Yu; Bian-hua Zhou; Yi-lin Yang; Cheng-Xiang Guo; Jing Zhao; Hong-wei Wang (Biological Trace Element Research, 2022)

Myd88 knockdown with RNA interference induces in vitro immune hyporesponsiveness in dendritic cells from rhesus monkeys - Qiuhong Wang; Dongyun Cun; Desong Xu; Liang Lin; Jian Jiao; Li Zhang; Cheng Xi; Wei Li; Peng Chen; Mingdao Hu (Immunogenetics, 2022)

Berberisides A-D: three novel prenylated benzoic acid derivatives and a clerodane glycoside from Berberis tsarica aherndt. - Zhao-Yue Dong; Qing-Hong Zeng; Lin Wei; Xin Guo; Yan Sun; Fan-Cheng Meng; Guo-Wei Wang; Xiao-Zhong Lan; Zhi-Hua Liao; Min Chen (Natural Product Research, 2022)

Biomechanical superiority of locking plate designed with cluster of head screws compared to conventional buttress plate for fixation of posteromedial tibial plateau fractures: A computational assessment - Kai-Cheng Lin; Yih-Wen Tarng; Kun-Jhih Lin; Hung-Wen Wei (Journal of Medical and Biological Engineering, 2022)

Alternaria species causing leaf spot on hemp (Cannabis sativa) in Northern China - Hong Cheng; Lin Zhao; Xin Wei; Xi Liu; Guo-Yang Gao; Jian-Xin Deng; Mei-Jia Li (European Journal of Plant Pathology, 2022)

Assessment of potential sediment disasters and resilience management of mountain roads using environmental indicators - Chao-Yuan Lin; Yuan-Chung Lai; Shao-Wei Wu; Fan-Chung Mo; Cheng-Yu Lin (Natural Hazards, 2022)
In recent years, extreme rainfall events occur frequently, causing serious watershed sediment disasters, destroying mountain roads, and endangering the safety of residents' lives and property. This study aims to deal with the spatial change of potential sediment movement on the road slope pre-disaster and to screen disaster hot spots for early warning and control system. The conceptual model is used to simulate the distribution of primary and/or derived disasters on a watershed scale to assess the impact of sediment disasters caused by heavy rain event. Correlation analysis shows that the models in assessment of primary disaster and derived disaster are significantly correlated with the collapse ratio and disaster ratio, respectively. Since the primary disaster has been considered when calculating the derived disaster risk, the terrain subdivision along Provincial Highway 21 (Tai-21) is extracted to understand the derived sediment disaster on the road slope. The model can effectively evaluate the road sections prone to disasters. According to the risk level, the hot spot of road slope disasters and the management of disaster resilience are determined and can be the reference for disaster prevention and control.

Towards a rapid assessment of highway slope disasters by using multidisciplinary techniques - Meng-Chia Weng; Cheng-Han Lin; Wen-Jie Shiu; Wei-An Chao; Chia-Chi Chiu; Ching-Fang Lee; Wei-Kai Huang; Che-Ming Yang (Landslides, 2022)
Mega-earthquakes and extreme climate events accompanied by intrinsic fragile geology lead to numerous landslides along mountain highways in Taiwan, causing enormous life and economic losses. In this study, a system for rapid slope disaster information integration and assessment is proposed with the aim of providing information on landslide occurrence, failure mechanisms, and subsequent landslide-affected areas to the highway authority rapidly. The functionality of the proposed system is deployed into three units: (1) geohazard rapid report (GeoPORT I), (2) multidisciplinary geological survey report (GeoPORT II), and (3) site-specific landslide simulation report (GeoPORT III). After landslide occurrence, the seismology-based monitoring network rapidly provides the initial slope disaster information, including preliminary location, event magnitude, earthquake activity, and source dynamics, within an hour. Within 3 days of the landslide, a multidisciplinary geological survey is conducted to collect high-precision topographical, geological, and remote-sensing data to determine the possible failure mechanism. After integrating the aforementioned information, a full-scale three-dimensional landslide simulation based on the discrete element method is performed within 10 days to reveal the failure process and to identify the areas potentially affected by subsequent disasters through scenario modeling. Overall, the proposed system can promptly provide comprehensive and objective information to relevant authorities after the event occurrence for hazard assessment. The proposed system was validated using a landslide event in the Central Cross-Island Highway of Taiwan.

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Downregulated Calcium-Binding Protein S100A16 and HSP27 in Placenta-Derived Multipotent Cells Induce Functional Astrocyte Differentiation - Yu-Che Cheng; Chi-Jung Huang; Wei-Chi Ku; Shu-Lin Guo; Lu-Tai Tien; Yih-Jing Lee; Chih-Cheng Chien (Stem Cell Reviews and Reports, 2022)
Little is known about genes that induce stem cells differentiation into astrocytes. We previously described that heat shock protein 27 (HSP27) downregulation is directly related to neural differentiation under chemical induction in placenta-derived multipotent stem cells (PDMCs). Using this neural differentiation cell model, we cross-compared transcriptomic and proteomic data and selected 26 candidate genes with the same expression trends in both omics analyses. Those genes were further compared with a transcriptomic database derived from Alzheimer’s disease (AD). Eighteen out of 26 candidates showed opposite expression trends between our data and the AD database. The mRNA and protein expression levels of those candidates showed downregulation of HSP27, S100 calcium-binding protein A16 (S100A16) and two other genes in our neural differentiation cell model. Silencing these four genes with various combinations showed that co-silencing HSP27 and S100A16 has stronger effects than other combinations for astrocyte differentiation. The induced astrocyte showed typical astrocytic star-shape and developed with ramified, stringy and filamentous processes as well as differentiated endfoot structures. Also, some of them connected with each other and formed continuous network. Immunofluorescence quantification of various neural markers indicated that HSP27 and S100A16 downregulation mainly drive PDMCs differentiation into astrocytes. Immunofluorescence and confocal microscopic images showed the classical star-like shape morphology and co-expression of crucial astrocyte markers in induced astrocytes, while electrophysiology and Ca 2+ influx examination further confirmed their functional characteristics. In conclusion, co-silencing of S100A16 and HSP27 without chemical induction leads to PDMCs differentiation into functional astrocytes. Graphical abstract

Chemical constituents from the fruits of Piper longum L. and their vascular relaxation effect on rat mesenteric arteries - Dan Li; Rui Wang; Xiaohan Cheng; Jianfeng Yang; Yihui Yang; Huichong Qu; Sen Li; Shan Lin; Donghua Wei; Yuhua Bai; Xiaodong Zheng (Natural Product Research, 2022)

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Biomimetic synthesis of 6-substituted dihydrobenzophenanthridine alkaloids based on visible-light promoted radical addition reaction - Pi Cheng; Wei Wang; Xinhao Wang; Lin Wang; Wei Liu; Jianguo Zeng (Natural Product Research, 2022)

Electrical Impedance Tomography Analysis Between Two Similar Respiratory System Compliance During Decremetal PEEP Titration in ARDS Patients - Po-Lan Su; Wei-Chieh Lin; Yen-Fen Ko; Kuo-Sung Cheng; Chang-Wen Chen (Journal of Medical and Biological Engineering, 2021)
Purpose The positive end-expiratory pressure (PEEP) level with best respiratory system compliance (Crs) is frequently used for PEEP selection in acute respiratory distress syndrome (ARDS) patients. On occasion, two similar best Crs (where the difference between the Crs of two PEEP levels is < 1 ml/cm H 2 O) may be identified during decremental PEEP titration. Selecting PEEP under such conditions is challenging. The aim of this study was to provide supplementary rationale for PEEP selection by assessing the global and regional ventilation distributions between two PEEP levels in this situation. Methods Eight ARDS cases with similar best Crs at two different PEEP levels were analyzed using examination-specific electrical impedance tomography (EIT) measures and airway stress index (SIaw). Five Crs were measured at PEEP values of 25 cm H 2 O (PEEP 25 ), 20 cm H 2 O (PEEP 20 ), 15 cm H 2 O (PEEP H ), 11 cm H 2 O (PEEP I ), and 7 cm H 2 O (PEEP L ). The higher PEEP value of the two PEEPs with similar best Crs was designated as PEEP upper , while the lower designated as PEEP lower . Results PEEP H and PEEP I shared the best Crs in two cases, while similar Crs was found at PEEP I and PEEP L in the remaining six cases. SIaw was higher with PEEP upper as compared to PEEP lower (1.06 ± 0.10 versus 0.99 ± 0.09, p = 0.05). Proportion of lung hyperdistension was significantly higher with PEEP upper than PEEP lower (7.0 ± 5.1% versus 0.3 ± 0.5%, p = 0.0002). In contrast, proportion of recruitable lung collapse was higher with PEEP lower than PEEP upper (18.6 ± 4.4% versus 5.9 ± 3.7%, p < 0.0001). Cyclic alveolar collapse and reopening during tidal breathing was higher at PEEP lower than PEEP upper (34.4 ± 19.3% versus 16.0 ± 9.1%, p = 0.046). The intratidal gas distribution (ITV) index was also significantly higher at PEEP lower than PEEP upper (2.6 ± 1.3 versus 1.8 ± 0.7, p = 0.042). Conclusions PEEP upper is a rational selection in ARDS cases with two similar best Crs. EIT provides additional information for the selection of PEEP in such circumstances.

Effects of Fatigue on Inter-joint Coordination in Ballet Dancers During a Ballet Jumping Movement (petit échappé sauté) - Chai-Wei Lin; Jeng-Feng Yang; Yi-An Chen; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

The major photoprotective role of anthocyanins in leaves of Arabidopsis thaliana under long-term high light treatment: antioxidant or light attenuator? - Xiao-Ting Zheng; Zheng-Chao Yu; Jun-Wei Tang; Min-Ling Cai; Yi-Lin Chen; Cheng-Wei Yang; Wah Soon Chow; Chang-Lian Peng (Photosynthesis Research, 2021)

Advantage of Multi-Directional Stability of Spiral Clavicle Plate in Treatment of Middle One-Third Clavicle Fracture: A Finite Element Study - Dan-Kai Wu; Wen-Chuan Chen; Kun-Jhih Lin; Cheng-Lun Tsai; Kang-Ping Lin; Hung-Wen Wei (Journal of Medical and Biological Engineering, 2021)

Performance Comparison of the Deep Learning and the Human Endoscopist for Bleeding Peptic Ulcer Disease - Hsu-Heng Yen; Ping-Yu Wu; Pei-Yuan Su; Chia-Wei Yang; Yang-Yuan Chen; Mei-Fen Chen; Wen-Chen Lin; Cheng-Lun Tsai; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2021)
Purpose Management of peptic ulcer bleeding is clinically challenging. Accurate characterization of the bleeding during endoscopy is key for endoscopic therapy. This study aimed to assess whether a deep learning model can aid in the classification of bleeding peptic ulcer disease. Methods Endoscopic still images of patients ( n = 1694) with peptic ulcer bleeding for the last 5 years were retrieved and reviewed. Overall, 2289 images were collected for deep learning model training, and 449 images were validated for the performance test. Two expert endoscopists classified the images into different classes based on their appearance. Four deep learning models, including Mobile Net V2, VGG16, Inception V4, and ResNet50, were proposed and pre-trained by ImageNet with the established convolutional neural network algorithm. A comparison of the endoscopists and trained deep learning model was performed to evaluate the model’s performance on a dataset of 449 testing images. Results The results first presented the performance comparisons of four deep learning models. The Mobile Net V2 presented the optimal performance of the proposal models. The Mobile Net V2 was chosen for further comparing the performance with the diagnostic results obtained by one senior and one novice endoscopists. The sensitivity and specificity were acceptable for the prediction of “normal” lesions in both 3-class and 4-class classifications. For the 3-class category, the sensitivity and specificity were 94.83% and 92.36%, respectively. For the 4-class category, the sensitivity and specificity were 95.40% and 92.70%, respectively. The interobserver agreement of the testing dataset of the model was moderate to substantial with the senior endoscopist. The accuracy of the determination of endoscopic therapy required and high-risk endoscopic therapy of the deep learning model was higher than that of the novice endoscopist. Conclusions In this study, the deep learning model performed better than inexperienced endoscopists. Further improvement of the model may aid in clinical decision-making during clinical practice, especially for trainee endoscopist.

Aestuariibaculum sediminum sp. nov., a marine bacterium isolated from a tidal flat in Zhoushan - Zhi-Cheng Wu; Xin-Yin Zhang; Cong Sun; Lin Xu; Ge-Yi Fu; Xue-Wei Xu (Archives of Microbiology, 2021)

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Quantitative characterization of horizontal well production performance with multiple indicators: a case study on the Weiyuan shale gas field in the Sichuan Basin, China - Rongze Yu; Wei Guo; Lin Ding; Meizhu Wang; Feng Cheng; Xiaowei Zhang; Shangwen Zhou; Leifu Zhang (Frontiers of Earth Science, 2021)

PtP38 May Increase the Immune Ability of Portunus trituberculatus Stimulated by LPS Imitating a Gram-Negative Bacterial Infection - Cheng-Peng Lu; Chao-Guang Wei; Jun-Quan Zhu; Dao-Jun Tang; Chun-Lin Wang; Cong-Cong Hou (Frontiers in Marine Science, 2021)
The P38 mitogen-activated protein kinase (MAPK) signal transduction pathway is widespread in organisms and plays important roles in immune activities. The infection mechanism of environmental gram-negative bacteria on crustaceans is an important scientific problem. In this study, the cDNA full-length sequence of Portunus trituberculatus P38 (PtP38) was cloned and its structure was analyzed by bioinformatics methods. To study the function of the PtP38 gene after a Gram-negative bacterial infection, we injected P. trituberculatus with LPS to activate the immune response instead of directly infecting with Gram-negative bacteria. With LPS stimulation, the expression of the PtP38 gene in different tissues increased significantly. At the same time, the expression of immune-related genes (ALF and crustin) in the hepatopancreas, activities of antioxidant enzymes [superoxide dismutase (SOD), catalase (CAT), and inducible nitric oxide synthase (iNOS) enzymes], and expression of apoptosis-related genes (caspase2 and caspase3) were increased significantly. To further conform the function of PtP38 in the immune response, we injected P. trituberculatus with P38 inhibitor and subsequently injected with LPS. The results showed that the expression of immune-related genes was inhibited, the activity of antioxidant enzymes was decreased, and the expression of apoptosis-related genes were inhibited. Thus, we speculated that PtP38 may increase the immune ability by improving the expression of antimicrobial peptides, increasing the activity of oxidative stress-related enzymes, and promoting cell apoptosis in infected P. trituberculatus . This study also laid the foundation for further study of the P38 MAPK signaling pathway and immune mechanism of P. trituberculatus .

An Efficient Monte-Carlo Simulation for the Dynamic Reliability Analysis of Jacket Platforms Subjected to Random Wave Loads - Wei Lin; Cheng Su (Journal of Marine Science and Engineering, 2021)
The growing demand for the application of jacket platforms in deep water requires more attention on the assessment of structural reliability. This paper is devoted to the dynamic reliability analysis of jacket platforms subjected to random wave loads with the Monte-Carlo simulation (MCS), in which a sample size of the order of magnitude of 104 to 105 for repeated time–history analyses is required for small failure probability problems, and a duration time up to three hours needs to be considered in the time–history analyses for a specific sea condition. To tackle the difficulty involved in the MCS, the explicit time-domain method (ETDM) is used for the required time–history analyses of jacket platforms, in which truncated explicit expressions of critical responses with regards to the contributing loading terms are first established and then used for numerous repeated sample analyses. The use of ETDM greatly enhances the computational efficiency of MCS, making it feasible for the dynamic reliability analysis of jacket platforms under random wave loads. A jacket platform with 11,688 degrees of freedom was analyzed for the evaluation of dynamic reliability under a given sea condition, indicating the accuracy and efficiency of the present approach and its feasibility to practical structures.

Structure of SARS-CoV-2 main protease in the apo state - Xuelan Zhou; Fanglin Zhong; Cheng Lin; Xiaohui Hu; Yan Zhang; Bing Xiong; Xiushan Yin; Jinheng Fu; Wei He; Jingjing Duan; Yang Fu; Huan Zhou; et al. (Science China Life Sciences, 2021)

Phylogeny and taxonomy of two new Alternaria (Ascomycota: Pleosporaceae) species in section Gypsophilae from China - Lin He; Hong Cheng; Aye Aye Htun; Hui Ge; Zhen Zhou Xia; Jian Wei Guo; Jian Xin Deng; Tao Du (Mycological Progress, 2021)

AKR1C1 Contributes to Cervical Cancer Progression via Regulating TWIST1 Expression - Xing Wei; Zhongheng Wei; Yueyong Li; Zhongqiu Tan; Cheng Lin (Biochemical Genetics, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Sesquiterpenoids and meroterpenoids from a mangrove derived fungus Diaporthe sp. SCSIO 41011 - Xiao-Wei Luo; Chun-Mei Chen; Kun-Long Li; Xiu-Ping Lin; Cheng-Hai Gao; Xue-Feng Zhou; Yong-Hong Liu (Natural Product Research, 2021)

Explicit Time-Domain Approach for Random Vibration Analysis of Jacket Platforms Subjected to Wave Loads - Wei Lin; Cheng Su; Youhong Tang (Journal of Marine Science and Engineering, 2020)
This paper is devoted to the random vibration analysis of jacket platforms under wave loads using the explicit time-domain approach. The Morison equation is first used to obtain the nonlinear random wave loads, which are discretized into random loading vectors at a series of time instants. The Newmark-β integration scheme is then employed to construct the explicit expressions for dynamic responses of jacket platforms in terms of the random vectors at different time instants. On this basis, Monte Carlo simulation can further be conducted at high efficiency, which not only provides the statistical moments of the random responses, but also gives the mean peak values of responses. Compared with the traditional power spectrum method, nonlinear wave loads can be readily taken into consideration in the present approach rather than using the equivalent linearized Morison equation. Compared with the traditional Monte Carlo simulation, the response statistics can be obtained through the direct use of the explicit expressions of dynamic responses rather than repeatedly solving the equation of motion. An engineering example is analyzed to illustrate the accuracy and efficiency of the present approach.

Influences of Physical Vegetation Management on Odonata Abundance in Urbanized Ecosystem: a Case Study in Northern Taiwan - Pin-Yuan Chen; Cheng-Tao Lin; Rita S. W. Yam; Hsiao-Wei Yuan (Wetlands, 2020)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Optimizing the MIC breakpoints of amoxicillin and tetracycline for antibiotic selection in the rescue therapy of H. pylori with bismuth quadruple regimen - Ming-Tsung Hsieh; Wei-Lun Chang; Chung-Tai Wu; Hsiao-Bai Yang; Hsin-Yu Kuo; Meng-Ying Lin; Hsiu-Chi Cheng; Yu-Chin Tsai; Bor-Shyang Sheu (European Journal of Clinical Pharmacology, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

How do Biotic and Abiotic Factors Regulate Soil Enzyme Activities at Plot and Microplot Scales Under Afforestation? - Qianxi Li; Ji Chen; Jiao Feng; Junjun Wu; Qian Zhang; Wei Jia; Qiaoling Lin; Xiaoli Cheng (Ecosystems, 2020)

Correction to: Complete genome sequences of two novel dicistroviruses detected in yellow crazy ants (Anoplolepis gracilipes) - Chih-Chi Lee; Chun-Yi Lin; Hung-Wei Hsu; Chin-Cheng Scotty Yang (Archives of Virology, 2020)

Complete genome sequences of two novel dicistroviruses detected in yellow crazy ants (Anoplolepis gracilipes) - Chih-Chi Lee; Chun-Yi Lin; Hung-Wei Hsu; Chin-Cheng Scotty Yang (Archives of Virology, 2020)

Modification-bioremediation of copper, lead, and cadmium-contaminated soil by combined ryegrass (Lolium multiflorum Lam.) and Pseudomonas aeruginosa treatment - Guang-yu Shi; Ying-jia Yan; Zhi-qiang Yu; Lu Zhang; Yuan-yuan Cheng; Wei-lin Shi (Environmental Science and Pollution Research, 2020)

Putative Probiotic Strains Isolated from Kefir Improve Gastrointestinal Health Parameters in Adults: a Randomized, Single-Blind, Placebo-Controlled Study - Ming-Cheng Wang; Ahmad Imran Zaydi; Wei-Hung Lin; Jin-Seng Lin; Min-Tze Liong; Jiunn-Jong Wu (Probiotics and Antimicrobial Proteins, 2020)

Evolution of Neolithic site distribution (9.0–4.0 ka BP) in Anhui, East China - Li Wu; Xiaoling Sun; Wei Sun; Cheng Zhu; Tongxin Zhu; Shuguang Lu; Hui Zhou; Qingchun Guo; Houchun Guan; Wei Xie; Rui Ke; Guiping Lin (Journal of Geographical Sciences, 2020)

Five new ent -kaurane diterpenes from Annona squamosa L. pericarps - Ya-Yun Chen; Cheng-Yao Ma; Mao-Lin Wang; Jia-Hui Lu; Peng Hu; Jian-Wei Chen; Xiang Li; Yong Chen (Natural Product Research, 2020)

Relationship Between Seismic Moment and Source Duration for Seismogenic Earthquakes in Taiwan: Implications for the Product of Static Stress Drop and the Cube of Rupture Velocity - Ruey-Der Hwang; Cheng-Ying Ho; Tzu-Wei Lin; Wen-Yen Chang; Yi-Ling Huang; Cai-Yi Lin; Chiung-Yao Lin (Pure and Applied Geophysics, 2020)

Baicalein attenuates caspase-independent cells death via inhibiting PARP-1 activation and AIF nuclear translocation in cerebral ischemia/reperfusion rats - Wei-Han Li; Ying-Lin Yang; Xiao Cheng; Man Liu; Shan-Shan Zhang; Yue-Hua Wang; Guan-Hua Du (Apoptosis, 2020)

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Dynamic Alterations of Brain Injury, Functional Recovery, and Metabolites Profile after Cerebral Ischemia/Reperfusion in Rats Contributes to Potential Biomarkers - Xiao Cheng; Ying-Lin Yang; Wei-Han Li; Man Liu; Shan-Shan Zhang; Yue-Hua Wang; Guan-Hua Du (Journal of Molecular Neuroscience, 2020)

Nanochemoprevention with therapeutic benefits: An updated review focused on epigallocatechin gallate delivery - Qiong-Qiong Yang; Xin-Lin Wei; Ya-Peng Fang; Ren-You Gan; Min Wang; Ying-Ying Ge; Dan Zhang; Li-Zeng Cheng; Harold Corke (Critical Reviews in Food Science and Nutrition, 2020)

Impacts of elevated temperature and pCO2 on the brooded larvae of Pocillopora damicornis from Luhuitou Reef, China: evidence for local acclimatization - Lei Jiang; Ming-Lan Guo; Fang Zhang; Yu-Yang Zhang; Guo-Wei Zhou; Xin-Ming Lei; Xiang-Cheng Yuan; You-Fang Sun; Tao Yuan; Lin Cai; Jian-Sheng Lian; Sheng Liu; et al. (Coral Reefs, 2020)

Potential Genes Related to Levofloxacin Resistance in Mycobacterium tuberculosis Based on Transcriptome and Methylome Overlap Analysis - Hai-cheng Li; Hui-xin Guo; Tao Chen; Wei Wang; Zhu-hua Wu; Liang Chen; Hui-zhong Wu; Gao-po Xu; Xun-xun Chen; Lin Zhou (Journal of Molecular Evolution, 2020)
Drug-resistant Mycobacterium tuberculosis ( M. tuberculosis ) has become an increasingly serious public health problem and has complicated tuberculosis (TB) treatment. Levofloxacin (LOF) is an ideal anti-tuberculosis drug in clinical applications. However, the detailed molecular mechanisms of LOF-resistant M. tuberculosis in TB treatment have not been revealed. Our study performed transcriptome and methylome sequencing to investigate the potential biological characteristics of LOF resistance in M. tuberculosis H37Rv. In the transcriptome analysis, 953 differentially expressed genes (DEGs) were identified; 514 and 439 DEGs were significantly downregulated and upregulated in the LOF-resistant group and control group, respectively. The KEGG pathway analysis revealed that 97 pathways were enriched in this study. In the methylome analysis, 239 differentially methylated genes (DMGs) were identified; 150 and 89 DMGs were hypomethylated and hypermethylated in the LOF-resistant group and control group, respectively. The KEGG pathway analysis revealed that 74 pathways were enriched in this study. The overlap study suggested that 25 genes were obtained. It was notable that nine genes expressed downregulated mRNA and upregulated methylated levels, including pgi , fadE4 , php , cyp132 , pckA , rpmB1 , pfkB , acg , and ctpF , especially cyp132 , pckA , and pfkB , which were vital in LOF-resistant M. tuberculosis H37Rv. The overlapping genes between transcriptome and methylome could be essential for studying the molecular mechanisms of LOF-resistant M. tuberculosis H37Rv. These results may provide informative evidence for TB treatment with LOF.

Chemical fingerprint and source apportionment of PM2.5 in highly polluted events of southern Taiwan - Huazhen Shen; Tsung-mou Yang; Chun-chung Lu; Chung-shin Yuan; Chung-Hsuang Hung; Chi-tsan Lin; Chia-wei Lee; Guohua Jing; Gongren Hu; Kuo-cheng Lo (Environmental Science and Pollution Research, 2020)

Plasma biomarkers and plaque strain predict long-term cardiovascular events in patients with acute coronary syndrome - Mingjun Xu; Xiaobo Hu; Lin Wang; Wei Zhang; Lindi Wu; Jifu Li; Yuguo Chen; Pengfei Zhang; Haijun Su; Yaling Han; Cheng Zhang; Mei Zhang; et al. (Science China Life Sciences, 2020)

Leveraging complementary computational models for prioritizing chemicals of developmental and reproductive toxicity concern: an example of food contact materials - Chun-Wei Tung; Hsien-Jen Cheng; Chia-Chi Wang; Shan-Shan Wang; Pinpin Lin (Archives of Toxicology, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

A multidecadal change analysis for irrigation ponds in Taoyuan, Taiwan, using multisource data - Yen-Ching Chen; Wei-Chun Lin; Lin-Hsuan Hsiao; Ke-Sheng Cheng (Paddy and Water Environment, 2020)

Chitin synthase is involved in vegetative growth, asexual reproduction and pathogenesis of Phytophthora capsici and Phytophthora sojae - Wei Cheng; Menglan Lin; Min Qiu; Liang Kong; Yuanpeng Xu; Yaning Li; Yan Wang; Wenwu Ye; Suomeng Dong; Shuilin He; Yuanchao Wang (Environmental Microbiology, 2019)
Summary Chitin is a structural and functional component of the fungal cell wall and also serves as a pathogen‐associated molecular pattern (PAMP) that triggers the innate immune responses of host plants. However, no or very little chitin is found in the fungus‐like oomycetes. In Phytophthora spp., the presence of chitin has not been demonstrated so far, although putative chitin synthase (CHS) genes, which encode the enzymes that synthesize chitin, are present in their genomes. Here, we revealed that chitin is present in the zoospores and released sporangia of Phytophthora , and this is most consistent with the transcriptional pattern of PcCHS in Phytophthora capsici and PsCHS1 in Phytophthora sojae . Disruption of the CHS genes indicated that PcCHS and PsCHS1 , but not PsCHS2 (which exhibited very weak transcription), have similar functions involved in mycelial growth, sporangial production, zoospore release and the pathogenesis of P. capsici and P. sojae . We also suggest that chitin in the zoospores of P. capsici can act as a PAMP that is recognized by the chitin receptors AtLYK5 or AtCERK1 of Arabidopsis . These results provide new insights into the biological significance of chitin and CHSs in Phytophthora and help with the identification of potential targets for disease control.

Application of Cas12a and nCas9-activation-induced cytidine deaminase for genome editing and as a non-sexual strategy to generate homozygous/multiplex edited plants in the allotetraploid genome of tobacco - Chen-Tran Hsu; Yu-Jung Cheng; Yu-Hsua Yuan; Wei-Fon Hung; Qiao-Wei Cheng; Fu-Hui Wu; Lan-Ying Lee; Stanton B. Gelvin; Choun-Sea Lin (Plant Molecular Biology, 2019)

Remediation of TCE-contaminated groundwater using KMnO4 oxidation: laboratory and field-scale studies - Zong-Han Yang; Jiun-Hau Ou; Cheng-Di Dong; Chiu-Wen Chen; Wei-Han Lin; Chih-Ming Kao (Environmental Science and Pollution Research, 2019)

Aflatoxin B1 enhances pyroptosis of hepatocytes and activation of Kupffer cells to promote liver inflammatory injury via dephosphorylation of cyclooxygenase-2: an in vitro, ex vivo and in vivo study - Li-Yin Zhang; Deng-Lin Zhan; Yuan-Yuan Chen; Wei-Hua Wang; Cheng-Yong He; Yi Lin; Yu-Chun Lin; Zhong-Ning Lin (Archives of Toxicology, 2019)

Adsorption Removal of Cr(VI) with Activated Carbon Prepared by Co-pyrolysis of Rice Straw and Sewage Sludge with ZnCl2 Activation - Liangqian Fan; Wenxin Wan; Xianda Wang; Jie Cai; Fenghui Chen; Wei Chen; Lin Ji; Hongbing Luo; Lin Cheng (Water, Air, & Soil Pollution, 2019)

Self-rooted grafting influences the growth and cadmium accumulation characteristics in the post generation of Cosmos sulphureus - Jin Wang; Yumei Tan; Ming’an Liao; Lijin Lin; Yi Tang; Huifen Zhang; Hui Xia; Dong Liang; Qunxian Deng; Xiulan Lv; Cheng Chen; Wei Ren (Environmental Science and Pollution Research, 2019)

Complete Genome Sequence of Qipengyuania sediminis CGMCC 1.12928T, Shed Light on Its Role in Matter-Cycle and Cold Adaption Mechanism of the Genus Qipengyuania - Yan Gao; Yue-Hong Wu; Lin Xu; Hong Cheng; Chun-Sheng Wang; Xue-Wei Xu (Current Microbiology, 2019)

Steroid-Enriched Fraction of Achyranthes bidentata Protects Amyloid β Peptide 1–40-Induced Cognitive Dysfunction and Neuroinflammation in Rats - Li-Wei Lin; Fan-Hsuan Tsai; Wan-Cheng Lan; Yih-Dih Cheng; Sheng-Chi Lee; Chi-Rei Wu (Molecular Neurobiology, 2019)

Adult sacrococcygeal teratoma: a retrospective study over eight years at a single institution - Xiang-ming Xu; Feng Zhao; Xiao-fei Cheng; Wei-xiang Zhong; Jing-peng Liu; Wei-qin Jiang; Xiao-kai Yu; Jian-jiang Lin (Journal of Zhejiang University-SCIENCE B, 2019)

A Carbon Footprint of High‐Speed Railways in China: A Case Study of the Beijing‐Shanghai Line - Jianyi Lin; Huimei Li; Wei Huang; Wangtu(Ato) Xu; Shihui Cheng (Journal of Industrial Ecology, 2019)
Summary A carbon footprint (CF) assessment of Chinese high‐speed railways (HSRs) can help guide further development of the world's longest HSR network. In this research, a hybrid economic input‐output and life cycle assessment (EIO‐LCA) method was applied to estimate the CF of the Beijing‐Shanghai HSR line. Specific CFs were analyzed of different subsystems of the line, different stages of production, and three calculation scopes. Results showed that the annual CF of the Beijing‐Shanghai HSR is increasing, whereas the per‐passenger CF constantly declined between 2011 and 2014. Scope 1 emissions account for an average of 4% of the total annual CF, Scope 2 contribute 71%, and Scope 3 comprise 25%. Among the different stages, operation contributes the largest (71%), followed by construction (20%) and maintenance (9%). In the construction stage, the bridges have the largest CF, followed by trains, and then rails. A trade‐off exists between the increase in carbon emissions due to construction of bridges and the reduction in operation emissions affected by leveling changes in terrain. The Beijing‐Shanghai HSR line has a relatively higher per‐passenger CF than eight other HSR lines, which is largely due to China's coal‐based carbon‐intensive energy mix of electricity generation, high proportion of bridges, higher operating speed, and heavier train body. In the future, cleaner electricity supply options, more efficient raw material production, and improvement of trains are keys to reducing the CF of Chinese HSRs.

Role of a VGF/BDNF/TrkB Autoregulatory Feedback Loop in Rapid-Acting Antidepressant Efficacy - Cheng Jiang; Wei-Jye Lin; Stephen R. Salton (Journal of Molecular Neuroscience, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

The Anti-bacterial and Anti-adherent Effects of Pentraxin-3 on Porcine Kidney Epithelial PK15 Cells Against Staphylococcus aureus Infection - Bao-Hong Lee; Wei-Hsuan Hsu; Cheng-Hui Lin (International Journal of Peptide Research and Therapeutics, 2019)

The complete maternal mitochondrial genome of Acuticosta chinensis (Bivalvia: Unionoida: Unionidae) - Qishuo Wang; Lin Li; Cheng Wang; Cuizhen Wei; Ruijuan Feng; Jing Huang (Conservation Genetics Resources, 2019)

Lasiodiplodia spp. associated with Aquilaria crassna in Laos - Yu Wang; Sen Lin; Lin Zhao; Xiang Sun; Wei He; Ying Zhang; Yu-Cheng Dai (Mycological Progress, 2019)

Selective, Sensitive and Label-Free Detection of Fe3+ Ion in Tap Water Using Highly Fluorescent Graphene Quantum Dots - Yuanyuan Zhang; Xiangyue Yang; Yunxun Pu; Wei Cheng; Song Lin; Zeyu Shao; Xiaoling Liao (Journal of Fluorescence, 2019)

Cutting after grafting affects the growth and cadmium accumulation of Nasturtium officinale - Xingyu Zhang; Fenqin Zhang; Jin Wang; Lijin Lin; Ming’an Liao; Yi Tang; Guochao Sun; Xun Wang; Xiulan Lv; Qunxian Deng; Cheng Chen; Wei Ren (Environmental Science and Pollution Research, 2019)

A novel SGNH family hydrolase Ali5 with thioesterase activity and a GNSL motif but without a classic GDSL motif from Altererythrobacter ishigakiensis - Li-Guo Hong; Shu-Ling Jian; Ying-Yi Huo; Hong Cheng; Xiao-Jian Hu; Jixi Li; Heng-Lin Cui; Xue-Wei Xu (Biotechnology Letters, 2019)

2D Numerical Study of the Stability of Trench under Wave Action in the Immersing Process of Tunnel Element - Wei-Yun Chen; Cheng-Lin Liu; Lun-Liang Duan; Hao-Miao Qiu; Zhi-Hua Wang (Journal of Marine Science and Engineering, 2019)
The evaluation of the trench stability under the action of ocean waves is an important issue in the construction of an immersed tunnel. In this study, a two-dimensional coupling model of a wave-seabed-immersed tunnel is proposed for the dynamic responses of a trench under wave action in the immersing process of tunnel elements. The porous seabed is characterized by Biot consolidation equations. The k − ε model and RANS equation are adopted to achieve the flow field simulation, and the level set method (LSM) is used to capture the free surface between the water and air. The proposed numerical model is verified using the experimental data and analytical results. Then, the transient liquefaction and shear failure in the vicinity of the trench are discussed at two different conditions, namely, after the foundation groove is excavated and after the tunnel element is placed. The pore pressure amplitude on the weather side slope is demonstrated to be significantly smaller than that on the lee side slope. Also, the distribution of the surrounding flow field and pressure field change dramatically after the tunnel element is settled, leading to the significant changes of seabed stability.

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Plasminogen/thrombomodulin signaling enhances VEGF expression to promote cutaneous wound healing - Tsung-Lin Cheng; Po-Ku Chen; Wei-Kai Huang; Cheng-Hsiang Kuo; Chia-Fong Cho; Kuan-Chieh Wang; Guey-Yueh Shi; Hua-Lin Wu; Chao-Han Lai (Journal of Molecular Medicine, 2018)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Toward a higher yield: a wireless sensor network-based temperature monitoring and fan-circulating system for precision cultivation in plant factories - Joe-Air Jiang; Min-Sheng Liao; Tzu-Shiang Lin; Chen-Kang Huang; Cheng-Ying Chou; Shih-Hao Yeh; Ta-Te Lin; Wei Fang (Precision Agriculture, 2018)

Bacterial wilt caused by Ralstonia pseudosolanacearum (R. solanacearum phylotype I) on Luffa cylindrica in China - Yao Wen Zhang; YuanYuan Chen; Cheng Hui Hu; Qi Qin Li; Wei Lin; Gao Qing Yuan (Journal of Plant Pathology, 2018)

Regulatory Effects of Neuroinflammatory Responses Through Brain-Derived Neurotrophic Factor Signaling in Microglial Cells - Sheng-Wei Lai; Jia-Hong Chen; Hsiao-Yun Lin; Yu-Shu Liu; Cheng-Fang Tsai; Pei-Chun Chang; Dah-Yuu Lu; Chingju Lin (Molecular Neurobiology, 2018)

Dynamic response of a dip slope with multi-slip planes revealed by shaking table tests - Hung-Hui Li; Cheng-Han Lin; Wei Zu; Chi-Chieh Chen; Meng-Chia Weng (Landslides, 2018)

Clinical and microbiological characteristics of peritoneal dialysis-related peritonitis caused by Escherichia coli in southern Taiwan - Wei-Hung Lin; Chin-Chung Tseng; An-Bang Wu; Yu-Tzu Chang; Te-Hui Kuo; Jo-Yen Chao; Ming-Cheng Wang; Jiunn-Jong Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Acetaminophen Poisoning May Increase Coronary Artery Disease Risk: A Nationwide Cohort Study - Yu-Ting Chung; Che-Yi Chou; Wen-Chen Tsai; Wei-Kung Chen; Cheng-Li Lin; Wei-Sheng Chung (Cardiovascular Toxicology, 2018)

Temporal and Spatial Variations of Microbial Carbon Utilization in Water Bodies from the Dajiuhu Peatland, Central China - Rui-Cheng Wang; Hong-Mei Wang; Xing Xiang; Yu Gao; Qing-Wei Song; Lin-Feng Gong (Journal of Earth Science, 2018)

Sharp and laterally constrained multitrace impedance inversion based on blocky coordinate descent - Yaojun Wang; Wencheng Lin; San Cheng; Bin She; Guangmin Hu; Wei Liu (Acta Geophysica, 2018)

Assessment of Land Subsidence and Climate Change Impacts on Inundation Hazard in Southwestern Taiwan - Hsiao‐Wen Wang; Cheng‐Wei Lin; Chun‐Yao Yang; Chung‐Feng Ding; Hwung‐Hweng Hwung; Shih‐Chun Hsiao (Irrigation and Drainage, 2018)
Excessive extraction of groundwater resulting in serious land subsidence as well as intensified rainfall and storm surges due to climate change complicate the flooding problems in southwest Taiwan. A coupled set of different models was proposed to analyze the effect of inundation risk considering land subsidence and climate change. Three models, including the groundwater flow model, land subsidence model, and the physiographic drainage–inundation model, were used in this study, enabling simulations of different considerations. The results revealed that more severe flooding would result from land subsidence and climate change. The findings of a 21% increase in flood area with an inundation depth greater than 1.5 m for 200‐yr return period events clearly showed more severe flooding would result from land subsidence. The flooding in those severely subsiding areas would increase in a range from 3.4 to 21.5% when further considering climate change. While the simulation results revealed that the flood area could be decreased by as much as 50% taking into account the implemented policies, the coastal region would still be exposed to a high risk of being flooded. It thus suggests that policies focusing on infrastructure would be insufficient, and river basin management as well as spatial planning should be investigated further. Copyright © 2018 John Wiley & Sons, Ltd.

Immunogenicity of adenovirus and DNA vaccines co-expressing P39 and lumazine synthase proteins of Brucella abortus in BALB/c mice - Guo-Zhen Lin; Ju-Tian Yang; Suo-Cheng Wei; Shi-En Chen; Sheng-Dong Huo; Zhong-Ren Ma (Tropical Animal Health and Production, 2018)

c.835-5T>G Variant in SMN1 Gene Causes Transcript Exclusion of Exon 7 and Spinal Muscular Atrophy - Shuang Wu; Yun-Lu Li; Ning-Yi Cheng; Chong Wang; En-Lin Dong; Ying-Qian Lu; Jin-Jing Li; Xin-Xin Guo; Xiang Lin; Lu-Lu Lai; Zhi-Wei Liu; Ning Wang; et al. (Journal of Molecular Neuroscience, 2018)

An improved torque type gravity gradiometer with dynamic modulation - Jie Luo; Jia-Hao Xu; Qi Liu; Cheng-Gang Shao; Lin Zhu; Hui-Hui Zhao; Wei-Huang Wu (Acta Geodaetica et Geophysica, 2018)

Mobile carbon supply in trees and shrubs at the alpine treeline ecotone - Qing-Wei Wang; Cheng-Gang Liu; Wangming Zhou; Lin Qi; Li Zhou; Dapao Yu; Limin Dai (Plant Ecology, 2018)

Effects of melatonin on the growth and cadmium characteristics of Cyphomandra betacea seedlings - Lijin Lin; Jianhua Li; Fabo Chen; Ming’an Liao; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai; Xun Wang; Cheng Chen; Wei Ren (Environmental Monitoring and Assessment, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Evidence that NF-κB and MAPK Signaling Promotes NLRP Inflammasome Activation in Neurons Following Ischemic Stroke - David Yang-Wei Fann; Yun-An Lim; Yi-Lin Cheng; Ker-Zhing Lok; Prasad Chunduri; Sang-Ha Baik; Grant R. Drummond; S. Thameem Dheen; Christopher G. Sobey; Dong-Gyu Jo; Christopher Li-Hsian Chen; Thiruma V. Arumugam (Molecular Neurobiology, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Tamoxifen usage correlates with increased risk of Parkinson’s disease in older women with breast cancer: a case–control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2018)

Association of use of selective serotonin reuptake inhibitors with risk of acute pancreatitis: a case-control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Effects of mutual intercropping on the cadmium accumulation in accumulator plants Stellaria media, Malachium aquaticum, and Galium aparine - Qiyu Lu; Jianhua Li; Fabo Chen; Ming’an Liao; Lijin Lin; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai; Xun Wang; Cheng Chen; Wei Ren (Environmental Monitoring and Assessment, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Magnesium Ions Promote the Biological Behaviour of Rat Calvarial Osteoblasts by Activating the PI3K/Akt Signalling Pathway - Jian Wang; Xiang-Yu Ma; Ya-Fei Feng; Zhen-Sheng Ma; Tian-Cheng Ma; Yang Zhang; Xiang Li; Lin Wang; Wei Lei (Biological Trace Element Research, 2017)

Correlation between proton pump inhibitors and risk of pyogenic liver abscess - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

RNA-Seq reveals differential expression patterns of genes associated with carotenoid accumulation in loquat - Ting-ting Zheng; Zhi-ke Zhang; Muhammad Qasim Shahid; Wei-ling Wei; Faheem Shehzad Baloch; Jin-cheng Wu; Shun-quan Lin; Xiang-hui Yang (Acta Physiologiae Plantarum, 2017)

Coal Permeability Evolution and Gas Migration Under Non-equilibrium State - Ting Liu; Baiquan Lin; Wei Yang; Cheng Zhai; Tong Liu (Transport in Porous Media, 2017)

Mixture risk assessment due to ingestion of arsenic, copper, and zinc from milkfish farmed in contaminated coastal areas - Yi-Jun Lin; Min-Pei Ling; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Hsien Cheng; Shu-Han You; Wei-Chun Chou; Ming-Chao Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Ommaya reservoir in the treatment of cryptococcal meningitis - Baozhu Wei; Cheng Qian; Yang Liu; Xuan Lin; Jing Wan; Yanggan Wang (Acta Neurologica Belgica, 2017)

Erratum to: Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Novel interaction between CCR4 and CAF1 in rice CCR4–NOT deadenylase complex - Wei-Lun Chou; Yue-Lin Chung; Jhen-Cheng Fang; Chung-An Lu (Plant Molecular Biology, 2017)

Chemical composition and antioxidant activities of essential oils from different parts of the oregano - Fei Han; Guang-qiang Ma; Ming Yang; Li Yan; Wei Xiong; Ji-cheng Shu; Zhi-dong Zhao; Han-lin Xu (Journal of Zhejiang University-SCIENCE B, 2017)

Investigations into Salmonella contamination in feed production chain in Karst rural areas of China - Shenglin Yang; Zongfen Wu; Wei Lin; Longxin Xu; Long Cheng; Lin Zhou (Environmental Science and Pollution Research, 2017)

Interlukin-18 Is a Pivot Regulatory Factor on Matrix Metalloproteinase-13 Expression and Brain Astrocytic Migration - Jia-Hong Chen; Chon-Haw Tsai; Hsiao-Yun Lin; Chien-Fang Huang; Yuk-Man Leung; Sheng-Wei Lai; Cheng-Fang Tsai; Pei-Chun Chang; Dah-Yuu Lu; Chingju Lin (Molecular Neurobiology, 2016)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

Cobalt Protoporphyrin Upregulates Cyclooxygenase-2 Expression Through a Heme Oxygenase-Independent Mechanism - Hsiao-Yun Lin; Chon-Haw Tsai; Chingju Lin; Wei-Lan Yeh; Cheng-Fang Tsai; Pei-Chun Chang; Ling-Hsuan Wu; Dah-Yuu Lu (Molecular Neurobiology, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

SSR-based genetic mapping and QTL analysis for timing of spring bud flush, young shoot color, and mature leaf size in tea plant (Camellia sinensis) - Li-Qiang Tan; Li-Yuan Wang; Li-Yi Xu; Li-Yun Wu; Min Peng; Cheng-Cai Zhang; Kang Wei; Pei-Xian Bai; Hai-Lin Li; Hao Cheng; Gui-Nian Qi (Tree Genetics & Genomes, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Complete genome sequence of the cold-active bacteriophage VMY22 from Bacillus cereus - Kunhao Qin; Benxu Cheng; Shengting Zhang; Nan Wang; Yuan Fang; Qi Zhang; Anxiu Kuang; Lianbing Lin; Xiuling Ji; Yunlin Wei (Virus Genes, 2016)

Serotonin Receptor 2B Mediates Mechanical Hyperalgesia by Regulating Transient Receptor Potential Vanilloid 1 - Yeu-Shiuan Su; Yuan-Yi Chiu; Shih-Yuan Lin; Chih-Cheng Chen; Wei-Hsin Sun (Journal of Molecular Neuroscience, 2016)

Maternal exposure to di-(2-ethylhexyl) phthalate exposure deregulates blood pressure, adiposity, cholesterol metabolism and social interaction in mouse offspring - Kuan-I Lee; Chin-Wei Chiang; Hui-Ching Lin; Jin-Feng Zhao; Cheng-Ta Li; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

A new phenylethanoid glycoside from Orobanche cernua Loefling - Zheng-yi Qu; Yu-wei Zhang; Si-wen Zheng; Chun-lin Yao; Yin-ping Jin; Pei-he Zheng; Cheng-he Sun; Ying-ping Wang (Natural Product Research, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

PRL-3 promotes gastric cancer migration and invasion through a NF-κB-HIF-1α-miR-210 axis - Cheng Zhang; Wei Tian; Lin Meng; Like Qu; Chengchao Shou (Journal of Molecular Medicine, 2016)

Naringenin Suppresses Neuroinflammatory Responses Through Inducing Suppressor of Cytokine Signaling 3 Expression - Ling-Hsuan Wu; Chingju Lin; Hsiao-Yun Lin; Yu-Shu Liu; Caren Yu-Ju Wu; Cheng-Fang Tsai; Pei-Chun Chang; Wei-Lan Yeh; Dah-Yuu Lu (Molecular Neurobiology, 2016)

Humic acids enhance the microbially mediated release of sedimentary ferrous iron - Chun-Han Chang; Chia-Cheng Wei; Li-Hung Lin; Tzu-Hsuan Tu; Vivian Hsiu-Chuan Liao (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Improved random noise attenuation using f−x empirical mode decomposition and local similarity - Shu-Wei Gan; Shou-Dong Wang; Yang-Kang Chen; Jiang-Long Chen; Wei Zhong; Cheng-Lin Zhang (Applied Geophysics, 2016)

Six new metabolites produced by Colletotrichum aotearoa 09F0161, an endophytic fungus isolated from Bredia oldhamii - Yi Hsiao; Ming-Jen Cheng; Hsun-Shuo Chang; Ming-Der Wu; Sung-Yuan Hsieh; Ta-Wei Liu; Chu-Hung Lin; Gwo-Fang Yuan; Ih-Sheng Chen (Natural Product Research, 2016)

Joint observation results of Na layer and ionosphere in Wuhan during the Total Solar Eclipse - XueWu Cheng; Yong Yang; ZeLong Wang; FaQuan Li; GuoTao Yang; ZhengYu Zhao; Wei Gong; JiHong Wang; Xiong Hu; Xin Lin; XiaoCheng Wu; ShaLei Song; et al. (Science China Earth Sciences, 2016)

Scutellarin Alleviates Behavioral Deficits in a Mouse Model of Multiple Sclerosis, Possibly Through Protecting Neural Stem Cells - Wei-Wei Wang; Lin Lu; Tian-Hao Bao; Hong-Miao Zhang; Jing Yuan; Wei Miao; Shu-Fen Wang; Zhi-Cheng Xiao (Journal of Molecular Neuroscience, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Metabolic differences of industrial acarbose-producing Actinoplanes sp. A56 under various osmolality levels - Kun-tai Li; Wei-fu Peng; Wei Xia; Lin Huang; Xin Cheng (World Journal of Microbiology and Biotechnology, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

IL-17A enhances ADAMTS-7 expression through regulation of TNF-α in human nucleus pulposus cells - Shuai-Shuai Wang; Wei Zhang; Yuan-Qiang Zhang; Yunpeng Zhao; Yi Liu; Jing-kun Li; Hao-xuan Zhang; Lei Cheng; Lin Nie (Journal of Molecular Histology, 2015)

High-Performance Multiclass Classification Framework Using Cloud Computing Architecture - Feng-Sheng Lin; Chia-Ping Shen; Chia-Hung Liu; Han Lin; Chi-Ying F. Huang; Cheng-Yan Kao; Feipei Lai; Jeng-Wei Lin (Journal of Medical and Biological Engineering, 2015)

Voriconazole: a novel treatment option for cryptococcal meningitis - Yan Yao; Jia-Tang Zhang; Bo Yan; Ting Gao; Xiao-Wei Xing; Cheng-Lin Tian; Xu-Sheng Huang; Sheng-Yuan Yu (Infectious Diseases, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Mitoflash altered by metabolic stress in insulin-resistant skeletal muscle - Yi Ding; Huaqiang Fang; Wei Shang; Yao Xiao; Tao Sun; Ning Hou; Lin Pan; Xueting Sun; Qi Ma; Jingsong Zhou; Xianhua Wang; Xiuqin Zhang; et al. (Journal of Molecular Medicine, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Multi-muscle coordination during a challenging stance - Wen-Chieh Yang; Chih-Hsiu Cheng; Hsing-Kuo Wang; Kwan-Hwa Lin; Wei-Li Hsu (European Journal of Applied Physiology, 2015)

Experimental research on dynamic movement in strata overlying coal mines using similar material modeling - Kan Wu; Gong-Lin Cheng; Da-Wei Zhou (Arabian Journal of Geosciences, 2015)

Quercetin induces mitochondrial-derived apoptosis via reactive oxygen species-mediated ERK activation in HL-60 leukemia cells and xenograft - Wei-Jiunn Lee; Michael Hsiao; Junn-Liang Chang; Shun-Fa Yang; Tsui-Hwa Tseng; Chao-Wen Cheng; Jyh-Ming Chow; Ke-Hsun Lin; Yung-Wei Lin; Chung-Chi Liu; Liang-Ming Lee; Ming-Hsien Chien (Archives of Toxicology, 2015)

Increased relative risk of acute pancreatitis in zolpidem users - Shih-Wei Lai; Cheng-Li Lin; Kuan-Fu Liao (Psychopharmacology, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

Lysobacter lycopersici sp. nov., isolated from tomato plant Solanum lycopersicum - Shih-Yao Lin; Asif Hameed; Cheng-Zhe Wen; You-Cheng Liu; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Characterization of four B-chromosome-specific RAPDs and the development of SCAR markers on the maize B-chromosome - Kuo-Wei Kao; Chien-Yu Lin; Shu-Fen Peng; Ya-Ming Cheng (Molecular Genetics and Genomics, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Mechanism of mining subsidence in coal mining area with thick alluvium soil in China - Da-Wei Zhou; Kan Wu; Gong-Lin Cheng; Liang Li (Arabian Journal of Geosciences, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Oricola cellulosilytica gen. nov., sp. nov., a cellulose-degrading bacterium of the family Phyllobacteriaceae isolated from surface seashore water, and emended descriptions of Mesorhizobium loti and Phyllobacterium myrsinacearum - Asif Hameed; Mariyam Shahina; Wei-An Lai; Shih-Yao Lin; Li-Sen Young; You-Cheng Liu; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Neurochemical properties of the synapses between the parabrachial nucleus-derived CGRP-positive axonal terminals and the GABAergic neurons in the lateral capsular division of central nucleus of amygdala - Ya-Cheng Lu; Yan-Zhou Chen; Yan-Yan Wei; Xiao-Tao He; Xia Li; Wei Hu; Yuchio Yanagawa; Wen Wang; Sheng-Xi Wu; Yu-Lin Dong (Molecular Neurobiology, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

Folate and TAT Peptide Co-Modified Liposomes Exhibit Receptor-Dependent Highly Efficient Intracellular Transport of Payload In Vitro and In Vivo - Yaqin Zhu; Liang Cheng; Lifang Cheng; Fazhen Huang; Qing Hu; Ling Li; Chenmin Tian; Lin Wei; Dawei Chen (Pharmaceutical Research, 2014)

Analysis of non-separable spatiotemporal data with application to enterovirus study in Taiwan - Pei-Sheng Lin; Chao A. Hsiung; Chia-Wei Cheng (Environmental and Ecological Statistics, 2014)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Contents and chemical forms of heavy metals in school and roadside topsoils and road-surface dust of Beijing - Ruiping Li; Guanqing Cai; Jing Wang; Wei Ouyang; Hongguang Cheng; Chunye Lin (Journal of Soils and Sediments, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

The role of Mss11 in Candida albicans biofilm formation - Pei-Wen Tsai; Yu-Ting Chen; Cheng-Yao Yang; Hsueh-Fen Chen; Te-Sheng Tan; Tzung-Wei Lin; Wen-Ping Hsieh; Chung-Yu Lan (Molecular Genetics and Genomics, 2014)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

Typhoon-enhanced upwelling and its influence on fishing activities in the southern East China Sea - Yi Chang; Jui-Wen Chan; Yuan-Chao Angelo Huang; Wei-Quan Lin; Ming-An Lee; Kuo-Tien Lee; Cheng-Hsin Liao; Kae-Yih Wang; Yi-Chun Kuo (International Journal of Remote Sensing, 2014)

Hypohelion from China - Shuang Wang; Roland Kirschner; Yong-Wei Wang; Cheng-Lin Hou (Mycological Progress, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

Commonly Used Excipients Modulate UDP-Glucuronosyltransferase 2B7 Activity to Improve Nalbuphine Oral Bioavailability in Humans - Hong-Jaan Wang; Cheng-Huei Hsiong; Shung-Tai Ho; Min-Jen Lin; Tung-Yuan Shih; Pei-Wei Huang; Oliver Yoa-Pu Hu (Pharmaceutical Research, 2014)

Description of Niveispirillum fermenti gen. nov., sp. nov., isolated from a fermentor in Taiwan, transfer of Azospirillum irakense (1989) as Niveispirillum irakense comb. nov., and reclassification of Azospirillum amazonense (1983) as Nitrospirillum amazonense gen. nov - Shih-Yao Lin; Asif Hameed; Fo-Ting Shen; You-Cheng Liu; Yi-Han Hsu; Mariyam Shahina; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

Unpalatable weed Stellera chamaejasme L. provides biotic refuge for neighboring species and conserves plant diversity in overgrazing alpine meadows on the Tibetan Plateau in China - Wei Cheng; Geng Sun; Lin-fang Du; Yan Wu; Qun-ying Zheng; Hong-xuan Zhang; Lin Liu; Ning Wu (Journal of Mountain Science, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

A new benzopyran derivative from Pseuduvaria indochinensis Merr. - Cai-Gui Zhao; Ming-Jun Yao; Jin-Wei Yang; Ya-Lin Chai; Xiao-Dong Sun; Cheng-Shan Yuan (Natural Product Research, 2014)

Use of motor abundance in old adults in the regulation of a narrow-based stance - Wei-Li Hsu; Kwan-Hwa Lin; Rong-Sen Yang; Chih-Hsiu Cheng (European Journal of Applied Physiology, 2014)

The relationship between typhoons' peripheral circulation and ground-level ozone concentrations in central Taiwan - Wan-Li Cheng; Li-Wei Lai; Walter Den; Meng-Ting Wu; Chao-An Hsueh; Pay-Liam Lin; Chueh-Ling Pai; Yeou-Lih Yan (Environmental Monitoring and Assessment, 2014)

HOXA9 Gene Expression in Acute Myeloid Leukemia - De-Peng Li; Zhen-Yu Li; Wei Sang; Hai Cheng; Xiu-Ying Pan; Kai-Lin Xu (Cell Biochemistry and Biophysics, 2013)

The roles of two transcription factors, ABI4 and CBFA, in ABA and plastid signalling and stress responses - Zhong-Wei Zhang; Ling-Yang Feng; Jian Cheng; He Tang; Fei Xu; Feng Zhu; Zhong-Yi Zhao; Ming Yuan; Yang-Er Chen; Jian-Hui Wang; Shu Yuan; Hong-Hui Lin (Plant Molecular Biology, 2013)

Design, synthesis, and evaluation of fluorescent cell-penetrating peptidic antagonists of Grb2-SH2 for targeting MCF-7 breast cancer cells - Yu-Cheng Hsiao; Chen-Yu Lee; Yi-Jhen Lin; Shu-Huai Tsai; Kee-Ching G. Jeng; Wei-Ting Chao; Feng-Di T. Lung (Medicinal Chemistry Research, 2013)

Hesperetin protects against cardiac remodelling induced by pressure overload in mice - Wei Deng; Duan Jiang; Yi Fang; Heng Zhou; Zhihong Cheng; Yafen Lin; Rui Zhang; Jieyu Zhang; Peng Pu; Yuan Liu; Zhouyan Bian; Qizhu Tang (Journal of Molecular Histology, 2013)

A low-pH medium in vitro or the environment within a macrophage decreases the transcriptional levels of fimA, fimZ and lrp in Salmonella enterica serovar Typhimurium - Ke-Chuan Wang; Yuan-Hsun Hsu; Yi-Ning Huang; Ter-Hsin Chen; Jiunn-Horng Lin; Shih-Ling Hsuan; Maw-Sheng Chien; Wei-Cheng Lee; Kuang-Sheng Yeh (Journal of Biosciences, 2013)

Effects of extracellular calcium on viability and osteogenic differentiation of bone marrow stromal cells in vitro - Shaowen Cheng; Wei Wang; Zhongqin Lin; Ping Zhou; Xiaolei Zhang; Wei Zhang; Qingyu Chen; Dongquan Kou; Xiaozhou Ying; Yue Shen; Xiaojie Cheng; Ziming Yu; et al. (Human Cell, 2013)

An approach to evaluate groundwater recharge from streamflow and groundwater records - Wen-Jui Kung; Hsin-Fu Yeh; Hung-I Lin; Wei-Ping Chen; Cheng-Haw Lee (Geosciences Journal, 2013)

Identification of Streptomyces sp. nov. WH26 producing cytotoxic compounds isolated from marine solar saltern in China - Haizhou Liu; Lin Xiao; Jianteng Wei; John C. Schmitz; Ming Liu; Cuicui Wang; Linyou Cheng; Ning Wu; Lei Chen; Yuyan Zhang; Xiukun Lin (World Journal of Microbiology and Biotechnology, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

Application of a feature-based approach to debris flow detection by numerical simulation - Chih-Wei Lin; Cheng-Wu Chen; Wen-Ko Hsu; Chia-Yen Chen; Chung-Hung Tsai; Yi-Ping Hung; Wei-Ling Chiang (Natural Hazards, 2013)

Purification and characterization of alkaline phosphatase from the gut of sea cucumber Stichopus japonicus - Hai-Tao Wu; Dong-Mei Li; Bei-Wei Zhu; Jing-Heng Cheng; Jin-Jian Sun; Feng-Lin Wang; Yang Yang; Yu-Kun Song; Chen-Xu Yu (Fisheries Science, 2013)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

Levels of black carbon and their relationship with particle number levels—observation at an urban roadside in Taipei City - Yu-Hsiang Cheng; Ben-Tzung Shiu; Meng-Hsien Lin; Jhih-Wei Yan (Environmental Science and Pollution Research, 2013)

MicroRNA-210 targets antiapoptotic Bcl-2 expression and mediates hypoxia-induced apoptosis of neuroblastoma cells - Chung-Ching Chio; Jia-Wei Lin; Heien-An Cheng; Wen-Ta Chiu; Yuan-Hung Wang; Jhi-Joung Wang; Chung-Hsi Hsing; Ruei-Ming Chen (Archives of Toxicology, 2013)

The construction of a high-resolution visual monitoring for hazard analysis - Chi-Wei Lin; Yi-Ping Hung; Wen-Ko Hsu; Wei-Ling Chiang; Cheng-Wu Chen (Natural Hazards, 2013)

Association of the apolipoprotein M gene polymorphisms and serum lipid levels - Lynn Htet Htet Aung; Rui-Xing Yin; Dong-Feng Wu; Ting-Ting Yan; Qing Li; Jin-Zhen Wu; Wei-Xiong Lin; Cheng-Wu Liu; Shang-Ling Pan (Molecular Biology Reports, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Alpha-momorcharin, a RIP produced by bitter melon, enhances defense response in tobacco plants against diverse plant viruses and shows antifungal activity in vitro - Feng Zhu; Ping Zhang; Yan-Fa Meng; Fei Xu; Da-Wei Zhang; Jian Cheng; Hong-Hui Lin; De-Hui Xi (Planta, 2013)

The joint effect of cigarette smoking and polymorphisms on LRP5, LEPR, near MC4R and SH2B1 genes on metabolic syndrome susceptibility in Taiwan - Chuan-Wei Yang; Chia-Ing Li; Chiu-Shong Liu; Da-Tian Bau; Chih-Hsueh Lin; Wen-Yuan Lin; Tsai-Chung Li; Cheng-Chieh Lin (Molecular Biology Reports, 2013)

Infusion of Endothelial Progenitor Cells Accelerates Hematopoietic and Immune Reconstitution, and Ameliorates the Graft-Versus-Host Disease After Hematopoietic Stem Cell Transplantation - Lingyu Zeng; Chong Chen; Guoliang Song; Zhiling Yan; Shijuan Xu; Lu Jia; Shuang Ding; Jiang Cao; Wei Chen; Hai Cheng; Zhenyu Li; Wei Sang; et al. (Cell Biochemistry and Biophysics, 2012)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

Pharmacophore modeling, virtual screening, and molecular docking studies for discovery of novel Carbonic anhydrase IX inhibitors - Chun-Lin Lu; Lu Zhou; Zi-Cheng Li; Xiang Gao; Wei Zhang (Medicinal Chemistry Research, 2012)

Role of Neurotrophins in the Development and Function of Neural Circuits That Regulate Energy Homeostasis - Samira Fargali; Masato Sadahiro; Cheng Jiang; Amy L. Frick; Tricia Indall; Valeria Cogliani; Jelle Welagen; Wei-Jye Lin; Stephen R. Salton (Journal of Molecular Neuroscience, 2012)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Landslides and catchment sedimentation in the Ta-Chia River influenced by the 1999 Taiwan Chi-Chi earthquake - Keh-Jian Shou; Li-Yuan Fei; Jiin-Fa Lee; Cheng-Yueh Wei; Sheng-Tsi Huang; You-Chang Lin (International Journal of Remote Sensing, 2012)

Association between polymorphisms of the CYP11A1 gene and polycystic ovary syndrome in Chinese women - Cheng-wei Zhang; Xin-lin Zhang; Yan-jie Xia; Yun-xia Cao; Wen-jun Wang; Pei Xu; Ye-na Che; Xiao-ke Wu; Long Yi; Qian Gao; Yong Wang (Molecular Biology Reports, 2012)

An analytical investigation of a sequence of unusual springtime ozone episodes over metropolitan Taichung in 2007 - Wan-Li Cheng; Li-Wei Lai; Walter Den; Shu-Ying Wang; Pay-Liam Lin; Chueh-Ying Pai (Meteorology and Atmospheric Physics, 2012)

Occurrence of diarrheagenic Escherichia coli genes in raw water of water treatment plants - Shih-Wei Huang; Bing-Mu Hsu; Yen-Jui Su; Dar-Der Ji; Wei-Chen Lin; Jyh-Larng Chen; Feng-Cheng Shih; Po-Min Kao; Yi-Chou Chiu (Environmental Science and Pollution Research, 2012)

Disruption of Bombyx mori nucleopolyhedrovirus ORF71 (Bm71) results in inefficient budded virus production and decreased virulence in host larvae - Min-Juan Zhang; Ruo-Lin Cheng; Yi-Han Lou; Wan-Lu Ye; Tao Zhang; Xiao-Ying Fan; Hai-Wei Fan; Chuan-Xi Zhang (Virus Genes, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Caffeine’s effect on intermittent sprint cycling performance with different rest intervals - Chia-Lun Lee; Ching-Feng Cheng; Jung-Charng Lin; Hsin-Wei Huang (European Journal of Applied Physiology, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Co-occurrence of arseniasis and fluorosis due to indoor combustion of high fluorine and arsenic content coal in a rural township in northwest China: epidemiological and toxicological aspects - Guo-fang Lin; Shi-you Gong; Cheng Wei; Ji-gang Chen; Klaus Golka; Jian-hua Shen (Archives of Toxicology, 2012)

Blockade of acid-sensing ion channels protects articular chondrocytes from acid-induced apoptotic injury - Wei Hu; Fei-Hu Chen; Feng-Lai Yuan; Teng-Yue Zhang; Fan-Rong Wu; Chao Rong; Sheng Jiang; Jie Tang; Cheng-Cheng Zhang; Mei-Ying Lin (Inflammation Research, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Nicotine promotes proliferation and collagen synthesis of chondrocytes isolated from normal human and osteoarthritis patients - Xiaozhou Ying; Shaowen Cheng; Yue Shen; Xiaojie Cheng; Ferdinand An Rompis; Wei Wang; Zhongqin Lin; Qingyu Chen; Wei Zhang; Dongquan Kou; Lei Peng; Xin Qiao Tian; et al. (Molecular and Cellular Biochemistry, 2012)

Chronic alcohol intake-induced oxidative stress and apoptosis: role of CYP2E1 and calpain-1 in alcoholic cardiomyopathy - Ling Jing; Cheng-mei Jin; Shan-shan Li; Feng-min Zhang; Lin Yuan; Wei-min Li; Ying Sang; Shuang Li; Li-jun Zhou (Molecular and Cellular Biochemistry, 2012)

Effect of Boron on Osteogenic Differentiation of Human Bone Marrow Stromal Cells - Xiaozhou Ying; Shaowen Cheng; Wei Wang; Zhongqin Lin; Qingyu Chen; Wei Zhang; Dongquan Kou; Yue Shen; Xiaojie Cheng; Ferdinand An Rompis; Lei Peng; Chuan zhu Lu (Biological Trace Element Research, 2011)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Replicative senescence of human bone marrow and umbilical cord derived mesenchymal stem cells and their differentiation to adipocytes and osteoblasts - HuanChen Cheng; Lin Qiu; Jun Ma; Hao Zhang; Mei Cheng; Wei Li; Xuefei Zhao; Keyu Liu (Molecular Biology Reports, 2011)

Involvement of OsNPR1/NH1 in rice basal resistance to blast fungus Magnaporthe oryzae - Jia-Xun Feng; Lin Cao; Juan Li; Cheng-Jie Duan; Xue-Mei Luo; Ning Le; Haihong Wei; Shujia Liang; Chengcai Chu; Qinghua Pan; Ji-Liang Tang (European Journal of Plant Pathology, 2011)

Assessing nitrate contamination and its potential health risk to Kinmen residents - Chen-Wuing Liu; Chun-Nan Lin; Cheng-Shin Jang; Min-Pei Ling; Jeng-Wei Tsai (Environmental Geochemistry and Health, 2011)

Identification and characterization of Sox genes in the silkworm, Bombyx mori - Ling Wei; Daojun Cheng; Dong Li; Meng Meng; Lina Peng; Lin Tang; Minhui Pan; Zhonghuai Xiang; Qingyou Xia; Cheng Lu (Molecular Biology Reports, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Acacetin inhibits the invasion and migration of human non-small cell lung cancer A549 cells by suppressing the p38α MAPK signaling pathway - Shang-Tao Chien; Su-Shun Lin; Cheng-Kun Wang; Yuan-Bin Lee; Kun-Shiang Chen; Yao Fong; Yuan-Wei Shih (Molecular and Cellular Biochemistry, 2011)

Artesunate inhibits growth and induces apoptosis in human osteosarcoma HOS cell line in vitro and in vivo - Qiang Xu; Zhao-xu Li; Hui-qin Peng; Zheng-wang Sun; Rui-lin Cheng; Zhao-ming Ye; Wei-xu Li (Journal of Zhejiang University-SCIENCE B, 2011)

Vulnerability of large city and its implication in urban planning: A perspective of intra-urban structure - Chunliang Xiu; Lin Cheng; Wei Song; Wei Wu (Chinese Geographical Science, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

Erratum to: Super-ensemble of three RCMs for climate projection over East Asia and Taiwan - Chung-Ming Liu; Ming-Chin Wu; Sahana Paul; Ying-Chen Chen; Shu-Hua Lin; Wei-Shiang Lin; Yen-Chih Lee; Huang-Hsung Hsu; Ren-Yow Tzeng; Cheng-Ta Chen (Theoretical and Applied Climatology, 2011)

Super-ensemble of three RCMs for climate projection over East Asia and Taiwan - Chung-Ming Liu; Ming-Chin Wu; Sahana Paul; Ying-Chen Chen; Shu-Hua Lin; Wei-Shiang Lin; Yen-Chih Lee; Huang-Hsung Hsu; Ren-Yow Tseng; Cheng-Ta Chen (Theoretical and Applied Climatology, 2011)

Honokiol: an effective inhibitor of high-glucose-induced upregulation of inflammatory cytokine production in human renal mesangial cells - Jian-Ping Wu; Wei Zhang; Fang Wu; Ying Zhao; Lin-Fang Cheng; Jun-Jun Xie; Hang-Ping Yao (Inflammation Research, 2010)

Overexpression of constitutively active BMP-receptor-IB in mouse skin causes an ichthyosis-vulgaris-like disease - Xueyan Yu; Ramón A. Espinoza-Lewis; Cheng Sun; Lisong Lin; Fenglei He; Wei Xiong; Jing Yang; Alun Wang; YiPing Chen (Cell and Tissue Research, 2010)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

High prevalence of a novel porcine bocavirus in weanling piglets with respiratory tract symptoms in China - Shaolun Zhai; Cheng Yue; Zuzhang Wei; Jinxue Long; Duoliang Ran; Tao Lin; Yu Deng; Lv Huang; Lichang Sun; Haihong Zheng; Fei Gao; Hao Zheng; et al. (Archives of Virology, 2010)

The Chebyshev spectral element method using staggered predictor and corrector for elastic wave simulations - Cheng-Xuan Che; Xiu-Ming Wang; Wei-Jun Lin (Applied Geophysics, 2010)

Mesoscale barotropic instability of vortex Rossby waves in tropical cyclones - Wei Zhong; Han-Cheng Lu; Da-Lin Zhang (Advances in Atmospheric Sciences, 2010)

Assessment of the role of brine shrimp Artemia in white spot syndrome virus (WSSV) transmission - Jia-Song Zhang; Shuang-Lin Dong; Yun-Wei Dong; Xiang-Li Tian; Yi-Cheng Cao; Zuo-Jia Li; Dong-Chun Yan (Veterinary Research Communications, 2010)

Ameliorative effects of Vaccaria segetalis extract on osteopenia in ovariectomized rats - Chun-Ching Shih; Cheng-Hsiu Lin; Wei-Li Lin (Journal of Natural Medicines, 2009)

An ANN–RTS smoother scheme for accurate INS/GPS integrated attitude determination - Kai-Wei Chiang; Yung-Cheng Lin; Yun-Wen Huang; Hsiu-Wen Chang (GPS Solutions, 2009)

Early transcriptional deregulation of hepatic mitochondrial biogenesis and its consequent effects on murine cholestatic liver injury - Mao-Meng Tiao; Tsu-Kung Lin; Cha-Wei Liou; Pei-Wen Wang; Jin-Bor Chen; Fang-Ying Kuo; Chao-Cheng Huang; Yao-Min Chou; Jiin-Haur Chuang (Apoptosis, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Cistanche deserticola Ma cultivated as a new crop in China - Rong Xu; Jun Chen; Shi-Lin Chen; Tong-Ning Liu; Wei-Cheng Zhu; Jiang Xu (Genetic Resources and Crop Evolution, 2009)

Effect of calmidazolium on [Ca2+]i and viability in human hepatoma cells - Wei-Chuan Liao; Chorng-Chih Huang; He-Hsiung Cheng; Jue-Long Wang; Ko-Long Lin; Jin-Shiung Cheng; Kuo-Liang Chai; Pei-Te Hsu; Jeng-Yu Tsai; Yi-Chien Fang; Yih-Chau Lu; Hong-Tai Chang; et al. (Archives of Toxicology, 2009)

Supplementary tests for confirmation of brain death - Wei-lung Cheng; Kao-chang Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Compositions and source apportionments of atmospheric aerosol during Asian dust storm and local pollution in central Taiwan - Man-Ting Cheng; Wei-Chun Chou; Chia-Pin Chio; Shih-Chieh Hsu; Yi-Ru Su; Pei-Hsuan Kuo; Ben-Jei Tsuang; Shuen-Hsin Lin; Charles C.-K. Chou (Journal of Atmospheric Chemistry, 2008)

Expression of a Bacillus thuringiensis toxin (cry1Ab) gene in cabbage (Brassica oleracea L. var. capitata L.) chloroplasts confers high insecticidal efficacy against Plutella xylostella - Cheng-Wei Liu; Chin-Chung Lin; Jinn-Chin Yiu; Jeremy J. W. Chen; Menq-Jiau Tseng (Theoretical and Applied Genetics, 2008)

White-spot disease of Chinese soft-shelled turtles (Trionyx sinens) caused by Paecilomyces lilacinus - Xiao-liang Li; Chu-long Zhang; Wei-huan Fang; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Impact of genetic polymorphisms of leptin and TNF-α on rosiglitazone response in Chinese patients with type 2 diabetes - Hai-Ling Liu; Yang-Gen Lin; Jing Wu; Hong Sun; Zhi-Cheng Gong; Ping-Cheng Hu; Ji-Ye Yin; Wei Zhang; Dan Wang; Hong-Hao Zhou; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2008)

Pravastatin attenuates carboplatin-induced cardiotoxicity via inhibition of oxidative stress associated apoptosis - Ching-Feng Cheng; Shu-Hui Juan; Jin-Jer Chen; Ying-Chi Chao; His-Hsien Chen; Wei-Shiung Lian; Chun-Yi Lu; Chung-I Chang; Ted-H Chiu; Heng Lin (Apoptosis, 2008)

Expression of a Bacillus thuringiensis toxin (cry1Ab) gene in cabbage (Brassica oleracea L. var. capitata L.) chloroplasts confers high insecticidal efficacy against Plutella xylostella - Cheng-Wei Liu; Chin-Chung Lin; Jinn-Chin Yiu; Jeremy J. W. Chen; Menq-Jiau Tseng (Theoretical and Applied Genetics, 2008)

Complete sequence analysis reveals two distinct poleroviruses infecting cucurbits in China - Hai-ying Xiang; Qiao-xia Shang; Cheng-gui Han; Da-wei Li; Jia-lin Yu (Archives of Virology, 2008)

Four new aromatic allenic ethers from the fungus Xylaria sp. No. 2508 - San-Yong Wang; Zhong-Liang Xu; Wei-Wei Mao; Zhi-Gang She; Ni Tan; Chun-Rong Li; Yong-Cheng Lin (Natural Product Research, 2008)

Hypoxia-induced compensatory effect as related to Shh and HIF-1α in ischemia embryo rat heart - Jin-Ming Hwang; Yi-Jiun Weng; James A. Lin; Da-Tian Bau; Fu-Yang Ko; Fuu-Jen Tsai; Chang-Hai Tsai; Chieh-Hsi Wu; Pei-Cheng Lin; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2008)

Protective immunity of E. coli-synthesized NS1 protein of Japanese encephalitis virus - Cheng-Wen Lin; Kuang-Ting Liu; Hong-Da Huang; Wei-June Chen (Biotechnology Letters, 2008)

Apoptosis induced by ardipusilloside III through BAD dephosphorylation and cleavage in human glioblastoma U251MG cells - Hong Lin; Xiang Zhang; Guang Cheng; Hai-Feng Tang; Wei Zhang; Hai-Ning Zhen; Jin-Xiang Cheng; Bo-Lin Liu; Wei-Dong Cao; Wen-Peng Dong; Peng Wang (Apoptosis, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Stable chloroplast transformation in cabbage (Brassica oleracea L. var. capitata L.) by particle bombardment - Cheng-Wei Liu; Chin-Chung Lin; Jeremy J. W. Chen; Menq-Jiau Tseng (Plant Cell Reports, 2007)

Interleukin-18 gene polymorphism, but not interleukin-2 gene polymorphism, is associated with rheumatoid arthritis - Cheng-Chun Lee; Wei-Yong Lin; Lei Wan; Yuhsin Tsai; Ying-Ju Lin; Chang-Hai Tsai; Chung-Ming Huang; Fuu-Jen Tsai (Immunogenetics, 2007)

Callus of Securinega suffruticosa , a cell line accumulates dextro Securinega alkaloids - Wei Yuan; Ping Zhu; Kedi Cheng; Chao Meng; Lin Ma; Feng Wu; Huixin Zhu (Natural Product Research, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Inhibitory effect of trilinolein on endothelin-1-induced c-fos gene expression in cultured neonatal rat cardiomyocytes - Hung-Yu Yang; Ju-Chi Liu; Yen-Ling Chen; Cheng-Hsien Chen; Heng Lin; Jia-Wei Lin; Wen-Ta Chiu; Jin-Jer Chen; Tzu-Hurng Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

A thermostable leucine aminopeptidase from Bacillus kaustophilus CCRC 11223 - Long-Liu Lin; Wen-Hwei Hsu; Cheng-Pu Wu; Meng-Chun Chi; Wei-Mou Chou; Hui-Yu Hu (Extremophiles, 2004)

Microsatellite polymorphism in promoter of heme oxygenase-1 gene is associated with susceptibility to coronary artery disease in type 2 diabetic patients - Ying-Hwa Chen; Shing-Jong Lin; Ming-Wei Lin; Hui-Ling Tsai; San-San Kuo; Jaw-Wen Chen; Min-Ji Charng; Tao-Cheng Wu; Lung-Ching Chen; Philip Ding; Wen-Harn Pan; Yuh-Shan Jou; et al. (Human Genetics, 2002)

Daily changes in components of xanthophyll cycle and antioxidant systems in leaves of rice at different developing stage - Cheng-Wei Yang; Yi-Zhu Chen; Chang-Lian Peng; Duan Jun; Gui-Zhu Lin (Acta Physiologiae Plantarum, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Direct determination of selenium in human blood plasma and seminal plasma by graphite furnace atomic absorption spectrophotometry and clinical application - Te-Hsien Lin; Wei-Chang Tseng; Su-Ya Cheng (Biological Trace Element Research, 1998)